Subcluster EK2 Annotation Report - McFerrin, Harris; Bollivar, David; Gurney, Susan; Adewumi, Olubusuyi; Edgington, Nicholas; Mayoral, Jaime; Rudner, Adam; Balish, Mitchell (QUBES, 2026)
This report describes features of actinobacteriophages assigned to subcluster EK2. Additional phages may have been added to the phagesDB database since the generation of this report.
Keywords: Annotation; Feature (linguistics); Genetic data; Genome; Human genome; dept.bio

Subcluster AZ1 Annotation Report - Beyer, Andrea; Bouklas, Tejas; Dojs, Madeline; Edgington, Nicholas; Harrison, Melinda; Rudner, Adam; Swerdlow, Sarah; Delesalle, Veronique; Page, Shallee (QUBES, 2025)
This report describes features of actinobacteriophages assigned to subcluster AZ1. Additional phages may have been added to the phagesDB database since the generation of this report.
Keywords: Annotation; DNA; Genome; Genomics; Human genome; Selection (genetic algorithm); dept.bio

Tissue-specific I-Smad mechanisms revealed by structure-function analysis in Drosophila - Simoncek, Ania; Sviridoff, Steven; Hays, J.; Graichen, Noah; Sulkowski, Mikolaj (bioRxiv (Cold Spring Harbor Laboratory), 2025)
Abstract Inhibitory Smads (I-Smads) regulate TGF-β/BMP signaling through multiple distinct mechanisms, but whether different tissues preferentially employ specific mechanisms remains unknown. To address this question, we performed structure-function analyses of the Drosophila I-Smad Dad and its vertebrate orthologs Smad6 and Smad7 in neural and wing tissues, measuring in vivo outputs of BMP signaling. We identified a critical 24-amino acid putative DNA-binding domain (DNABD) within the MH1 domain of the Drosophila I-Smad, Dad, that is essential for inhibitory function in wing tissue but unessential in neural tissue. Structural analyses revealed that ΔDNABD disrupts a beta hairpin structure homologous to R-Smad DNA-binding regions. We also found that Dad requires an intact MH1 domain to disrupt wing development, whereas either MH1 or MH2 can independently disrupt BMP signaling in motor neurons. These findings support a model where Dad functions through MH1-mediated transcriptional regulation in wing primordium, but through multiple mechanisms in neurons. Comparative analysis revealed that vertebrate I-Smad orthologs also show tissue-specific activity patterns, with structural predictions suggesting that Smad6 retains ancestral DNA-binding capacity while Smad7 has evolved enhanced MH2-mediated functions. These results reveal context-dependent mechanisms of I-Smads that further the understanding of TGF-β/BMP pathway regulation.
Keywords: Biology; Cell biology; Context (archaeology); Decapentaplegic; Drosophila melanogaster; Function (biology); Gene; Genetics; Primordium; SMAD; Signal transduction; Vertebrate; dept.bio

Comparative genomic analysis of Cluster AZ Arthrobacter phages - Freise, Amanda; Furlong, Kieran; Klyczek, Karen; Beyer, Andréa; Chong, Rebecca; Edgington, Nicholas; Gibb, Bryan; Swerdlow, Sarah; Bendele, Madison; Cobb, Isobel; Mitchell, Zachary; Cresawn, Steven; et al. (bioRxiv (Cold Spring Harbor Laboratory), 2025)
Abstract Bacteria in the Arthrobacter genus belong to the phylum Actinobacteria and are primarily soil-dwelling. Over 600 bacteriophages infecting Arthrobacter hosts have been isolated and sequenced, and genomic analyses show these phages to be highly diverse with mosaic genome architectures. We describe here a group of 32 Arthrobacter phages grouped in Cluster AZ, isolated on four different Arthrobacter strains all with siphoviral morphologies. The Cluster AZ phages exhibit a spectrum of diversity and can be subdivided into four subclusters. The diversity in minor tail protein and endolysin genes correlates partly with isolation host strain and may be predictive of the host range of these phages. Most of the Cluster AZ phages are temperate, form stable lysogens, and encode an integrase; however, an immunity repressor gene has not been identified. The intracluster diversity was analyzed in-depth at the whole genome level and through individual genes. As more Arthrobacter phages are isolated and analyzed they continue to provide new insights into phage evolution.
Keywords: Arthrobacter; Bacteria; Biology; Cluster (spacecraft); Computational biology; Computer science; Genetics; dept.bio

Alternative splicing and parallel patterns of gene expression underlie population and life history divergence in an amphibian - Hu, Juntao; Ren, Xingyue; Barrett, Rowan; Samma, Eman; Sulkowski, Mikloaj; Brady, Steven (2025)
Keywords: Alternative splicing; Amphibian; Biology; Computational biology; Demography; Divergence (linguistics); Ecology; Evolutionary biology; Gene; Gene expression; Genetics; Life history; Messenger RNA; Population; RNA splicing; Sociology; dept.bio

Genomic comparison of the temperate coral Astrangia poculata with tropical corals yields insights into winter quiescence, innate immunity, and sexual reproduction - Stankiewicz, Kathryn; Guiglielmoni, Nadège; Kitchen, Sheila; Flot, Jean‐François; Barott, Katie; Davies, Sarah; Finnerty, John; Grace, Sean; Kaufman, Leslie; Putnam, Hollie; Rotjan, Randi; Sharp, Koty; et al. (G3 Genes Genomes Genetics, 2025)
Facultatively symbiotic corals provide important experimental models to explore the establishment, maintenance, and breakdown of the mutualism between corals and members of the algal family Symbiodiniaceae. Here, we report the de novo chromosome-scale genome assembly and annotation of the facultatively symbiotic, temperate coral Astrangia poculata. Though widespread segmental/tandem duplications of genomic regions were detected, we did not find strong evidence of a whole-genome duplication event. Comparison of the gene arrangement between As. poculata and the tropical coral Acropora millepora revealed considerable conserved colinearity despite ∼415 million years of divergence. Gene families related to sperm hyperactivation and innate immunity, including lectins, were found to contain more genes in Ac. millepora relative to As. poculata. Sperm hyperactivation in Ac. millepora is expected given the extreme requirements of gamete competition during mass spawning events in tropical corals, while lectins are important in the establishment of coral-algal symbiosis. By contrast, gene families involved in sleep promotion, feeding suppression, and circadian sleep/wake cycle processes were expanded in As. poculata. These expanded gene families may play a role in As. poculata's ability to enter a dormancy-like state (winter quiescence) to survive freezing temperatures at the northern edges of the species' range.
Keywords: Biology; Coral; Ecology; Evolutionary biology; Gene; Genetics; Genome; dept.bio

Isolated Abelisaurid Teeth from Gondwana and Dental Evolution in Abelisauridae - Hendrickx, Christophe; Núñez, Matías Soto; Araújo, Ricardo; Meso, Jorge G.; Maganuco, Simone; Ben-Salahuddin, Adé (Ameghiniana, 2025)
Abelisauridae were medium to large-bodied carnivorous dinosaurs with short, ornamented skulls, poorly recurved ziphodont teeth, and reduced forelimbs. They were the dominant terrestrial carnivores in many Gondwanan ecosystems during the Cretaceous. Their Jurassic origin, primarily based on the putative abelisaurid Eoabelisaurus from the Early Jurassic of Patagonia, remains debated, with many authors considering Abelisauridae as a strictly Cretaceous theropod radiation. Here, we describe several historically and stratigraphically important isolated theropod teeth from Gondwana, identified as belonging to abelisaurids using new cladistic and machine learning methods. Dental evolution in Abelisauridae was additionally explored using an updated version of a dentition-based data matrix focused on ceratosaurs. Results of this study show that the evolution of the dentition in abelisaurids was marked by a decrease in size of the mesialmost dentary teeth and the displacement of the tallest crowns towards the middle part of the maxilla. Two isolated abelisaurid teeth from the Late Cretaceous of India and Patagonia were also identified as the earliest published record of a non-avian theropod in Asia and an abelisaurid in Argentina, respectively. More importantly, isolated theropod teeth confidently referred to Abelisauridae from the Middle Jurassic of Madagascar provide additional support for the emergence of this clade in Gondwana before the Late Jurassic and reveal that the acquisition of abelisaurid dental traits occurred early in the evolutionary history of one of the most successful radiations of non-avian theropods from Europe and the Southern Hemisphere. © 2025 Asociación Paleontológica Argentina (APA)
Keywords: Biological evolution; Ceratosauria; Corona; Crown; Dentición; Dentition; Gondwana; Hemisferio Sur; Mandible (arthropod mouthpart); Phylogenetics; Southern Hemisphere; Terópodos; Theropoda; dept.bio

Tissue-specific I-Smad mechanisms revealed by structure–function analysis in Drosophila - Simoncek, Ania; Sviridoff, Steven; Hays, Joshua; Graichen, Noah; Sulkowski, Mikolaj (Life Science Alliance, 2026)
Inhibitory Smads (I-Smads) regulate TGF-β/BMP signaling through multiple distinct mechanisms, but whether different tissues preferentially employ specific mechanisms remains unknown. To address this question, we performed structure–function analyses of the Drosophila I-Smad, Dad, and its vertebrate orthologs Smad6 and Smad7 in neural and wing tissues, measuring outputs of BMP signaling in vivo. We identified a 24–amino acid putative DNA-binding domain within the MH1 domain of Dad that is essential for inhibitory function in wing tissue but unessential in neural tissue. Structural analyses revealed that ΔDNA-binding domain disrupts a β-hairpin structure homologous to R-Smad DNA-binding regions. We also found that Dad requires an intact MH1 domain to disrupt wing development, whereas either MH1 or MH2 can independently disrupt BMP signaling in motor neurons. These findings support a model where Dad functions through MH1-mediated transcriptional regulation in wing primordium, but through multiple mechanisms in neurons. Comparative analysis revealed that vertebrate I-Smad orthologs also show tissue-specific activity patterns, with structural predictions suggesting that Smad6 retains ancestral DNA-binding capacity, whereas Smad7 has evolved enhanced MH2-mediated functions. These results reveal context-dependent mechanisms of I-Smads that further the understanding of TGF-β/BMP pathway regulation.
Keywords: Domain (mathematical analysis); Function (biology); Homologous chromosome; Signal transduction; Vertebrate; Wing; dept.bio

Effects of intraspecies and interspecies competition on genetic device construction and performance - Thompson, Samantha; Williams, Adrian; Dill, Veronica; Marshall, Deven; Sawyer, Emily; Alexander, Mason; Rahn-Lee, Lilah; Shih, Joseph (mSphere, 2025)
ABSTRACT One exciting class of future genetic devices could be those deployed in microbes that join complex microbial environments in the wild. We sought to determine whether genetic parts designed for monoculture are predictable when used in co-culture by testing constitutive Anderson promoters driving the expression of chromoproteins from a plasmid. In Escherichia coli monoculture, a high copy number origin of replication causes stochastic expression regardless of promoter strength, and high constitutive Anderson promoter strength leads to selection for inactivating mutations, resulting in inconsistent chromoprotein expression. Medium- and low-strength constitutive Anderson promoters function more predictably in E. coli monoculture but experience an increase in inactivating mutations when grown in co-culture over many generations with Pseudomonas aeruginosa . Expression from regulated promoters instead of constitutive Anderson promoters can lead to stable expression in a complex wastewater culture. Overall, we show intraspecies selection for inactivating mutations due to a competitive growth advantage for E. coli that do not express the genetic device compared to their peers that retain the functional device. We show additional interspecies selection against the functional device when E. coli is co-cultured with another organism. Together, these two selection pressures create a significant barrier to genetic device function in microbial communities that we overcome by utilizing a regulated E. coli promoter. Future strategies for genetic device design in microorganisms that need to function in a complex microbial environment should focus on regulated promoters and/or strategies that give the microorganism carrying the device a selective or growth advantage. IMPORTANCE First-generation biotechnology focused on genetic devices designed for use in monoculture conditions. One class of next-generation biotechnology devices could be designed to function in complex ecosystems with other organisms, so we sought to create conditions where the genetic device retained function when the organism carrying it is in co-culture with other organisms. We discovered that when the genetic device is a significant resource burden on the organism carrying the device, mutations will be selected for due to intraspecies and interspecies selection pressures, and the device will be rendered non-functional. Therefore, genetic device design for complex ecosystems in next-generation biotechnology needs to balance functionality of the genetic device with the need to reduce resource burden on the organism carrying it.
Keywords: Competition (biology); Function (biology); Genetic diversity; Genetic screen; Model organism; Organism; Resource (disambiguation); Selection (genetic algorithm); chromoproteins; dept.bio; genetics; interspecies selective pressure; microbial communities; promoters

Alternative Splicing and Gene Expression Variation Underlie Population and Life History Differences in an Amphibian - Hu, Juntao; Ren, Xingyue; Barrett, Rowan; Samma, Eman; Sulkowski, Mikolaj; Brady, Steven (Ecology and Evolution, 2025)
ABSTRACT Phenotypic variation is common across life history and among populations occupying different environments, yet the molecular mechanisms underlying these axes of divergence remain poorly understood. Much work has focused on gene expression as a link between genetic variation, environmental variation, and phenotypes, but post‐transcriptional processes such as alternative splicing—which affect how transcripts are assembled rather than how much of a transcript is produced—are increasingly recognized as additional modulators of plasticity and adaptation. Here, we examined gene expression and alternative splicing together in the wood frog ( Rana sylvatica ), an amphibian with a complex life cycle whose populations differ across replicated gradients of road adjacency and associated pollution. We found extensive transcriptomic differences between hatchlings and adults, with thousands of genes differentially expressed or spliced. Individuals clustered strongly by population for both expression and splicing. Differences at the habitat level were less extensive, but revealed two differentially expressed genes ( HSP70 and Gpsm2 ) and one differentially spliced gene ( Cd82 ) that consistently distinguished roadside and woodland populations. Overall, genetic differentiation between populations was low, suggesting that phenotypic and transcriptomic differences likely emerge in the presence of gene flow and reflect plastic responses. Together, these results highlight transcriptomic plasticity as an important mechanism shaping variation across both development and population differentiation.
Keywords: Alternative splicing; Amphibian; Gene; Gene expression; Genetic variation; Phenotypic plasticity; Population; Transcriptome; alternative splicing; dept.bio; gene expression; local adaptation; maladaptation; population divergence

Freshwater salinization leads to sluggish, bloated frogs and small, cramped embryos but adaptive countergradient variation in eggs - Brady, Steven; Kang, Samantha; Wang, Z.; Layne, Craig; Calsbeek, Ryan (Integrative and Comparative Biology, 2025)
Keywords: Amphibian; Aquatic ecosystem; Biology; Cottus; Ecology; Ecosystem; Freshwater ecosystem; Habitat; Population; Salinity; Soil salinity; dept.bio

Freshwater salinization of seasonal ponds: high salinity and stratification threaten critical, overlooked habitats - Brady, Steven; Benoit, Gaboury (Environmental Science & Technology, 2025)
Keywords: Biology; Critical habitat; Ecology; Environmental science; Fishery; Geology; Habitat; Oceanography; Salinity; Soil salinity; Stratification (seeds); dept; bio; peer-reviewed

The evolution of femoral morphology in giant non-avian theropod dinosaurs - Pintore, Romain; Hutchinson, John R.; Bishop, Peter J.; Tsai, Henry P.; Houssaye, Alexandra (Paleobiology, 2024)
Theropods are obligate bipedal dinosaurs that appeared 230 Ma and are still extant as birds. Their history is characterized by extreme variations in body mass, with gigantism evolving convergently between many lineages. However, no quantification of hindlimb functional morphology has shown whether these body mass increases led to similar specializations between distinct lineages. Here we studied femoral shape variation across 41 species of theropods (n = 68 specimens) using a high-density 3D geometric morphometric approach. We demonstrated that the heaviest theropods evolved wider epiphyses and a more distally located fourth trochanter, as previously demonstrated in early archosaurs, along with an upturned femoral head and a mediodistal crest that extended proximally along the shaft. Phylogenetically informed analyses highlighted that these traits evolved convergently within six major theropod lineages, regardless of their maximum body mass. Conversely, the most gracile femora were distinct from the rest of the dataset, which we interpret as a femoral specialization to “miniaturization” evolving close to Avialae (bird lineage). Our results support a gradual evolution of known “avian” features, such as the fusion between lesser and greater trochanters and a reduction of the epiphyseal offset, independent from body mass variations, which may relate to a more “avian” type of locomotion (more knee than hip driven). The distinction between body mass variations and a more “avian” locomotion is represented by a decoupling in the mediodistal crest morphology, whose biomechanical nature should be studied to better understand the importance of its functional role in gigantism, miniaturization, and higher parasagittal abilities.
Keywords: dept.bio; open-access; peer-reviewed

Population origin and heritable effects mediate road salt toxicity and thermal stress in an amphibian - Conner, L.M.; Goedert, D.; Fitzpatrick, S.W.; Fearnley, A.; Gallagher, E.L.; Peterman, J.D.; Forgione, M.E.; Kokosinska, S.; Hamilton, M.; Masala, L.A.; Merola, N.; Rico, H.; et al. (Chemosphere, 2024)
Human impacts on wild populations are numerous and extensive, degrading habitats and causing population declines across taxa. Though these impacts are often studied individually, wild populations typically face suites of stressors acting concomitantly, compromising the fitness of individuals and populations in ways poorly understood and not easily predicted by the effects of any single stressor. Developing understanding of the effects of multiple stressors and their potential interactions remains a critical challenge in environmental biology. Here, we focus on assessing the impacts of two prominent stressors associated with anthropogenic activities that affect many organisms across the planet – elevated salinity (e.g., from road de-icing salt) and temperature (e.g. from climate change). We examined a suite of physiological traits and components of fitness across populations of wood frogs originating from ponds that differ in their proximity to roads and thus their legacy of exposure to pollution from road salt. When experimentally exposed to road salt, wood frogs showed reduced survival (especially those from ponds adjacent to roads), divergent developmental rates, and reduced longevity. Family-level effects mediated these outcomes, but high salinity generally eroded family-level variance. When combined, exposure to both temperature and salt resulted in very low survival, and this effect was strongest in roadside populations. Taken together, these results suggest that temperature is an important stressor capable of exacerbating impacts from a prominent contaminant confronting many freshwater organisms in salinized habitats. More broadly, it appears likely that toxicity might often be underestimated in the absence of multi-stressor approaches. © 2024 Elsevier Ltd
Keywords: Amphibians; Climate change; Local adaptation; Maladaptation; Pollution; Road salt; dept.bio; peer-reviewed

Population Origin and Heritable Effects Mediate Road Salt Toxicity and Thermal Stress - Conner, Lauren M.; Goedert, Debora; Fitzpatrick, Sarah W.; Fearnley, Amber; Gallagher, Emma L.; Peterman, Jessica D.; Forgione, Mia E.; Kokosinska, Sophia; Hamilton, Malik; Masala, Lydia A.; Merola, Neil; Rico, Hennesy; et al. (2023)
Human impacts on wild populations are numerous and extensive, degrading habitats and causing population declines across taxa. Though these impacts are often studied individually, wild populations typically face suites of stressors acting concomitantly, compromising the fitness of individuals and populations in ways poorly understood and not easily predicted by the effects of any single stressor. Developing understanding of the effects of multiple stressors and their potential interactions remains a critical challenge in environmental biology. Here, we focus on assessing the impacts of two prominent stressors affecting many organisms across the planet – elevated salinity (an increasingly common pollutant in freshwater habitats) and elevated temperature. We examined a suite of physiological traits and components of fitness across populations of wood frogs originating from ponds that differ in their proximity to roads and thus their legacy of exposure to road salt pollution. When experimentally exposed to road salt, wood frogs showed reduced survival, especially those from ponds adjacent to roads, and delayed time to metamorphosis. Family level effects mediated these outcomes, but high salinity generally eroded family level variance. When combined, exposure to both temperature and salt resulted in very low survival, and this effect was strongest in roadside populations. Taken together, these results suggest that temperature is an important stressor capable of exacerbating impacts from a prominent contaminant confronting many freshwater organisms in salinized habitats. More broadly, it appears likely that toxicity might often be underestimated in the absence of multi-stressor approaches.
Keywords: Climate change; Maladaptation; SCSU-student; amphibians; dept.bio; local adaptation; pollution; road salt

Genomic comparison of the temperate coral Astrangia poculata with tropical corals yields insights into winter quiescence, innate immunity, and sexual reproduction - Stankiewicz, Kathryn H.; Guiglielmoni, Nadège; Kitchen, Sheila A.; Flot, Jean-François; Barott, Katie L.; Davies, Sarah W.; Finnerty, John R.; Grace, Sean P.; Kaufman, Leslie S.; Putnam, Hollie M.; Rotjan, Randi D.; Sharp, Koty H.; et al. (bioRxiv, 2023)
Facultatively symbiotic corals provide important experimental models to explore the establishment, maintenance, and breakdown of the mutualism between corals and members of the algal family Symbiodiniaceae. The temperate coral Astrangia poculata is one such model as it is not only facultatively symbiotic, but also occurs across a broad temperature and latitudinal gradient. Here, we report the de novo chromosome-scale assembly and annotation of the A. poculata genome. Though widespread segmental/tandem duplications of genomic regions were detected, we did not find strong evidence of a whole genome duplication (WGD) event. Comparison of the gene arrangement between A. poculata and the tropical coral Acropora millepora revealed 56.38% of the orthologous genes were conserved in syntenic blocks despite ∼415 million years of divergence. Gene families related to sperm hyperactivation and innate immunity, including lectins, were found to contain more genes in A. millepora relative to A. poculata. Sperm hyperactivation in A. millepora is expected given the extreme requirements of gamete competition during mass spawning events in tropical corals, while lectins are important in the establishment of coral-algal symbiosis. By contrast, gene families involved in sleep promotion, feeding suppression, and circadian sleep/wake cycle processes were expanded in A. poculata. These expanded gene families may play a role in A. poculata’s ability to enter a dormancy-like state (“winter quiescence”) to survive freezing temperatures at the northern edges of the species’ range.
Pages: 2023.09.22.558704 Section: New Results
Keywords: dept.bio

Quiescence and Coral Biology: Will Warming Waters Result in a New Understanding on Coral Resiliency? - Grace, Sean P. (2018)
The objectives of this sabbatical were to examine the resilience of temperate corals (Astrangia poculata, Ellis & Solander 1787) and to address the following questions: 1. Do corals exhibit quiescence at warmer temperatures?; 2. Does Astrangia poculata exhibit quiescence across their geographic range?; 3. Does the microbial population on corals change during quiescence?; and 4. Does temperature cause a change in symbiotic state in A. poculata?
Keywords: dept.bio; faculty_collection; sabbatical_report

North American Songbirds: Identify the Most Common Songbirds and Hear Their Calls on Your Smartphone - Proctor, Noble S. (Cool Springs Press, 2014)
"Provides information about the habits and habitats of North America's 100 most common birds. Includes information on how to attract birds as well as how to identify their songs with a QR code that links directly to a recording of each bird's song"–
Keywords: Identification; Identification; Birdsongs; North America; Songbirds; dept.bio; faculty_collection

A Field Guide to the Southeast Coast & Gulf of Mexico: Coastal Habitats, Seabirds, Marine Mammals, Fish, & Other Wildlife - Proctor, Noble S. (Yale University Press, 2011)
"This superb book, with its unique focus on the entire marine coastal environment, is the most comprehensive and up-to-date field guide available on the southeastern Atlantic Coast and the Gulf Coast. Not just for beachgoers, the book is essential for birders, whale watchers, fishers, boaters, scuba divers and snorkelers, and shoreline visitors" –Publisher description.
Keywords: Atlantic Coast (South Atlantic States); Coastal animals; Guidebooks; Guidebooks; Atlantic Coast (South Atlantic States); Guidebooks; Coastal ecology; Guidebooks; Marine ecology; Guidebooks; Mexico; Gulf of; Gulf States; Identification; Coastal animals; Identification; Coastal ecology; Identification; Marine animals; Mexico; Gulf of; South Atlantic States; dept.bio; faculty_collection

The Songbirds Bible: A Visual Directory of 100 of the Most Popular Songbirds in North America - Proctor, Noble S. (Ronnie Sellers, 2006)
Keywords: Identification; Identification; Birdsongs; North America; Songbirds; dept.bio; faculty_collection

A Field Guide to North Atlantic Wildlife: Marine Mammals, Seabirds, Fish, and Other Sea Life - Proctor, Noble S.; Lynch, Patrick J. (Yale University Press, 2005)
Keywords: Atlantic Coast (Canada); Atlantic Coast (U.S.); Identification; Identification; Marine algae; Identification; Marine animals; Marine animals; dept.bio; faculty_collection

A Revision of the Genus Leptophlebia Westwood in North America (ephemeroptera:leptophlebiidae:leptophlebiinae) - Burian, Steven K. (Ohio Biological Survey, College of Biological Sciences, Ohio State University, 2001)
Keywords: Classification; Identification; Leptophlebia; Leptophlebia; North America; dept.bio; faculty_collection

Kelp carbon sink potential decreases with warming due to accelerating decomposition - Filbee-Dexter, Karen; Feehan, Colette J.; Smale, Dan A.; Krumhansl, Kira A.; Augustine, Skye; Bettignies, Florian de; Burrows, Michael T.; Byrnes, Jarrett E. K.; Campbell, Jillian; Davoult, Dominique; Dunton, Kenneth H.; Franco, João N.; et al. (PLOS Biology, 2022)
Cycling of organic carbon in the ocean has the potential to mitigate or exacerbate global climate change, but major questions remain about the environmental controls on organic carbon flux in the coastal zone. Here, we used a field experiment distributed across 28° of latitude, and the entire range of 2 dominant kelp species in the northern hemisphere, to measure decomposition rates of kelp detritus on the seafloor in relation to local environmental factors. Detritus decomposition in both species were strongly related to ocean temperature and initial carbon content, with higher rates of biomass loss at lower latitudes with warmer temperatures. Our experiment showed slow overall decomposition and turnover of kelp detritus and modeling of coastal residence times at our study sites revealed that a significant portion of this production can remain intact long enough to reach deep marine sinks. The results suggest that decomposition of these kelp species could accelerate with ocean warming and that low-latitude kelp forests could experience the greatest increase in remineralization with a 9% to 42% reduced potential for transport to long-term ocean sinks under short-term (RCP4.5) and long-term (RCP8.5) warming scenarios. However, slow decomposition at high latitudes, where kelp abundance is predicted to expand, indicates potential for increasing kelp-carbon sinks in cooler (northern) regions. Our findings reveal an important latitudinal gradient in coastal ecosystem function that provides an improved capacity to predict the implications of ocean warming on carbon cycling. Broad-scale patterns in organic carbon decomposition revealed here can be used to identify hotspots of carbon sequestration potential and resolve relationships between carbon cycling processes and ocean climate at a global scale.
10 citations (Crossref) [2023-10-31]
Keywords: Carbon sequestration; Decomposition; Deep sea; Forests; Latitude; Ocean temperature; Oceans; Seaweed; dept.bio; peer-reviewed

Plant growth promotion by rhizosphere dwelling microbes - Lewis Roberts, Elizabeth (Rhizosphere Engineering, 2022)
This work summarizes the roles of various plant promoting (PGP) microorganism on several types of plant hosts. In particular, rhizosphere dwelling bacteria and fungi that increase plant growth, protect plants from pathogens, and increase tolerance to abiotic stresses are presented. These traits are due, in part, to the production of enzymes, hormones, and a plethora a various metabolites produced by rhizosphere microorganisms that directly or indirectly benefit the plants. The impact of selective grazing by bacterivorous protozoa on plant growth promotion is also examined. In addition to reviewing research from other investigators, this paper introduces a recently isolated Pseudomonad bacterium that has demonstrated growth promotion and protection of heirloom tomato (Solanum lycopersicum) in the face of both abiotic and biotic stresses. Our findings indicate that the novel Pseudomonas koreensis strain could serve as an agricultural inoculant to induce plant growth and protection. The potential to create effective bioinoculum using rhizosphere microorganisms is discussed.
Keywords: Plant growth promoting Rhizobacteria; Plant growth promoting fungi; Protozoa; dept.bio

Salted roads lead to oedema and reduced locomotor function in amphibian populations - Brady, S.P.; Goedert, D.; Frymus, L.E.; Zamora-Camacho, F.J.; Smith, P.C.; Zeiss, C.J.; Comas, M.; Abbott, T.A.; Basu, S.P.; DeAndressi, J.C.; Forgione, M.E.; Maloney, M.J.; et al. (Freshwater Biology, 2022)
Human activities have caused massive losses of natural populations across the globe. Like many groups, amphibians have experienced substantial declines worldwide, driven by environmental changes such as habitat conversion, pollution, and disease emergence. Each of these drivers is often found in close association with the presence of roads. Here we report a novel consequence of roads affecting an amphibian native to much of North America, the wood frog (Rana sylvatica). Across 38 populations distributed from southern to central New England, we found that adult wood frogs living adjacent to roads had higher incidence and severity of oedema (indicated by obvious bloating caused by subcutaneous fluid accumulation) during the breeding season than frogs living away from the influence of roads. This effect was best explained by increased conductivity of breeding ponds, probably caused by runoff pollution from road salt used for de-icing. Oedema severity was negatively correlated with locomotor performance in more northerly populations. Interestingly, northern populations experience more intense winters, which tends to result in more de-icing salt runoff and increased energetic demands associated with overwintering cryoprotection needs. Thus, this emerging consequence of roads appears to impose potential fitness costs associated with locomotion, and these effects might be most impactful on populations living in regions where de-icing is most intense. Together, our findings reveal a novel set of impacts of roads and runoff pollution on wood frog physiology and performance, which seem likely to contribute to population decline. Given the global prevalence of roads and increasing salinisation of freshwater habitats, oedema and related impacts could be widespread consequences faced by amphibian populations across much of the planet's temperate zones. © 2022 John Wiley & Sons Ltd.
1 citations (Crossref) [2023-10-31]
Keywords: amphibian; bloating; dept.bio; freshwater salinisation; peer-reviewed; performance; physiology; pollution; road salt runoff; winter de-icing

A comparison of the relative abundance and size of Juvenile winter flounder, Pseudopleuronectes americanus, in natural intertidal and anthropogenically altered marina habitats - Carlson, J.K.; Mroczka, M.E.; Randall, T.A.; Pellegrino, P.E. (Journal of Northwest Atlantic Fishery Science, 2000)
The relative abundance and size distributions of juvenile winter flounder, Pseudopleuronectes americanus, were compared in two areas; an anthropogenically altered marina basin and a natural intertidal flat habitat. Winter flounder were sampled from March through November 1990-95 with a 1.0 m beam trawl. No significant difference was observed in catch-per-unit-effort between areas but significant differences were found between seasons. Relative abundance (number of flounder/m2) increased from spring (0.007 marina and 0.011 intertidal flats) to summer (0.059 marina and 0.051 intertidal flats) and then declined slightly in the autumn (0.047 marina and 0.027 intertidal flats). Relative abundance was similar between areas from 1990-95 but differed between years. Length frequency distributions of winter flounder were similar between areas for all seasons but mean sizes were statistically different in summer. These results suggest that juvenile winter flounder are equally abundant in both natural intertidal habitats and marina basins, indicating that both could serve as nursery areas. However, more specific research is required to resolve the relative importance of marinas and the factors involved in utilization of each habitat.
6 citations (Crossref) [2023-10-31]
Keywords: Clinton Harbor; Connecticut; Flounder; Intertidal flats; Marina; Nursery; Pseudopleuronectes americanus; United States; dept.bio; ecological impact; intertidal environment; marina; nursery ground; relative abundance; size distribution

Life history aspects of the mayfly Siphlonurus typicus (Ephemeroptera: Siphlonuridae) with a new application for measuring nymphal development and growth - Kosnicki, E.; Burian, S. (Hydrobiologia, 2003)
Little is known about the life history of mayflies that inhabit temporary ponds. The purpose of this study was to observe and quantify life histories attributes of Siphlonurus typicus, which is known to reside in temporary ponds. Weekly samples of nymphs were taken from two temporary ponds in eastern Connecticut from March to June, 1999. Individuals were graded into 11 maturity classes, based on developmental characteristics, as a means of predicting population maturity rates. Head capsule widths (HCWs) were used to determine if growth occurred between maturity classes. Degree days were found to be an excellent predictor for population maturity (r2 = 0.963, p < 0.0001). Nymphs that hatched earlier in the year had larger HCWs than nymphs that hatched later in the year, possibly because of different temperature regimes. The University of Connecticut Forest pond (UCF) population matured faster than the Merrow Meadows pond (MER) population, but both sexes of the UCF population tended to be smaller than their counter parts from the MER population. Sex ratios were female bias for the UCF population (1.35:1), but were not different for the MER population. Adult emergence and mating occurred from 27 May to 21 June. There was a positive relationship between number of eggs per female and female body length. Oviposition at both sites occurred directly on the ponds, pond inlets, and outlets, indicating that pond populations were the result of local migrants as well as permanent residents. Temperature was a determining factor of maturity and fecundity for Siphlonurus typicus.
10 citations (Crossref) [2023-10-31]
Keywords: Age classes; Arthropoda; Biodiversity; Ephemeroptera; Growth rates; Invertebrata; Marine biology; Mating behavior; Maturity; Maturity rates; Mayflies; Ponds; Population statistics; Siphlonuridae; Siphlonurus; Siphlonurus typicus; Swarming; dept.bio; ephemeral pool; growth; larval development; life history; mayfly; swarming

Selecting appropriate controls in studies of owl nest-site selection (reply to Marks) - Bosakowski, T.; Smith, D.G. (Journal of Field Ornithology, 2001)
Marks (2001) is critical of our study of nest-site selection in Great Horned Owls (Bubo virginianus) because we compared our data from owl nests with data from random points rather than from unused stick nests. We argue that Great Horned Owls have so many options for nesting in eastern forests that there is little constraint on nest-site selection. Therefore, their choice of nest sites is determined largely by vegetation characteristics in the surrounding landscape, and comparison of owl nests with random points is the best way to assess nest-site selection. Furthermore, we believe that use of unused nests as controls, as advocated by Marks, is biased because control nests will have many of the same characteristics as nests used by owls.
1 citations (Crossref) [2023-10-31]
Keywords: Bubo virginianus; Strigiformes; dept.bio

Habitat, food habits, and productivity of Northern Goshawks nesting in Connecticut - Becker, T.E.; Smith, D.G.; Bosakowski, T. (2006)
We documented active nests of the Northern Goshawk (Accipiter gentilis) at 16 different areas in Connecticut from 1997-1999. A total of 176 prey individuals were identified from remains found under goshawk nests and prey-plucking posts. Birds represented the dominant component of diets (70.5%) with a lower contribution from mammals (29.5%). Overall, Connecticut goshawk diets were dominated by sciurids and Ruffed Grouse (Bonasa umbellus). Productivity calculated from 15 known nesting attempts totaled 32 young for an average of 2.13 young per nesting attempt (range 1-4 young). Goshawks nested in large tracts of mature forests with high levels of canopy cover (82%). The nest site topography was consistent with previous studies finding that goshawks avoid southern slopes. Tree densities in the larger size classes and basal area were characteristic for mature forest. Goshawks constructed their nests in large diameter trees, which averaged 41.7 cm in diameter at breast height. Patch size of contiguous forests surrounding goshawk nests revealed a very high mean of 324.5 ha, thus suggesting that large forest patch size may be important for nesting by this forest interior species. Analysis of 202 ha circles centered on each nest revealed that total forest cover averaged 156.1 ha, which was comprised of 65.2 ha for conifer forest, 75.6 ha for deciduous forest, and 17.4 ha for mixed forest. Overall, the post-fledgling family areas for these nests were dominated by forest cover (>75%). Our results suggest that goshawks usually prefer isolation and little human disturbance at the nest site, but some exceptions were noted. Given the highly fragmented and urbanized landscape of Connecticut, we suggest that goshawk management should focus on providing large tracts of mature forest at least 300 ha in extent.
Issue: 31 Journal Abbreviation: Stud. Avian Biol. Pages: 125 Publication Title: Stud. Avian Biol.
Keywords: Accipiter; Accipiter gentilis; Aves; Bonasa umbellus; Coniferophyta; Connecticut; Forest; Fragmentation; Habitat; Mammalia; Nest sites; Northern Goshawk; Prey; Productivity; Sciuridae; Site fidelity; dept.bio

Ecology of the Northern Goshawk in the New York-New Jersey Highlands - Bosakowski, T.; Smith, D.G. (2006)
Evidence suggests that the Northern Goshawk (Accipiter gentilis) was once extirpated in the New York-New Jersey Highlands, but has recolonized the Highlands in the 1960s and 1970s following a dramatic reforestation in the 20th century. The reforestation produced large tracts of contiguous mature forest, which appear to be a primary habitat requirement of this species. Most goshawk nests in the Highlands were found deep in remote forest areas where nest sites are typically distant from human habitation and paved roads. Nest trees were almost always built in co-dominant or dominant trees of the stand, but were seldom built in the largest tree of the nesting stand. Canopy cover is very high (90%) and shrub cover is often reduced or nearly devoid (28.3%) at goshawk nest sites. Ruffed Grouse (Bonasa umbellus) appears to be the most common prey, but other predominant bird species in diets of Highlands goshawks included the Blue Jay (Cyanocitta cristata), Mourning Dove (Zenaida macroura), Rock Dove (Columba livia), and blackbirds. Sciurids, including eastern chipmunks (Tamias striatus), red squirrel (Tamiasciurus hudsonicus), and gray squirrel (Sciurus carolinensis) were also important components of goshawk diets from the Northeast. Highlands goshawks had a mean prey weight of 365.8 g, with bird prey averaging 332.3 g and mammal prey averaging 442.9 g. In the Highlands, productivity calculated from 36 nesting attempts averaged 1.4 young per nest, lower than found in two Connecticut studies (1.75 and 2.13). Although the goshawk is generally considered to be a permanent resident, dozens of northeastern hawk migration observation stations reveal a small, but distinct, fall migration during non-invasion years. Breeding bird atlas data confirm that the goshawk is rare in New Jersey, moderately rare in Pennsylvania (mostly northern), and numerous in New York. Various factors impacting Highlands goshawks are discussed including interspecific competition, lack of reserves, timber harvesting, tree diseases, and human disturbance factors.
Issue: 31 Journal Abbreviation: Stud. Avian Biol. Pages: 118 Publication Title: Stud. Avian Biol.
Keywords: Accipiter gentilis; Aves; Bonasa umbellus; Columba livia; Competition; Cyanocitta cristata; Food-niche overlap; Forestry; Habitat; Mammalia; Migration; Nest sites; New Jersey; New York; Northern Goshawk; Prey; Productivity; Sciuridae; Sciurus carolinensis; Site fidelity; Tamias striatus; Tamiasciurus hudsonicus; Zenaida macroura; dept.bio

Ethnobotany and the loss of traditional knowledge in the 21st century - Ramirez, C.R. (Ethnobotany Research and Applications, 2007)
30 citations (Crossref) [2023-10-31]
Keywords: dept.bio

Ephemeroptera (Mayflies) - Burian, S.K. (Encyclopedia of Inland Waters, 2009)
Mayflies are members of a small, but diverse order of aquatic insects that dates back some 290. My. Mayflies are widely distributed on all continents and most large islands. Currently, the order contains about 3100. species distributed among 42 extant families. Adults are fully terrestrial and short lived, but the aquatic nymphs can live for more than a year and are important components of nutrient and energy pathways in a wide range of aquatic habitats. Higher classification and phylogeny of the mayflies are still in a state of flux, but evidence is accumulating providing stronger support for some groups. Alpha-level taxonomy still remains a problem and much work remains to be done in some genera and in some parts of the world. Extensive morphological studies have provided a solid base of knowledge, but similarly intense physiological, histological, and immunological studies are needed. Much work has been done on the ecology of genera and some species. Much finer scale ecological studies are needed to better understand the importance of small-scale ecological interactions among instars of the same and different species. Globally, there are many surveys in progress to document and map the occurrence and distribution of species. This work is critical to developing conservation strategies for mayflies and other vulnerable aquatic species. © 2009 Elsevier Inc. All rights reserved.
Journal Abbreviation: Encycl. of Inland Waters
Keywords: Biogeography; Biology; Conservation; Ecology; Ephemeroptera; Life history; Mayfly; Phylogeny; Taxonomy; dept.bio

Microbial diversity of boron-rich volcanic hot springs of St. Lucia, Lesser Antilles - Stout, L.M.; Blake, R.E.; Greenwood, J.P.; Martini, A.M.; Rose, E.C. (FEMS Microbiology Ecology, 2009)
The volcanic Sulphur Springs, St. Lucia, present an extreme environment due to high temperatures, low pH values, and high concentrations of sulfate and boron. St. Lucia offers some unique geochemical characteristics that may shape the microbial communities within the Sulphur Springs area. We chose six pools representing a range of geochemical characteristics for detailed microbial community analyses. Chemical concentrations varied greatly between sites. Microbial diversity was analyzed using 16S rRNA gene clone library analyses. With the exception of one pool with relatively low concentrations of dissolved ions, microbial diversity was very low, with Aquificales sequences dominating bacterial communities at most pools. The archaeal component of all pools was almost exclusively Acidianus spp. and did not vary between sites with different chemical characteristics. In the pool with the highest boron and sulfate concentrations, only archaeal sequences were detected. Compared with other sulfur springs such as those at Yellowstone, the microbial diversity at St. Lucia is very different, but it is similar to that at the nearby Lesser Antilles island of Montserrat. While high elemental concentrations seem to be related to differences in bacterial diversity here, similarities with other Lesser Antilles sites suggest that there may be a biogeographical component as well. © 2009 Federation of European Microbiological Societies. Published by Blackwell Publishing Ltd. All rights reserved.
25 citations (Crossref) [2023-10-31]
Keywords: Acidianus; Aquificales; Archaea; Archean; Atlantic Ocean; Atlantic islands; Bacteria; Bacteria (microorganisms); Biodiversity; Boron; Caribbean Islands; DNA; Archaeal; DNA; Bacterial; Extreme environments; Geochemistry; Hot Springs; Lesser Antilles; Microbial communities; Phylogeny; RNA; Ribosomal; 16S; Saint Lucia; Sequence Analysis; DNA; Sulfur springs; Windward Islands [Lesser Antilles]; article; bacterium detection; boron; concentration (parameters); controlled study; dept.bio; geochemistry; high temperature; microbial community; microbial diversity; molecular analysis; molecular cloning; nonhuman; nucleic acid analysis; nucleotide sequence; pH; priority journal; ribosome RNA; sulfate; thermal spring; volcanic landform

Variation in seed dormancy quantitative Trait Loci in arabidopsis thaliana originating from one site - Silady, R.A.; Effgen, S.; Koornneef, M.; Reymond, M. (PLoS ONE, 2011)
A Quantitative Trait Locus (QTL) analysis was performed using two novel Recombinant Inbred Line (RIL) populations, derived from the progeny between two Arabidopsis thaliana genotypes collected at the same site in Kyoto (Japan) crossed with the reference laboratory strain Landsberg erecta (Ler). We used these two RIL populations to determine the genetic basis of seed dormancy and flowering time, which are assumed to be the main traits controlling life history variation in Arabidopsis. The analysis revealed quantitative variation for seed dormancy that is associated with allelic variation at the seed dormancy QTL DOG1 (for Delay Of Germination 1) in one population and at DOG6 in both. These DOG QTL have been previously identified using mapping populations derived from accessions collected at different sites around the world. Genetic variation within a population may enhance its ability to respond accurately to variation within and between seasons. In contrast, variation for flowering time, which also segregated within each mapping population, is mainly governed by the same QTL. © 2011 Silady et al.
13 citations (Crossref) [2023-10-31]
Keywords: Arabidopsis; Arabidopsis Proteins; Arabidopsis protein; Arabidopsis thaliana; DOG1 protein; Arabidopsis; Delay Of Germination 1 gene; Delay Of Germination 6 gene; Japan; Plants; Genetically Modified; Quantitative Trait Loci; Seed Dormancy; article; controlled study; dept.bio; flowering; gene mapping; genetic variability; genetics; genotype; nonhuman; peer-reviewed; physiology; plant chromosome; plant gene; quantitative trait locus; recombinant inbred strain; seed dormancy; transgenic plant

Rauisuchia - Nesbitt, S.J.; Brusatte, S.L.; Desojo, J.B.; Liparini, A.; De França, M.A.G.; Weinbaum, J.C.; Gower, D.J. (2013)
'Rauisuchia' comprises Triassic pseudosuchians that ranged greatly in body size, locomotor styles and feeding ecologies. Our concept of what constitutes a rauisuchian is changing as a result of discoveries over the last 15 years. New evidence has shown that rauisuchians are probably not a natural (monophyletic) group, but instead are a number of smaller clades (e.g. Rauisuchidae, Ctenosauriscidae, Shuvosauridae) that may not be each other's closest relatives within Pseudosuchia. Here, we acknowledge that there are still large gaps in the basic understanding in the alphalevel taxonomy and relationships of these groups, but good progress is being made. As a result of renewed interest in rauisuchians, an expanding number of recent studies have focused on the growth, locomotor habits, and biomechanics of these animals, and we review these studies here. We are clearly in the midst of a renaissance in our understanding of rauisuchian evolution and the continuation of detailed descriptions, the development of explicit phylogenetic hypotheses, and explicit palaeobiological studies are essential in advancing our knowledge of these extinct animals. © The Geological Society of London 2013.
Issue: 1 Journal Abbreviation: Geol. Soc. Spec. Publ. Pages: 274 Publication Title: Geol. Soc. Spec. Publ.
Keywords: Triassic; biomechanics; body size; crocodilian; dept.bio; feeding ecology; paleobiology; paleontology; phylogenetics; taxonomy

Hot bats go cold: Heterothermy in neotropical bats - Czenze, Z.J.; Dunbar, M.B. (Canadian Journal of Zoology, 2017)
Torpor is common in bats, but has historically been viewed as an energy-saving technique reserved for temperate and subarctic climates; however, torpor use is common across several tropical bat families. Central America hosts a great diversity of bats with approximately 150 species, yet data from this area are lacking compared with tropical Africa and Australia. We investigated thermoregulatory responses of bats from neotropical Belize and captured adult bats in the tropical forests of Lamanai Archeological Reserve, Belize. After a 12 h acclimation period, we recorded rectal temperature prior to and after exposing bats to an ambient temperature (Ta) of 7 °C forupto 2 h in anenvironmental chamber. All 11 species across four families expressed torpor to some degree upon exposure to cool temperatures. Individuals from Vespertilionidae defended the lowest resting body temperature (Tb) and showed the greatest decrease in Tb after acute exposure to low Ta. Our data help to establish a new spectrum of physiological ability for this group of mammals and shed light on the evolution of torpor and heterothermy. Weshow that energy conservation is important even in warm and energetically stable environmental conditions. Understanding how and why torpor is used in warm climates will help to better define paradigms in physiological ecology. © 2017, Canadian Science Publishing. All rights reserved.
6 citations (Crossref) [2023-10-31]
Keywords: Africa; Australia; Bats; Belize; Belize [Central America]; Central America; Heterothermy; Lamanai; Mammalia; Neotropical Region; Orange Walk; Torpor; Tropics; Vespertilionidae; acclimation; bat; body temperature; dept.bio; ecophysiology; energy conservation; environmental conditions; physiological response; thermoregulation; torpor; tropical forest; tropical region

First records for spawning of caribbean acropora species in Colombian MPAs - Hudson, D.M.; Christie, B.L.; Gómez-Lemos, L.A.; Valcarcel, C.; Duque, D.; Arévalo, J.C.Z.; Rojas, J.; Reyes, O.; Marrugo, M.; Rosa, M.; Caicedo Torrado, I.A.; Tarazona, D.; et al. (Gulf and Caribbean Research, 2020)
0 citations (Crossref) [2023-10-31]
Keywords: Acropora cervicornis; Acropora palmata; Coral restoration; Endangered coral; Sexual reproduction; dept.bio; peer-reviewed

First record of introduction of metacarcinus magister dana, 1852 (Crustacea: Decapoda: Cancridae) and range extension of Eriocheir sinensis Milne-Edwards, 1853 (Crustacea: Decapoda: Varunidae) in the long Island sound - Hudson, D.M.; Schaefer-Padgett, S.; Christie, B.L.; Harris, R. (BioInvasions Records, 2019)
Invasive crustacean species have been present in the Long Island Sound, northwestern Atlantic Ocean, for over two centuries. Three new records of introduction are recorded here from collections by local fishermen. Two records are for male Dungeness crabs, Metacarcinus magister (Dana, 1852), collected in the Western Long Island Sound (2017) and Cape Cod Bay (2018). The other record is that of a range extension documented by a single male Chinese mitten crab, Eriocheir sinensis (Milne-Edwards, 1853), found in New Haven Harbor, Connecticut. Both species could potentially harbor nonnative epibionts and endoparasites. Additionally, E. sinensis may be more likely to establish, as it has in numerous locations in the region and worldwide. © Hudson et al.
0 citations (Crossref) [2023-10-31]
Keywords: Brachyura; Chinese mitten crab; Connecticut; Dungeness crab; Introduced species; Invasive species; Massachusetts; dept.bio; peer-reviewed

Instructional models for course-based research experience (CRE) teaching - Hanauer, D.I.; Graham, M.J.; Arnold, R.J.; Ayuk, M.A.; Balish, M.F.; Beyer, A.R.; Butela, K.A.; Byrum, C.A.; Chia, C.P.; Chung, H.-M.; Clase, K.L.; Conant, S.; et al. (CBE life sciences education, 2022)
The course-based research experience (CRE) with its documented educational benefits is increasingly being implemented in science, technology, engineering, and mathematics education. This article reports on a study that was done over a period of 3 years to explicate the instructional processes involved in teaching an undergraduate CRE. One hundred and two instructors from the established and large multi-institutional SEA-PHAGES program were surveyed for their understanding of the aims and practices of CRE teaching. This was followed by large-scale feedback sessions with the cohort of instructors at the annual SEA Faculty Meeting and subsequently with a small focus group of expert CRE instructors. Using a qualitative content analysis approach, the survey data were analyzed for the aims of inquiry instruction and pedagogical practices used to achieve these goals. The results characterize CRE inquiry teaching as involving three instructional models: 1) being a scientist and generating data; 2) teaching procedural knowledge; and 3) fostering project ownership. Each of these models is explicated and visualized in terms of the specific pedagogical practices and their relationships. The models present a complex picture of the ways in which CRE instruction is conducted on a daily basis and can inform instructors and institutions new to CRE teaching.
6 citations (Crossref) [2023-10-31] tex.document_type: Article tex.pubmed_id: 34978921 tex.source: Scopus
Keywords: Educational; Engineering; Faculty; Humans; Mathematics; Models; Students; Teaching; dept.bio; educational model; engineering; human; mathematics; peer-reviewed; student; teaching; university

Seasonal variation in the bioaccumulation of potentially toxic metals in the tissues of Astrangia poculata in the northeastern United States - Trumbauer, W.; Grace, S.P.; Rodrigues, L.J. (Marine Pollution Bulletin, 2022)
Astrangia poculata inhabits coasts near dense human populations in the northeastern United States and may be exposed to elevated pollutants. No studies have assessed heavy metal concentration in temperate corals despite their proximity to anthropogenic activity. We collected colonies four times in one year and analyzed coral tissue for As, Cd, Cr, Pb, and Zn. Most heavy metals except for As were 1.5–3.3 times lower in summer compared to other seasons. Pb, As, and Cd were three orders of magnitude higher than concentrations for other Narragansett Bay benthic species, suggesting that A. poculata bioaccumulates more readily and/or inhabits more contaminated areas of the Bay. Zn, Pb, and As had similar concentrations to tropical corals inhabiting anthropogenically polluted sites. While physiological impacts are unknown, this population of A. poculata may have a higher tolerance for heavy metal pollution than most scleractinians, making it an interesting candidate for future studies. © 2021 Elsevier Ltd
1 citations (Crossref) [2023-10-31] tex.art_number: 113180 tex.author_keywords: Astrangia poculata; Heavy metal pollution; Narragansett Bay; Seasonality; Temperate tex.coden: MPNBA tex.document_type: Article tex.pubmed_id: 34871902 tex.source: Scopus
Keywords: Animals; Anthozoa; Anthropogenic Effects; Article; Astrangia poculata; Astrangium poculatum; Bioaccumulation; Biochemistry; Chemical; Environmental Monitoring; Exposed to; Heavy; Heavy metal concentration; Heavy metals; Heavy metals pollution; Human population; Humans; Metals; Narragansett Bay; Narragansett bay; Pollution; Rhode Island; Seasonal variation; Seasonality; Seasons; Temperate; Tissue; Toxic metals; United States; Water Pollutants; animal; anthropogenic source; arsenic; benthos; bioaccumulation; cadmium; chromium; concentration (composition); concentration (parameter); coral; dept.bio; environmental monitoring; heavy metal; human; lead; metal derivative; nonhuman; peer-reviewed; pollution; season; seasonal variation; seasonality; toxic substance; water pollutant; zinc

Road salt compromises functional morphology of larval gills in populations of an amphibian. - Szeligowski, Richard V.; Scanley, Jules A.; Broadbridge, Christine C.; Brady, Steven P. (Environmental pollution (Barking, Essex : 1987), 2021)
Across the planet, winter de-icing practices have caused secondary salinization of freshwater habitats. Many amphibians are vulnerable because of permeable skin and reliance on small ponds, where salinity can be high. Early developmental stages of amphibians are especially sensitive to salt, and larvae developing in salt-polluted environments must osmoregulate through ion exchange in gills. Though ionoregulation in amphibian gills is generally understood, the role of gill morphology remains poorly described. Yet gill structure should affect ionoregulatory capacity, for instance in terms of available surface area. As larval amphibian gills also play critical roles in gas exchange and foraging, changes in gill morphology from salt pollution potentially affect not only osmoregulation, but also respiration and feeding. Here, we used an exposure experiment to quantify salinity effects on larval gill morphology in wood frogs (Rana sylvatica). We measured a suite of morphological traits on gill tufts—where ionoregulation and gas exchange occur—and on gill filters used in feeding. Larvae raised in elevated salinity developed larger gill tufts but with lower surface area to volume ratio. Epithelial cells on these tufts were less circular but occurred at higher densities. Gill filters showed increased spacing, likely reducing feeding efficiency. Many morphological gill traits responded quadratically, suggesting that salinity might induce plasticity in gills at intermediate concentrations until energetic demands exceed plasticity. Together, these changes likely diminish ionoregulatory and respiratory functionality of gill tufts, and compromise feeding functionality of gill filters. Thus, a singular change in aquatic environment from a widespread pollutant appears to generate a suite of consequences via changes in gill morphology. Critically, these changes in traits likely compound the severity of fitness impacts in populations dwelling in salinized environments, whereby ionoregulatory energetic demands should increase respiratory and foraging demands, but in individuals who possess structures poorly adapted for these functions. © 2021 Elsevier Ltd
2 citations (Crossref) [2023-10-31]
Keywords: Amphibia; Animals; Article; Feeding; Freshwater habitats; Functional morphology; Gas exchange; Gill morphology; Gills; Humans; Ion exchange; Larva; Morphology; Osmoregulation; Osmosis; Osmotic stress; Plasticity; Pollution; Rana sylvatica; Ranidae; Road effect; Road salts; Roads and streets; Salinisation; Secondary salinization; Sodium Chloride; Surface area; amphibian; animal; animal cell; animal experiment; animal tissue; aquatic environment; breathing; cell density; cell structure; controlled study; dept.bio; developmental stage; embryo; energetic demand; energy; epithelium cell; exposure; foraging; functional morphology; gill; gill filter; gill length; gill tuft; human; larva; length; nonhuman; osmoregulation; peer-reviewed; plasticity; pollution exposure; road; salinity; salinization; salt; sodium chloride; surface area; volume

Physiological seasonality in the symbiont and host of the northern star coral, Astrangia poculata - Trumbauer, Wolfgang; Grace, Sean P.; Rodrigues, Lisa J. (Coral reefs (Online), 2021)
Assessing physiological responses that correspond to the normal range of seasonal variation can provide a better understanding of how environmental stressors may impact physiology. Most tropical corals exhibit seasonal variation in their host and symbiont physiology within a narrow range of environmental conditions. In temperate regions and at the northern end of its distribution, Astrangia poculata must adapt to wide ranges in seasonal variability. The species is facultatively symbiotic, and it is unclear if or how symbiotic state and, consequently, host physiology is affected by environmental seasonality. We collected colonies of A. poculata with a visible range of symbiotic states from Fort Wetherill State Park in Jamestown, RI in fall, winter, spring, and summer seasons of 2018–2019. We measured physiological parameters, including symbiotic state [chlorophyll (Chl) a and c2], total lipid content, and stable carbon (δ13C) and nitrogen (δ15N) isotopes of the host and symbiont. Seasonal variation occurred in all physiological parameters we studied. Specifically, Chl a, c2, and lipid content all reached low points in the spring, suggesting a lag, where the consequences of the coldest temperatures in the winter took up to three months to manifest in the tissue. There were seasonal fluctuations in host:symbiont ratios of δ13C, reflecting changing rates of autotrophy relative to heterotrophy during the year. While some autotrophy occurred during the year, isotopic evidence indicated that carbon acquisition in A. poculata was mostly heterotrophic in the winter. Based on δ15N, the symbiont was primarily responsible for nitrogen assimilation, although other sources likely contributed. Both carbon acquisition and nitrogen acquisition were more similar to that of other aposymbiotic coral species, regardless of the symbiotic state of A. poculata. Therefore, it may be more appropriate to view A. poculata as a unique aposymbiotic coral that is capable of symbiosis, rather than the reverse. © 2021, The Author(s), under exclusive licence to Springer-Verlag GmbH Germany, part of Springer Nature.
5 citations (Crossref) [2023-10-31]
Keywords: Anthozoa; Astrangia poculata; California; Jamestown; United States; autotrophy; chlorophyll a; dept.bio; heterotrophy; lipid; nitrogen; peer-reviewed; physiology; seasonal variation; seasonality; symbiont

Taste receptors in aquatic mammals: Potential role of solitary chemosensory cells in immune responses. - Barboza, Meghan Lee Bills; Reyno, Beau (Anatomical record (Hoboken, N.J. : 2007), 2021)
The sense of taste is associated with the evaluation of food and other environmental parameters such as salinity. In aquatic mammals, anatomic and behavioral evidence of the use of taste varies by species and genomic analysis of taste receptors indicates an overall reduction and, in some cases, complete loss of intact bitter and sweet taste receptors. However, the receptors used by taste buds in the oral cavity are found on cells in other areas of the body and play an important role in immune responses. In the respiratory tract, an example of such cells is solitary chemosensory cells (SCCs) which have bitter and sweet taste receptors. The bitter receptors detect chemicals given off by pathogens and initiate an innate immune response. Although many aquatic mammals may not have a role for taste in the assessment of food, they likely would benefit from the added protection that SCCs provide, especially considering respiratory diseases are a problem for many aquatic mammals. While evidence indicates that some species do not possess functional bitter receptors for taste, many do have intact bitter receptor genes and it is important for researchers to be aware of all roles for these receptors in homeostasis. Through a better understanding of the anatomy and physiology of aquatic mammal's respiratory systems, better treatment and management is possible. © 2021 American Association for Anatomy.
1 citations (Crossref) [2023-10-31]
Keywords: Article; bitter taste; cell protection; chemoreceptor cell; dept.bio; homeostasis; innate immunity; mammal; nonhuman; peer-reviewed; receptor gene; respiratory system; respiratory tract disease; solitary chemosensory cell; sweetness; taste; taste bud

Estrogen dependent growth inhibitory effects of tamoxifen but not genistein in solid tumors derived from estrogen receptor positive (ER+) primary breast carcinoma MCF7: single agent and novel combined treatment approaches. - Nobert, Gayle S; Kraak, Martha M; Crawford, Sarah (Bulletin du cancer, 2006)
While many studies have documented tamoxifen's benefits as an adjuvant therapy in the treatment and prevention of recurrent breast cancer in estrogen receptor positive (ER+) breast carcinoma, this beneficial effect may decrease with long-term tamoxifen use. This experimental study was designed to compare the cytotoxic responses of ER+ primary breast cancer solid tumors derived from the MCF7 cell line to experimental therapeutics, including genistein, tamoxifen, all-trans retinoic acid (ATRA) and parthenolide in the presence and absence of exogenous beta-estradiol. The results of this study suggest that the growth inhibitory effects of tamoxifen, were dependent on beta-estradiol levels. In contrast, the cytotoxic effects of the isoflavone soy derivative, genistein, were observed to be independent of exogenous estrogen. Moreover, combined therapy using tamoxifen and genistein produced enhanced cytotoxic effects also independent of beta-estradiol levels. Additional studies involving the use of the novel agents all trans retinoic acid (ATRA) and parthenolide produced notable tumor responses and combined effects that were also estrogen-independent. Overall, these preclinical research findings suggest possible clinical applications suggesting that genistein might be a useful clinical adjuvant, particularly in post-menopausal women in whom breast cancer occurs more frequently. Moreover, this research suggests that combined treatment approaches involving the use of tamoxifen in conjunction with agents that inhibit NFkappaB pathway signaling, such as parthenolide and genistein, warrant further study.
Place: France Nobert, Gayle S. Department of Biology, Cancer Biology Laboratory, Southern Connecticut State University, New Haven, CT 06515, USA.
Keywords: *Antineoplastic Combined Chemotherapy Protocols/tu [Therapeutic Use]; *Breast Neoplasms/dt [Drug Therapy]; *Genistein/tu [Therapeutic Use]; *Neoplasms; Hormone-Dependent/dt [Drug Therapy]; *Tamoxifen/tu [Therapeutic Use]; Anticarcinogenic Agents; Anticarcinogenic Agents/tu [Therapeutic Use]; Antineoplastic Agents; Hormonal; Antineoplastic Agents; Hormonal/tu [Therapeutic Use]; Antineoplastic Combined Chemotherapy Protocols; Breast Neoplasms; Breast Neoplasms/ch [Chemistry]; Cell Line; Tumor; Dose-Response Relationship; Drug; Drug Resistance; Neoplasm; Drug Resistance; Neoplasm/de [Drug Effects]; Estradiol; Estradiol/pd [Pharmacology]; Female; Genistein; Humans; Neoplasms; Hormone-Dependent; Neoplasms; Hormone-Dependent/ch [Chemistry]; Receptors; Estrogen; Sesquiterpenes; Sesquiterpenes/tu [Therapeutic Use]; Spheroids; Cellular; Spheroids; Cellular/de [Drug Effects]; Tamoxifen; Tretinoin; Tretinoin/tu [Therapeutic Use]; antineoplastic agent; antineoplastic hormone agonists and antagonists; article; breast tumor; chemistry; dept.bio; dose response; drug effect; drug resistance; estradiol; estrogen receptor; female; genistein; human; multicellular spheroid; neoplasm; parthenolide; retinoic acid; sesquiterpene; tamoxifen; tumor cell line; ⛔ No DOI found

Homogenization and miniaturization of habitat structure in temperate marine forests. - Pessarrodona, Albert; Filbee-Dexter, Karen; Alcoverro, Teresa; Boada, Jordi; Feehan, Colette; Fredriksen, Stein; Grace, Sean; Nakamura, Yohei; Narvaez, Carla; Norderhaug, Kjell; Wernberg, Thomas (Global Change Biology, 2021)
Humans are rapidly transforming the structural configuration of the planet's ecosystems, but these changes and their ecological consequences remain poorly quantified in underwater habitats. Here, we show that the loss of forest-forming seaweeds and the rise of ground-covering 'turfs' across four continents consistently resulted in the miniaturization of underwater habitat structure, with seascapes converging towards flattened habitats with smaller habitable spaces. Globally, turf seascapes occupied a smaller architectural trait space and were structurally more similar across regions than marine forests, evidencing habitat homogenization. Surprisingly, such habitat convergence occurred despite turf seascapes consisting of vastly different species richness and with different taxa providing habitat architecture, as well as across disparate drivers of marine forest decline. Turf seascapes contained high sediment loads, with the miniaturization of habitat across 100s of km in mid-Western Australia resulting in reefs retaining an additional ~242 million tons of sediment (four orders of magnitude more than the sediments delivered fluvially annually). Together, this work demonstrates that the replacement of marine forests by turfs is a generalizable phenomenon that has profound consequences for the ecology of temperate reefs., (C) 2021 John Wiley & Sons, Ltd
31 citations (Crossref) [2023-10-31] Place: (C) 2021 John Wiley & Sons, Ltd
Keywords: Australia; Ecosystem; Forests; Humans; Miniaturization; Seaweed; Western Australia; algal turf; climate change; dept.bio; ecological impact; ecosystem; epilithic algal matrix; forest; foundation species; habitat change; habitat structure; human; kelp forest; kelp forests; miniaturization; peer-reviewed; regime shift; seaweed; sediment pollution; species richness; temperate forest

Is it time for a new paradigm for systemic cancer treatment? Lessons from a century of cancer chemotherapy. - Crawford, Sarah (Frontiers in pharmacology, 2013)
U.S. SEER (Surveillance Epidemiology and End Results) data for age-adjusted mortality rates for all cancers combined for all races show only a modest overall 13% decline over the past 35 years. Moreover, the greatest contributor to cancer mortality is treatment-resistant metastatic disease. The accepted therapeutic paradigm for the past half-century for the treatment of advanced cancers has involved the use of systemic chemotherapy drugs cytotoxic for cycling cells (both normal and malignant) during DNA synthesis and/or mitosis. The failure of this therapeutic modality to achieve high-level, consistent rates of disease-free survival for some of the most common cancers, including tumors of the lung, colon breast, brain, melanoma, and others is the focus of this paper. A retrospective assessment of critical milestones in cancer chemotherapy indicates that most successful therapeutic regimens use cytotoxic cell cycle inhibitors in combined, maximum tolerated, dose-dense acute treatment regimens originally developed to treat acute lymphoblastic leukemia and some lymphomas. Early clinical successes in this area led to their wholesale application to the treatment of solid tumor malignancies that, unfortunately, has not produced consistent, long-term high cure rates for many common cancers. Important differences in therapeutic sensitivity of leukemias/lymphomas versus solid tumors can be explained by key biological differences that define the treatment-resistant solid tumor phenotype. A review of these clinical outcome data in the context of recent developments in our understanding of drug resistance mechanisms characteristic of solid tumors suggests the need for a new paradigm for the treatment of chemotherapy-resistant cancers. In contrast to reductionist approaches, the systemic approach targets both microenvironmental and systemic factors that drive and sustain tumor progression. These systemic factors include dysregulated inflammatory and oxidation pathways shown to be directly implicated in the development and maintenance of the cancer phenotype. The paradigm stresses the importance of a combined preventive/therapeutic approach involving adjuvant chemotherapies that incorporate anti-inflammatory and anti-oxidant therapeutics.
80 citations (Crossref) [2023-10-31] Place: Switzerland Crawford, Sarah. Cancer Biology Research Laboratory, Southern Connecticut State University New Haven, CT, USA.
Keywords: Adjuvant; Anti-inflammatory; Anti-oxidant; Chemotherapy; Drug resistance; Neoplasm; Tumor microenvironment; Vinca alkaloid; acute lymphoblastic leukemia; adjuvant therapy; advanced cancer; aminopterin; antibiotic agent; antineoplastic activity; antineoplastic agent; antioxidant; article; bladder cancer; bleomycin; brain cancer; breast cancer; cancer cell; cancer chemotherapy; cancer growth; cancer mortality; cancer recurrence; cancer regression; cancer resistance; cancer survival; carboplatin; carmustine; chemosensitivity; childhood leukemia; chlorambucil; chlormethine; choriocarcinoma; cisplatin; colon cancer; cyclophosphamide; dept.bio; disease activity; disease free survival; doxorubicin; drug intermittent therapy; drug megadose; drug tolerability; drug treatment failure; elastin; etoposide; fludarabine; fluorouracil; gemcitabine; head and neck cancer; human; hydroxyurea; infection; inflammation; leukemia; lung cancer; lymphoma; malignant neoplastic disease; maximum tolerated dose; melanoma; mercaptopurine; metastasis; methotrexate; mitoxantrone; multiple cycle treatment; multiple myeloma; nonhodgkin lymphoma; nonhuman; ovary cancer; ovary carcinoma; paclitaxel; pancreas cancer; phenotype; platinum complex; prednisone; procarbazine; solid tumor; systemic therapy; testis cancer; topotecan; tumor microenvironment; unindexed drug; vinblastine; vinblastine sulfate; vincristine

Encoding human serine phosphopeptides in bacteria for proteome-wide identification of phosphorylation-dependent interactions. - Barber, Karl W; Muir, Paul; Szeligowski, Richard V; Rogulina, Svetlana; Gerstein, Mark; Sampson, Jeffrey R; Isaacs, Farren J; Rinehart, Jesse (Nature biotechnology, 2018)
Post-translational phosphorylation is essential to human cellular processes, but the transient, heterogeneous nature of this modification complicates its study in native systems. We developed an approach to interrogate phosphorylation and its role in protein-protein interactions on a proteome-wide scale. We genetically encoded phosphoserine in recoded E. coli and generated a peptide-based heterologous representation of the human serine phosphoproteome. We designed a single-plasmid library encoding >100,000 human phosphopeptides and confirmed the site-specific incorporation of phosphoserine in >36,000 of these peptides. We then integrated our phosphopeptide library into an approach known as Hi-P to enable proteome-level screens for serine-phosphorylation-dependent human protein interactions. Using Hi-P, we found hundreds of known and potentially new phosphoserine-dependent interactors with 14-3-3 proteins and WW domains. These phosphosites retained important binding characteristics of the native human phosphoproteome, as determined by motif analysis and pull-downs using full-length phosphoproteins. This technology can be used to interrogate user-defined phosphoproteomes in any organism, tissue, or disease of interest.
27 citations (Crossref) [2023-10-31] Place: United States Barber, Karl W. Department of Cellular & Molecular Physiology, Yale University, New Haven, Connecticut, USA. Barber, Karl W. Systems Biology Institute, Yale University, West Haven, Connecticut, USA. Muir, Paul. Systems Biology Institute, Yale University, West Haven, Connecticut, USA. Muir, Paul. Department of Molecular, Cellular and Developmental Biology, Yale University, New Haven, Connecticut, USA. Szeligowski, Richard V. Systems Biology Institute, Yale University, West Haven, Connecticut, USA. Szeligowski, Richard V. Biology Department, Southern Connecticut State University, New Haven, Connecticut, USA. Rogulina, Svetlana. Department of Cellular & Molecular Physiology, Yale University, New Haven, Connecticut, USA. Rogulina, Svetlana. Systems Biology Institute, Yale University, West Haven, Connecticut, USA. Gerstein, Mark. Systems Biology Institute, Yale University, West Haven, Connecticut, USA. Gerstein, Mark. Program in Computational Biology and Bioinformatics, Yale University, New Haven, Connecticut, USA. Gerstein, Mark. Department of Molecular Biophysics and Biochemistry, Yale University, New Haven, Connecticut, USA. Gerstein, Mark. Department of Computer Science, Yale University, New Haven, Connecticut, USA. Sampson, Jeffrey R. Agilent Laboratories, Agilent Technologies, Santa Clara, California, USA. Isaacs, Farren J. Systems Biology Institute, Yale University, West Haven, Connecticut, USA. Isaacs, Farren J. Department of Molecular, Cellular and Developmental Biology, Yale University, New Haven, Connecticut, USA. Rinehart, Jesse. Department of Cellular & Molecular Physiology, Yale University, New Haven, Connecticut, USA. Rinehart, Jesse. Systems Biology Institute, Yale University, West Haven, Connecticut, USA.
Keywords: *Peptides/ge [Genetics]; *Protein Interaction Maps/ge [Genetics]; *Proteome/ge [Genetics]; *Serine Proteases/ge [Genetics]; 14-3-3 Proteins; 14-3-3 Proteins/ch [Chemistry]; 14-3-3 Proteins/ge [Genetics]; 14-3-3 proteins; Amino Acid Motifs; Amino Acid Motifs/ge [Genetics]; Amino acids; Article; Binding characteristics; Cellular process; DNA library; Encoding (symbols); Enzyme activity; Escherichia coli; Escherichia coli/ge [Genetics]; Gene Library; Human proteins; Humans; Motif analysis; Peptides; Peptides/ch [Chemistry]; Phosphopeptides; Phosphoproteomes; Phosphorylation; Phosphoserine; Phosphoserine/ch [Chemistry]; Plasmids; Plasmids/ge [Genetics]; Protein Interaction Maps; Protein-protein interactions; Proteome; Serine Proteases; Serine Proteases/ch [Chemistry]; Signal encoding; WW Domains; WW Domains/ge [Genetics]; WW domain; amino terminal sequence; assay; carboxy terminal sequence; cell lysate; chemistry; controlled study; dept.bio; fluorescence activated cell sorting; fusion protein; gene library; genetics; high throughput sequencing; human; immunoblotting; immunoprecipitation; in vitro study; ligand binding; mass spectrometry; nonhuman; peer-reviewed; peptide; peptide library; phosphopeptide; phosphorylation; phosphoserine; plasmid; priority journal; protein 14 3 3; protein analysis; protein degradation; protein motif; protein phosphorylation; protein protein interaction; proteome; proteomics; pull down assay; serine; serine proteinase; transcription factor FKHRL1; transfer RNA

Foliar Application of Copper Oxide Nanoparticles Suppresses Fusarium Wilt Development on Chrysanthemum. - Elmer, Wade H; Zuverza-Mena, Nubia; Triplett, Lindsay R; Roberts, Elizabeth L; Silady, Rebecca A; White, Jason C (Environmental science & technology, 2021)
Micronutrients applied as nanoparticles of metal oxides have shown efficacy in vegetable and other crops for improving yield and reducing Fusarium diseases, but their role in ornamental crop management has not been investigated. In 2017, 2018, and 2020, nanoparticles of CuO, Mn2O3, or ZnO were foliarly applied at 500 mug/mL (0.6 mg/plant) to chrysanthemum transplants and planted in potting soil noninfested or infested with Fusarium oxysporum f. sp. chrysanthemi. An untreated control and a commercial fungicide, Fludioxonil, was also included. Chrysanthemums treated with nanoscale CuO had a 55, 30, and 32% reduction in disease severity ratings compared to untreated plants in 2017, 2018, and 2020, respectively. Specifically, the average dry biomass for the three years was reduced 22% by disease, but treatment with nanoscale CuO led to a 23% increase when compared to controls. Similar trends with plant height were observed. Horticultural quality was improved 28% with nano CuO and was equal to the fungicide. Nanoscale Mn2O3 and the fungicide did not consistently reduce disease ratings or increase dry biomass each year. Nanoscale ZnO was ineffective. Nanoscale CuO-treated plants had 24 to 48% more Cu/g tissue than controls (P < 0.001). These findings agree with past reports on food crops where single applications of nanoscale CuO improved plant health, growth, and yield and could offer significant impacts for managing plant diseases on ornamentals.
25 citations (Crossref) [2023-10-31] Place: United States Elmer, Wade H. Department of Plant Pathology and Ecology, The Connecticut Agricultural Experiment Station, New Haven, Connecticut 06511 United States. Zuverza-Mena, Nubia. Department of Analytical Chemistry, The Connecticut Agricultural Experiment Station, New Haven, Connecticut 06511 United States. Triplett, Lindsay R. Department of Plant Pathology and Ecology, The Connecticut Agricultural Experiment Station, New Haven, Connecticut 06511 United States. Roberts, Elizabeth L. Department of Biology, Southern Connecticut State University, New Haven, Connecticut 06515 United States. Silady, Rebecca A. Department of Biology, Southern Connecticut State University, New Haven, Connecticut 06515 United States. White, Jason C. Department of Analytical Chemistry, The Connecticut Agricultural Experiment Station, New Haven, Connecticut 06511 United States.
Keywords: *Chrysanthemum; *Fusarium; *Metal Nanoparticles; *Nanoparticles; Article; Chrysanthemum; Copper; Copper oxide nanoparticles; Copper oxides; Crops; Disease ratings; Disease severity; Foliar application; Fungi; Fungicides; Fusarium; Fusarium oxysporum f. sp. chrysanthemi; Fusarium oxysporums; Fusarium wilt; II-VI semiconductors; Manganese oxide; Metal Nanoparticles; Metal nanoparticles; Nanoparticles; Nanoscale ZnO; Ornamental crops; Oxide minerals; Oxides; Soils; Untreated control; Zinc oxide; biomass; comparative study; controlled study; copper; copper oxide nanoparticle; crop protection; dept.bio; disease severity; elemental analysis; filamentous alga; foliage; food crop; gene; growing season; horticultural species; horticulture; hydrodynamics; metal nanoparticle; nanoparticle; nonhuman; oxide; peer-reviewed; plant disease; plant growth; plant height; plant tissue; trace element; wilt

A continuum of genetic mixing for conservation management along the (mal)adaptation spectrum: A comment on Hoffmann et al. - Crispo, Erika; Derry, Alison M.; Brady, Steven P. (Evolutionary Applications, 2021)
When restoring gene flow for conservation management, genetic variation should be viewed along a continuum of genetic divergence between donor and recipient populations. On the one hand, maintaining local adaptation (low divergence between donors and recipients) can enhance conservation success in the short term. On the other hand, reducing local adaptation in the short term by increasing genetic diversity (high divergence between some donors and recipients) might have better long-term success in the face of changing environmental conditions. Both Hoffman et al. (2020) and a paper we previously published in a Special Issue on Maladaptation in Applied Conservation (Derry et al., 2019) provide frameworks and syntheses for how best to apply conservation strategies in light of genetic variation and adaptation. A key difference between these two studies was that whereas Derry et al. (2019) performed a quantitative meta-analysis, Hoffman et al. (2020) relied on case studies and theoretical considerations, yielding slightly different conclusions. We here provide a summary of the two studies and contrast of the main similarities and differences between them, while highlighting terminology used to describe and explain main concepts. © 2021 The Authors. Evolutionary Applications published by John Wiley & Sons Ltd
0 citations (Crossref) [2023-10-31] Type: Note tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85099868646
Keywords: dept.bio; peer-reviewed

Gross and microscopic anatomy of the nasal cavity, including olfactory epithelium, of the florida manatee (Trichechus manatus latirostris) - Barboza, Meghan L. B.; Larkin, Iskande L.V. (Aquatic Mammals, 2020)
As a fully aquatic mammal, the Florida manatee (Trichechus manatus latirostris) spends a limited amount of time at the water's surface. However, as a mammal that breathes air, they do need to filter, warm, and humidify that air, and anecdotal evidence indicates manatees have a sense of smell. This study characterized the nasal turbinate system, including identification of the olfactory epithelium, and compared it to other mammals using a combination of gross and micro-anatomic examination. Major turbinates were present, including nasal, maxillary, and ethmoturbinates, but with minimal convolution. The respiratory epithelium was found throughout much of the nasal cavity and covered maxillary and nasal turbinates, as well as the septum. Mucus-producing cells and cavernous veins were extensive. The olfactory epithelium was found in the dorsocaudal ethmoturbinates. As a herbivore that feeds predominantly underwater, the manatee likely relies on taste and touch for assessing food and, therefore, does not need to use smell in the same way as other marine mammals such as mysticetes (Bouchard et al., 2019) and pinnipeds (Kowalewsky et al., 2006). However, there are still substantial numbers of olfactory cells, especially considering the decreased amount of exposure time to odorants when breathing at the surface. Therefore, the question remains of why manatees have maintained their ability to smell while other fully aquatic species such as odontocetes have not. Future research should focus on a combination of behavioral and molecular techniques to fully understand the olfactory capabilities of the Florida manatee. © 2020, European Association for Aquatic Mammals.
8 citations (Crossref) [2023-10-31] Type: Article tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85086587381
Keywords: Anatomy; Chemoreception; Mammalia; Manatee; Nasal; Olfaction; Pinnipedia; Trichechidae; Trichechus manatus; Trichechus manatus latirostris; anatomy; comparative study; dept.bio; herbivore; olfaction; peer-reviewed; sirenian

Detection of multiple grapevine viruses in New England vineyards - Borges, Darlan Ferreira; Preising, Stephanie; de Queiroz Ambrósio, Márcia Michelle; da Silva, Washington Luis (Crop Protection, 2020)
Vineyards in the New England region of the USA were surveyed for the occurrence of grapevine viruses. A total of ten vineyards were visited and 62 composite samples of leaves with the petioles were collected from symptomatic grapevines (Vitis spp.). All of the samples were assayed by double-antibody sandwich enzyme-linked immunosorbent assays (DAS-ELISA) using antibodies specific for four major grapevine leafroll-associated viruses (GLRaV-1, GLRaV-2, GLRaV-3, and GLRaV-4), grapevine fanleaf virus (GFLV), tobacco ringspot virus (TRSV), and tomato ringspot virus (ToRSV). Positive ELISA samples were further tested by reverse transcription polymerase chain reaction (RT-PCR) with primers specific for each of the viruses to confirm the ELISA results. Twenty-two samples were infected with at least one of the viruses tested. GLRaV-3 (24.19%) was the most prevalent virus detected followed by GLRaV-1 (12.90%), ToRSV (3.23%), and GLRaV-2 and TRSV (1.61%). This is the first study reporting on the presence of grapevine viruses in New England. Extensive surveys need to be conducted to evaluate the prevalence and economic impact of these viruses on New England vineyards. © 2020 Elsevier Ltd
5 citations (Crossref) [2023-10-31] tex.ids: borgesDetectionMultipleGrapevine2020a tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85081269363 type: Article
Keywords: Grapevine fanleaf virus; Grapevine leafroll-associated virus 1; Grapevine leafroll-associated virus 3; Grapevine viruses; New England; Tobacco ringspot virus; Tomato ringspot virus; United States; Vineyards; Vitis; dept.bio; detection method; economic impact; pathogen; peer-reviewed; tobacco; vineyard; viral disease; virus

A fig deal: A global look at fig mosaic disease and its putative associates. - Preising, Stephanie; Borges, Darlan; de Queiroz Ambrósio, Márcia Michelle; da Silva, Washington L. (Plant disease, 2021)
16 citations (Crossref) [2023-10-31]
Keywords: Badnavirus; Connecticut; Ficus; Phylogeny; Plant Diseases; dept.bio; peer-reviewed; phylogeny; plant disease

Body mass affects short‐term heterothermy in Neotropical bats - Czenze, Zenon J.; Dunbar, Miranda B. (Biotropica, 2020)
Recent work in Australia and Africa has shown that heterothermy is widespread among phylogenetically diverse tropical and subtropical mammalian taxa. However, data on the use of heterothermy by Neotropical mammals are relatively scant, and those studies that exist focus on insect-eating bats. We investigated the capacity of fruit-eating Neotropical bats to use heterothermy when exposed to acute cold temperatures, and compared this to previous data focused on insect-eating bats sampled from the same region and time of year. We measured rectal temperatures prior to acute cold exposure (1 hr at an air temperature of 6, 7, or 10°C), and again after exposure. Our data show considerable variation in the thermoregulatory patterns of Neotropical bats, and generally, our results show that smaller bats cool quicker and to a greater extent than larger bats. Our results highlight the importance of energy conservation even in environments in which resources are relatively abundant. © 2020 The Association for Tropical Biology and Conservation
3 citations (Crossref) [2023-10-31] tex.ids: czenzeBodyMassAffects2020a tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85086457249 type: Article
Keywords: Africa; Australia; Chiroptera; Hexapoda; Mammalia; Neotropical Region; bat; body mass; dept.bio; diet; heterothermy; insect; neotropics; peer-reviewed; temperature effect; thermoregulation

Functional morphology of the taste buds of Florida manatee, Trichechus manatus latirostris - Barboza, Meghan L. B.; Larkin, Iskande L.V. (Marine Mammal Science, 2020)
The Florida manatee, Trichechus manatus latirostris, is a fully aquatic, threatened marine mammal for which increased understanding of their physiology, reproduction, and nutrition supports management decisions. Manatees may use taste to distinguish saltwater gradients, toxin detection, food assessment, and social interactions. This study sought to locate and characterize manatee taste buds comparing location, structure, number, and size to other species. Entire heads from manatees (6 males, 4 females) of various ages were obtained. The muzzle, tissue surrounding the nares, oral cavity, and epiglottis were examined grossly for pits and papillae. Tissues were examined using light and transmission electron microscopy. Within the predominant taste bud location, the tongue root, taste bud number was estimated using samples from four animals. The average number of taste buds within the tongue root was 11,534 (range 2,711–23,237) with sparse taste buds located on the soft palate and epiglottis. The location along the lateral surface of the tongue root and bordered by grooves, through which tastants could be easily transported, has functional significance. Large numbers of taste buds within the tongue root suggest that taste is an important component of manatee sensory systems and behavioral research would clarify this. © 2020 Society for Marine Mammalogy
6 citations (Crossref) [2023-10-31] tex.ids: barbozaFunctionalMorphologyTaste2020a tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85083671006 type: Article
Keywords: Animalia; Florida [United States]; Mammalia; Trichechidae; Trichechus manatus; Trichechus manatus latirostris; chemoreception; dept.bio; detection method; functional morphology; histology; manatee; marine mammal; peer-reviewed; sensory system; taste; taste bud; tongue

Biological identifications of mayflies (Ephemeroptera) using DNA barcodes - Ball, Shelley L; Hebert, Paul D N; Burian, Steven K; Webb, J M (Journal of The North American Benthological Society, 2005)
We tested the efficacy of DNA barcodes in identifying mayfly species primarily from the northeastern United States and central Canada. We sequenced a 630-base-pair segment of the mitochondrial gene, cytochrome c oxidase 1 (COI), from 1 individual of each of 80 species to create a reference sequence profile. We used these reference sequences to identify 70 additional specimens representing 32 of the species that were in the profile. DNA barcodes correctly identified 69 of the 70 test specimens. The sole exception was an individual identified morphologically as Maccaffertium modestum that showed deep genetic divergence from other M. modestum specimens. Mean sequence divergence within species was 1%, whereas mean divergence among congeneric species was an order of magnitude greater (18%). We conclude that DNA barcoding can provide a powerful tool for mayfly species identification. © 2005 by The North American Benthological Society.
195 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/039-852-420-930-526 tex.type: [object Object]
Keywords: Aquatic invertebrates; COI; Canada; DNA; Ephemeroptera; Invertebrata; Maccaffertium; Mayfly; North America; Species identification; United States; Western Hemisphere; World; aquatic organism; dept.bio; identification method; mayfly; mtDNA

Caching behavior by wintering northern saw-whet owls, aegolius acadicus - Devine, Arnold; Smith, Dwight G (Canadian Field-Naturalist, 2005)
We observed 16 instances of caching behavior by Northern Saw-whet Owls in southern Connecticut between 30 October and 29 March over a 23-year period 1982 to 2004. Caches consisted of a single prey item in 13 instances and two prey items in three instances. Prey was cached either directly beneath the owl or from 5-28 cm distant, always on the same branch on which the owl was roosting. Observations of cached prey marked in the morning suggested that it was consumed after 14:30 in the afternoon of the same day. Such a delay indicated a true cache rather than delayed feeding.
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/040-847-703-560-106 tex.type: [object Object]
Keywords: Aegolius acadicus; Caching behavior; Connecticut; North America; Northern Saw-Whet Owl; Strigiformes; United States; caching; dept.bio; marking method; prey capture; raptor; roosting

Summer diet of the peregrine falcon in faunistically rich and poor zones of Arizona analyzed with capture-recapture modeling - Ellis, David H; Ellis, Catherine H; Sabo, Beth Ann; Rea, Amadeo M; Dawson, James W; Fackler, James K; Larue, Charles T; Grubb, Teryl G; Schmitt, John; Smith, Dwight G; Kery, Marc (The Condor, 2004)
We collected prey remains from 25 Peregrine Falcon (Falco peregrinus) territories across Arizona from 1977 to 1988 yielding 58 eyrie-years of data. Along with 793 individual birds (107 species and six additional genera), we found seven mammals and nine insects. In addition, two nestling peregrines were consumed. We found a larger dependence upon White-throated Swifts (Aeronautes saxatalis) and birds on migration in northern Arizona, while in southeastern and central Arizona average prey mass was greater and columbiforms formed the largest dietary component. In northern, central, and southeastern Arizona, 74, 66, and 56 avian prey taxa, respectively, were recorded. We used capture-recapture modeling to estimate totals of 111 ± 9.5, 113 ± 10.5, and 86 ± 7.9 (SE) avian taxa taken in these same three areas. These values are counterintuitive inasmuch as the southeast has the richest avifauna. For the entire study area, 156 ± 9.3 avian taxa were estimated to be taken by peregrines.
1 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/037-218-600-548-411 tex.type: [object Object]
Keywords: Aeronautes; Aeronautes saxatalis; Aeronautes saxatatilis; Arizona; Aves; Columbiformes; Diet; Falco; Falco peregrinus; Galliformes; Hexapoda; Insecta; Mammalia; Peregrine Falcon; Peregrinus; Prey; Vertebrata; dept.bio

Taxonomy of Eurylophella coxalis (McDunnough) with notes on larval habitat and behavior (Ephemeroptera:Ephemerellidae) - Burian, Steven K (Journal of The North American Benthological Society, 2002)
Larval stages have been associated for all of the known species of Eurylophella in eastern North America except for E. coxalis. The larva of E. coxalis is described herein from a reared series of specimens. Adults are redescribed and eggs are described for the 1st time, as are notes on larval habitat and behavior. Association of E. coxalis completes our knowledge of the life stages of a presumed different species, Dentatella bartoni, which was previously known only from the larval stage. This larva is now determined to be the larval stage of E. coxalis. Further, characters used to diagnose Dentatella danutae have shown that this taxon is not different from what has been called D. bartoni. Thus, Dentatella bartoni (Allen) and D. danutae McCafferty are now placed as subjective junior synonyms of E. coxalis. A conservative criterion requiring that apomorphic characters be discernable in both larval and adult life stages is proposed for recognizing mayfly genera when knowledge of life stages and/or the phylogenetic nature of diagnostic characters is incomplete. Field and laboratory observations of live E. coxalis larvae show this species to be associated with cold, swift, alkaline streams containing coarse inorganic substrates with well-developed periphyton.
3 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/107-802-643-426-414 tex.type: [object Object]
Keywords: Apus apus; D. bartoni; D. danutae; Dentatella; Dentatella bartoni; Dentatella danutae; E. coxalis; Ecology; Ephemerellidae; Ephemeroptera; Eurylophella; Eurylophella coxalis; Taxonomy; behavior; dept.bio; habitat; larva; taxonomy

Developmental expression of a voltage-dependent potassium channel (Kv3.1) in auditory neurons without cochlear input. - Feng, Jane; Morest, D Kent (Journal of Neuroscience Research, 2001)
Kv3.1, a voltage-dependent potassium channel, has two forms, -a and -b, which differ in expression during development and at the onset of function in the auditory system. To determine whether cochlear nerve input could affect the expression of these two forms, cultures of the developing cochlear nucleus were explanted in the absence of the cochlear nerve at the beginning of cell migration (Hamburger-Hamilton stage 28-30), while neuroblasts continued to migrate onto the culture substrate. After 8, 15, and 22 days in vitro (three survival groups), cultures were immunostained with antibodies recognizing either both forms of Kv3.1 or only the -b form. Only young and newly migrated nerve cells were sampled. In the three survival groups, all nerve cells expressed Kv3.1, among which only 50% or less expressed the -b form. Some of the more differentiated multipolar cells expressed the -b form, but most were labeled with the antibody that recognizes both forms. Thus, in the absence of peripheral input, both forms of Kv3.1 appear at stages very early in development, although not all cells necessarily coexpress both forms. These results agree with other observations in the chick embryo in situ. They are consistent with previous work implicating Kv3.1 in cell migration during early development.
6 citations (Crossref) [2023-10-31] tex.type: Journal article
Keywords: *Cell Differentiation/ph [Physiology]; *Cell Movement/ph [Physiology]; *Cochlear Nerve/em [Embryology]; *Cochlear Nucleus/em [Embryology]; *Gene Expression Regulation; Developmental/ph [Physiology]; *Neurons/me [Metabolism]; *Neuropeptides/me [Metabolism]; *Potassium Channels; Voltage-Gated; *Potassium Channels/me [Metabolism]; Age Factors; Animals; Cell Compartmentation; Cell Compartmentation/ph [Physiology]; Cell Differentiation; Cell Movement; Cell Size; Cell Size/ph [Physiology]; Cells; Cultured; Cells; Cultured/cy [Cytology]; Cells; Cultured/me [Metabolism]; Chick Embryo; Chicken embryo; Cochlear Nerve; Cochlear Nerve/me [Metabolism]; Cochlear Nucleus; Cochlear Nucleus/cy [Cytology]; Cochlear Nucleus/me [Metabolism]; Cochlear nucleus; Denervation; Gene Expression Regulation; Developmental; Immunohistochemistry; Neurons; Neurons/cy [Cytology]; Neuropeptides; Nucleus magnocellularis; Potassium Channels; Potassium Channels; Voltage-Gated; Protein Isoforms; Protein Isoforms/me [Metabolism]; Sensory Deprivation; Sensory Deprivation/ph [Physiology]; Shaw Potassium Channels; Tissue culture; amino terminal sequence; animal cell; article; auditory nervous system; cell differentiation; cell migration; cell survival; chicken; cochlear nucleus; dept.bio; immunohistochemistry; magnocellular nucleus; nonhuman; potassium channel; priority journal; protein expression; tissue culture

Use of subtidal habitat by the asian shore crab hemigrapsus sanguineus in long island sound - Gilman, Michael; Grace, Sean (Northeastern Naturalist, 2009)
Hemigrapsus sanguineus Asian Shore Crab is an introduced but now common crab found intertidally along the Connecticut coastline. Little is known of its subtidal occurrence. This species was found to be seasonally abundant subtidally, at depths varying from 1.33.9 m, during a 2-year study conducted within a commercial marina in Clinton Harbor, CT. Hemigrapsus sanguineus was trapped at three subtidal locations, with highest concentrations observed during the winter. A total of 2020 crabs were caught: 1255 males, 741 females, and 24 crabs that were 9 mm or smaller and sexually indistinguishable. Large males with carapace widths between 4548 mm were captured at all three locations. These sizes are among the largest reported for this species. This work documents year-round use of subtidal habitat by Asian Shore Crab in Long Island Sound.
12 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/032-369-736-830-527 tex.type: [object Object]
Keywords: Decapoda (Crustacea); Hemigrapsus sanguineus; dept.bio; peer-reviewed

Fragmentation of colonial ascidians: Differences in reattachment capability among species - Bullard, Stephan; Sedlack, Betsy; Reinhardt, James F; Litty, Carolyn; Gareau, Keith; Whitlatch, Robert B (Journal of Experimental Marine Biology and Ecology, 2007)
31 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/054-171-469-993-130 tex.type: [object Object]
Keywords: Ascidiacea; Ascidians; Asexual; Didemnum sp.; Didemnum sp. A; Dispersal; Fragments; Invasive; Reproduction; asexual reproduction; biological invasion; dept.bio; dispersal; invasive species; settling behavior; substrate; vertebrate

Life history of the northern mayfly Baetis bundyae in Rankin Inlet, Nunavut, Canada, with updates to the list of mayflies of Nunavut - Giberson, Donna J; Burian, Steven K; Shouldice, Michael (Canadian Entomologist, 2007)
Mayflies (Ephemeroptera) were collected from 35 sites (streams and tundra ponds) across southern Nunavut in 2002-2005. Nine mayfly species were previously reported for Nunavut: Acentrella feropagus Alba-Tercedor and McCafferty, Acerpenna pygmaea (Hagen), Baetis bundyae Lehmkuhl, B. flavistriga McDunnough, B. foemina McDunnough, Diphetor hageni (Eaton) (Baetidae), Ephemerella aurivillii (Bengtsson) (Ephemerellidae), Leptophlebia nebulosa (Walker) (Leptophlebiidae), and Metretopus borealis (Eaton) (Metrotopidae). We add 7 species to this list, bringing the total to 16: Ameletus inopinatus Eaton (Ameletidae), Acentrella lapponica Bengtsson, Baetis hudsonicus Ide, B. tricaudatus Dodds, Heptagenia solitaria McDunnough (Heptageniidae), Rhithrogena jejuna Eaton (Heptageniidae), and Parameletus chelifer Bengtsson (Siphlonuridae). Based on numbers collected, the dominant mayfly family was Baetidae. Baetis bundyae was the most common mayfly collected, particularly in coastal areas, where larvae were found in permanent and temporary streams and in small or shallow tundra ponds. Larvae hatched 2-3 weeks after ice-out and developed rapidly in 2.5-4 weeks, emerging as adults by early August. All populations containing larvae that were large enough to sex showed female-biased sex ratios, suggesting parthenogenesis. A combination of freeze-tolerant eggs, good dispersal ability, and probable parthenogenesis is probably responsible for the success of Baetidae across the Arctic. © 2007 Entomological Society of Canada.
17 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/035-294-733-369-347 tex.type: [object Object]
Keywords: Acentrella feropagus; Acentrella lapponica; Acerpenna pygmaea; Ameletidae; Ameletus inopinatus; Baetidae; Baetis bundyae; Baetis hudsonicus; Canada; Diphetor hageni; Ephemerella aurivillii; Ephemerellidae; Ephemeroptera; Heptagenia solitaria; Heptageniidae; Leptophlebia nebulosa; Leptophlebiidae; Metretopus borealis; North America; Nunavut; Parameletus chelifer; Rhithrogena jejuna; Siphlonuridae; dept.bio; life history; mayfly; parthenogenesis

The size of the nucleus increases as yeast cells grow - Jorgensen, Paul; Edgington, Nicholas P; Schneider, Brandt L; Rupes, Ivan; Tyers, Mike; Futcher, Bruce (Molecular Biology of the Cell, 2007)
It is not known how the volume of the cell nucleus is set, nor how the ratio of nuclear volume to cell volume (N/C) is determined. Here, we have measured the size of the nucleus in growing cells of the budding yeast Saccharomyces cerevisiae. Analysis of mutant yeast strains spanning a range of cell sizes revealed that the ratio of average nuclear volume to average cell volume was quite consistent, with nuclear volume being ∼7% that of cell volume. At the single cell level, nuclear and cell size were strongly correlated in growing wild-type cells, as determined by three different microscopic approaches. Even in G1-phase, nuclear volume grew, although it did not grow quite as fast as overall cell volume. DNA content did not appear to have any immediate, direct influence on nuclear size, in that nuclear size did not increase sharply during S-phase. The maintenance of nuclear size did not require continuous growth or ribosome biogenesis, as starvation and rapamycin treatment had little immediate impact on nuclear size. Blocking the nuclear export of new ribosomal subunits, among other proteins and RNAs, with leptomycin B also had no obvious effect on nuclear size. Nuclear expansion must now be factored into conceptual and mathematical models of budding yeast growth and division. These results raise questions as to the unknown force(s) that expand the nucleus as yeast cells grow. © 2007 by The American Society for Cell Biology.
317 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/157-415-132-250-932 tex.type: [object Object]
Keywords: Active Transport; Cell Nucleus; Cell Nucleolus; Cell Nucleus; Cell Size; DNA content; Green Fluorescent Proteins; Karyopherins; Microscopy; Electron; Mutation; Nuclear Localization Signals; Organelle Size; RNA transport; Receptors; Cytoplasmic and Nuclear; Ribosomes; Saccharomyces cerevisiae; Saccharomycetales; article; cell cycle G1 phase; cell division; cell nucleus; cell volume; dept.bio; fungal cell; fungal strain; fungus growth; leptomycin B; mathematical model; mutant; nonhuman; priority journal; protein transport; ribosome subunit; wild type

The mayflies (ephemeroptera) of new hampshire: seasonality and diversity of the stream fauna - Chandler, Donald S; Whitmore, Greg D; Burian, Steven K; Burger, John F (Transactions of The American Entomological Society, 2006)
Season-long sampling in streams and rivers produced 112 species of mayflies, which with other records totals 121 species for New Hampshire; 88 of these are new state records. Appearance of blackwing/mature larvae were used to develop statements on seasonality of species. Distinct differences were found between the faunas of southern and north-central New Hampshire, with an important factor being water temperatures through the season. A biogeographic analysis coupled with known habitat preferences reinforced the hypothesis that water temperature was a critical factor in determining species distributions in the state.
7 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/110-786-038-143-484 tex.type: [object Object]
Keywords: Ephemeroptera; dept.bio

Development of synapses and expression of a voltage-gated potassium channel in chick embryonic auditory nuclei. - Feng, Jane J; Morest, D Kent (Hearing research, 2006)
The potassium channel protein, Kv3.1, is abundantly expressed in the chick auditory pathway. Its b-isoform is found in nucleus magnocellularis, which receives the cochlear input, both before and after the establishment of synaptic connections. It is also present in cell cultures in the absence of any peripheral input. However, the expression of this isoform in the embryo has been shown to increase with development. Here, we address the question of the correlation between maturation of synapses in the auditory pathway and the pattern of expression of the b-isoform in a series of embryos prepared for immunohistochemistry at Hamburger-Hamilton stages equivalent to E10, E12, E14, and E17. We show here that this subunit translocates from the perinuclear cytoplasm to the cell membrane domain in nucleus magnocellularis at the time that cochlear nerve endings emerge as endbulbs of Held (E17). In nucleus laminaris, by this time, while abundant Kv3.1b occurs in the perinuclear cytoplasm, a translocation to the cell membrane domain has not yet occurred, and the mature peri-synaptic localization is delayed to a later stage. This difference suggests a hierarchy in the developmental expression of Kv3.1. An unexpected finding is the expression of the a-isoform of Kv3.1 in astrocytes, especially those which surround the developing nuclei and their connecting fibers. We also report here for the first time the presence of Kv3.1b in the initial segments of axons at the times when they begin to form. Our observations suggest that the Kv3.1 channel protein is regulated through mechanisms linked to the development of synaptic activity.
13 citations (Crossref) [2023-10-31] Place: Netherlands Feng, Jane J. Department of Biology, Southern Connecticut State University, New Haven, CT 06515, USA.
Keywords: *Cochlear Nucleus/me [Metabolism]; *Olivary Nucleus/ph [Physiology]; *Shaw Potassium Channels/ph [Physiology]; *Synapses/ph [Physiology]; Animals; Astrocyte; Astrocytes; Astrocytes/me [Metabolism]; Astrocytes/ph [Physiology]; Axon initial segment; Chick Embryo; Cochlear Nerve; Cochlear Nerve/em [Embryology]; Cochlear Nerve/me [Metabolism]; Cochlear Nucleus; Cochlear Nucleus/em [Embryology]; Gene Expression Regulation; Developmental; Immunohistochemistry; Kv3.1; Neurons; Neurons/me [Metabolism]; Nucleus laminaris; Nucleus magnocellularis; Olivary Nucleus; Olivary Nucleus/em [Embryology]; Shaw Potassium Channels; Shaw Potassium Channels/me [Metabolism]; Synapses; Translocation; animal tissue; article; astrocyte; auditory nervous system; cell membrane; cellular distribution; chick embryo; chronology; cochlear nerve; controlled study; correlation analysis; cytoplasm; dept.bio; developmental stage; embryo; embryo development; immunohistochemistry; intracellular transport; isoprotein; magnocellular nucleus; maturation; nerve ending; nerve fiber; nervous system development; nonhuman; priority journal; protein content; protein determination; protein domain; protein localization; protein subunit; protein transport; regulatory mechanism; synapse; synaptogenesis; thalamus intralaminar nucleus; voltage gated potassium channel

Marine heatwaves and the collapse of marginal North Atlantic kelp forests - Filbee-Dexter, K.; Wernberg, T.; Grace, S. P.; Thormar, J.; Fredriksen, S.; Narvaez, C. N.; Feehan, C. J.; Norderhaug, K. M. (Scientific Reports, 2020)
Extreme climatic events including marine heatwaves (MHWs) are becoming more frequent and severe in the Anthropocene. However, our understanding of how these events affect population dynamics of ecologically important species is limited, in part because extreme events are rare and difficult to predict. Here, we quantified the occurrence and severity of MHWs over 60 years in warm range edge kelp forests on both sides of the North Atlantic. The cumulative annual intensity of MHWs increased two- to four-fold during this period, coinciding with the disappearance of kelps. We experimentally demonstrated a relationship between strong and severe 2018 heatwaves and high kelp mortality in both regions. Patterns of kelp mortality were strongly linked to maximum temperature anomalies, which crossed lethal thresholds in both regions. Translocation and tagging experiments revealed similar kelp mortality rates on reefs dominated by healthy kelp forests and degraded sediment-laden algal ‘turfs’, indicating equal vulnerability to extreme events. These results suggest a mechanistic link between MHWs and broad-scale kelp loss, and highlight how warming can make ecosystem boundaries unstable, forcing shifts to undesirable ecosystem states under episodically extreme climatic conditions. © 2020, The Author(s).
67 citations (Crossref) [2023-10-31] tex.ids: filbee-dexterMarineHeatwavesCollapse2020a tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85089284202 type: Article
Keywords: dept.bio

Impact of enriched environment during adolescence on adult social behavior, hippocampal synaptic density and dopamine D2 receptor expression in rats - Gabriel, Paul; Mastracchio, Toni-Ann; Bordner, Kelly; Jeffrey, Rachel (Physiology & Behavior, 2020)
Environmental enrichment (EE) is one experimental manipulation that induces changes in the brain. However, it is important to distinguish between physical and social components of enrichment. To this end we established four groups of rats reared in different enriched environments during the adolescent period. Our results indicate heightened social memory and increased spine density in dentate gyrus specifically in socially enriched animals. Physical enrichment increased spine density in CA1. Dopamine D2 receptor expression in hippocampus was decreased across all enrichment conditions. Altogether, our results demonstrate differing effects of physical and social enrichment, supporting an important role for environment in synaptogenesis, behavior, and dopaminergic signaling. © 2020 The Authors
17 citations (Crossref) [2023-10-31] tex.ids: gabrielImpactEnrichedEnvironment2020a tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85089521109 type: Article
Keywords: Adolescence; Animals; Article; Dopamine; Environment; Environmental enrichment; Hippocampus; Memory; Rats; Receptors; Dopamine D2; Social Behavior; Social enrichment; Synapse density; animal; animal behavior; animal experiment; controlled study; dentate gyrus; dept.bio; dept.psy; dopamine 2 receptor; dopaminergic transmission; environment; environmental enrichment; female; hippocampal CA1 region; hippocampus; male; memory; nonhuman; peer-reviewed; priority journal; protein expression; rat; social behavior; spine; synapse; synaptogenesis

Temperate urchins clear space for corals - Grace, Sean P; Feehan, Colette (Frontiers in Ecology and the Environment, 2020)
1 citations (Crossref) [2023-10-31] tex.ids: graceTemperateUrchinsClear2020a tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85082756571 type: Note
Keywords: Anthozoa; dept.bio; peer-reviewed

Genomic diversity of bacteriophages infecting Microbacterium spp. - Jacobs-Sera, Deborah; Abad, Lawrence A; Alvey, Richard M; Anders, Kirk R; Aull, Haley G; Bhalla, Suparna S; Blumer, Lawrence S; Bollivar, David W; Bonilla, J Alfred; Butela, Kristen A; Coomans, Roy J; Cresawn, Steven G; et al. (PloS one, 2020)
The bacteriophage population is vast, dynamic, old, and genetically diverse. The genomics of phages that infect bacterial hosts in the phylum Actinobacteria show them to not only be diverse but also pervasively mosaic, and replete with genes of unknown function. To further explore this broad group of bacteriophages, we describe here the isolation and genomic characterization of 116 phages that infect Microbacterium spp. Most of the phages are lytic, and can be grouped into twelve clusters according to their overall relatedness; seven of the phages are singletons with no close relatives. Genome sizes vary from 17.3 kbp to 97.7 kbp, and their G+C% content ranges from 51.4% to 71.4%, compared to ~67% for their Microbacterium hosts. The phages were isolated on five different Microbacterium species, but typically do not efficiently infect strains beyond the one on which they were isolated. These Microbacterium phages contain many novel features, including very large viral genes (13.5 kbp) and unusual fusions of structural proteins, including a fusion of VIP2 toxin and a MuF-like protein into a single gene. These phages and their genetic components such as integration systems, recombineering tools, and phage-mediated delivery systems, will be useful resources for advancing Microbacterium genetics.
39 citations (Crossref) [2023-10-31] Place: United States Jacobs-Sera, Deborah. Department of Biological Sciences, University of Pittsburgh, Pittsburgh, Pennsylvania, United States of America. Abad, Lawrence A. Department of Biological Sciences, University of Pittsburgh, Pittsburgh, Pennsylvania, United States of America. Alvey, Richard M. Department of Biology, Illinois Wesleyan University, Bloomington, Illinois, United States of America. Anders, Kirk R. Department of Biology, Gonzaga University, Spokane, Washington, United States of America. Aull, Haley G. Department of Biological Sciences, University of Pittsburgh, Pittsburgh, Pennsylvania, United States of America. Bhalla, Suparna S. Department of Natural Sciences, Mount Saint Mary College, Newburgh, New York, United States of America. Blumer, Lawrence S. Department of Biology, Morehouse College, Atlanta, Georgia, United States of America. Bollivar, David W. Department of Biology, Illinois Wesleyan University, Bloomington, Illinois, United States of America. Bonilla, J Alfred. Department of Biology, University of Wisconsin-River Falls, River Falls, Wisconsin, United States of America. Butela, Kristen A. Department of Biological Sciences, University of Pittsburgh, Pittsburgh, Pennsylvania, United States of America. Coomans, Roy J. Department of Biology, North Carolina A&T State University, Greensboro, North Carolina, United States of America. Cresawn, Steven G. Department of Biology, James Madison University, Harrisonburg, Virginia, United States of America. D'Elia, Tom. Department of Biological Sciences, Indian River State College, Fort Pierce, Florida, United States of America. Diaz, Arturo. Department of Biology, La Sierra University, Riverside, California, United States of America. Divens, Ashley M. Department of Biological Sciences, University of Pittsburgh, Pittsburgh, Pennsylvania, United States of America. Edgington, Nicholas P. Department of Biology, Southern Connecticut State University, New Haven, Connecticut, United States of America. Frederick, Gregory D. Department of Biology and Kinesiology, LeTourneau University, Longview, Texas, United States of America. Gainey, Maria D. Department of Chemistry & Physics, Western Carolina University, Cullowhee, North Carolina, United States of America. Garlena, Rebecca A. Department of Biological Sciences, University of Pittsburgh, Pittsburgh, Pennsylvania, United States of America. Grant, Kenneth W. Department of Pathology, Wake Forest Baptist Health, Winston-Salem, North Carolina, United States of America. Gurney, Susan M R. Department of Biology, Drexel University, Philadelphia, Pennsylvania, United States of America. Hendrickson, Heather L. School of Natural and Computational Sciences, Massey University, Auckland, New Zealand. Hughes, Lee E. Department of Biological Sciences, University of North Texas, Denton, Texas, United States of America. Kenna, Margaret A. Department of Biological Sciences, Lehigh University, Bethlehem, Pennsylvania, United States of America. Klyczek, Karen K. Department of Biology, University of Wisconsin-River Falls, River Falls, Wisconsin, United States of America. Kotturi, Hari. Department of Biology, University of Central Oklahoma, Edmond, Oklahoma, United States of America. Mavrich, Travis N. Department of Biological Sciences, University of Pittsburgh, Pittsburgh, Pennsylvania, United States of America. McKinney, Angela L. Department of Biology, Nebraska Wesleyan University, Lincoln, Nebraska, United States of America. Merkhofer, Evan C. Department of Natural Sciences, Mount Saint Mary College, Newburgh, New York, United States of America. Moberg Parker, Jordan. Department of Microbiology, Immunology, & Molecular Genetics, University of California, Los Angeles, California, United States of America. Molloy, Sally D. Department of Molecular and Biomedical Sciences, University of Maine, Orono, Maine, United States of America. Monti, Denise L. Department of Biology, University of Alabama at Birmingham, Birmingham, Alabama, United States of America. Pape-Zambito, Dana A. Department of Biological Sciences, University of the Sciences in Philadelphia, Philadelphia, Pennsylvania, United States of America. Pollenz, Richard S. Department Cell Biology, Microbiology and Molecular Biology, University of South Florida, Tampa, Florida, United States of America. Pope, Welkin H. Department of Biological Sciences, University of Pittsburgh, Pittsburgh, Pennsylvania, United States of America. Reyna, Nathan S. Department of Biology, Ouachita Baptist University, Arkadelphia, Arkansas, United States of America. Rinehart, Claire A. Department of Biology, Western Kentucky University, Bowling Green, Kentucky, United States of America. Russell, Daniel A. Department of Biological Sciences, University of Pittsburgh, Pittsburgh, Pennsylvania, United States of America. Shaffer, Christopher D. Department of Biology, University of Washington in St. Louis, St. Louis, Missouri, United States of America. Sivanathan, Viknesh. Howard Hughes Medical Institute, Chevy Chase, Maryland, United States of America. Stoner, Ty H. Department of Biological Sciences, University of Pittsburgh, Pittsburgh, Pennsylvania, United States of America. Stukey, Joseph. Biology Department, Hope College, Holland, Michigan, United States of America. Sunnen, C Nicole. Department of Biological Sciences, University of the Sciences, Philadelphia, Pennsylvania, United States of America. Tolsma, Sara S. Biology Department, Northwestern College, Orange City, Iowa, United States of America. Tsourkas, Philippos K. School of Life Sciences, University of Nevada, Las Vegas, Las Vegas, Nevada, United States of America. Wallen, Jamie R. Department of Chemistry & Physics, Western Carolina University, Cullowhee, North Carolina, United States of America. Ware, Vassie C. Department of Biological Sciences, Lehigh University, Bethlehem, Pennsylvania, United States of America. Warner, Marcie H. Department of Biological Sciences, University of Pittsburgh, Pittsburgh, Pennsylvania, United States of America. Washington, Jacqueline M. Department of Natural Sciences, Nyack College, Nyack, New York, United States of America. Westover, Kristi M. Department of Biology, Winthrop University, Rock Hill, South Carolina, United States of America. Whitefleet-Smith, JoAnn L. Department of Biology & Biotechnology, Worcester Polytechnic Institute, Worcester, Massachusetts, United States of America. Wiersma-Koch, Helen I. Department of Biological Sciences, Indian River State College, Fort Pierce, Florida, United States of America. Williams, Daniel C. Department of Biology, Coastal Carolina University, Conway, South Carolina, United States of America. Zack, Kira M. Department of Biological Sciences, University of Pittsburgh, Pittsburgh, Pennsylvania, United States of America. Hatfull, Graham F. Department of Biological Sciences, University of Pittsburgh, Pittsburgh, Pennsylvania, United States of America.
Keywords: *Actinobacteria/vi [Virology]; *Bacteriophages/ge [Genetics]; *Genetic Variation; *Genome; Viral; Actinobacteria; Article; Bacteriophages; Bacteriophages/cl [Classification]; Bacteriophages/ip [Isolation & Purification]; Base Composition; DNA base composition; DNA; Viral; DNA; Viral/ge [Genetics]; Genes; Viral; Genetic Variation; Genome; Viral; Genomics; Microbacterium; MuF like protein; Phylogeny; VIP2 toxin; Viral Fusion Proteins; Viral Fusion Proteins/ge [Genetics]; bacterial genome; bacterial strain; bacterial toxin; bacteriophage; capsid protein; classification; comparative genomics; controlled study; dept.bio; fusion protein; gene sequence; genetic variability; genetic variation; genetics; genome size; genomics; isolation and purification; nonhuman; nucleotide sequence; peer-reviewed; phylogeny; unclassified drug; virology; virus DNA; virus fusion protein; virus gene; virus genome; virus infection; virus isolation

Postnatal development of NT3 and TrkC in mouse ventral cochlear nucleus. - Feng, J; Bendiske, J; Morest, D K (Journal of Neuroscience Research, 2010)
In the developing nervous system, neurotrophin 3 (NT3) and brain-derived neurotrophic factor (BDNF) have been shown to interact with each other and with different parts of a neuron or glia and over considerable distances in time and space. The auditory system provides a useful model for analyzing these events, insofar as it is subdivided into well-defined groups of specific neuronal types that are readily related to each other at each stage of development. Previous work in our laboratory suggested that NT3 and its receptor TrkC in the mouse cochlear nucleus (CN) may be involved in directing neuronal migration and initial targeting of inputs from cochlear nerve axons in the embryo. NT3 is hard to detect soon after birth, but TrkC lingers longer. Here we found NT3 and TrkC around P8 and the peak around P30. Prominent in ventral CN, associated with globular bushy cells and stellate cells, they were localized to different subcellular sites. The TrkC immunostain was cytoplasmic, and that of NT3 was axonal and perisomatic. TrkC may be made by CN neurons, whereas NT3 has a cochlear origin. The temporal pattern of their development and the likelihood of activity-dependent release of NT3 from cochlear axons suggest that it may not be critical in early synaptogenesis; it may provide long-term trophic effects, including stabilization of synapses once established. Activity-related regulation could coordinate the supply of NT3 with inner ear activity. This may require interaction with other neurotrophins, such as BDNF.
9 citations (Crossref) [2023-10-31] Place: United States Feng, J. Southern Connecticut State University, New Haven, CT, USA.
Keywords: *Cochlear Nucleus/me [Metabolism]; *Neurons/me [Metabolism]; *Neurotrophin 3/me [Metabolism]; *Receptor; trkC/me [Metabolism]; Age Factors; Animals; Cochlear Nucleus; Fluorescent Antibody Technique; Gene Expression Regulation; Developmental; Mice; Microscopy; Fluorescence; NT3; Neurons; Neurotrophin 3; Postnatal development; Receptor; trkC; TrkC; Ventral cochlear nucleus (VCN); animal cell; animal experiment; article; brain derived neurotrophic factor; cellular distribution; cochlear nerve; cochlear nucleus; controlled study; cytoplasm; dept.bio; embryo; female; immunohistochemistry; inner ear; male; mouse; nerve cell; nerve fiber; nerve root; neurotrophin 3; neurotrophin 3 receptor; nonhuman; postnatal development; priority journal; protein interaction; regulatory mechanism; stellate cell; synapse; synaptogenesis

Degeneration in the ventral cochlear nucleus after severe noise damage in mice - Feng, J; Bendiske, J; Morest, D K (Journal of Neuroscience Research, 2012)
To study the mechanisms of noise-induced hearing loss and the phantom noise, or tinnitus, often associated with it, we used a mouse model of noise damage designed for reproducible and quantitative structural analyses. We selected the posteroventral cochlear nucleus, which has shown considerable plasticity in past studies, and correlated its changes with the distribution of neurotrophin 3 (NT3). We used volume change, optical density analysis, and microscopic cluster analysis to measure the degeneration after noise exposure. There was a fluctuation pattern in the reorganization of nerve terminals. The data suggest that the source and size of the nerve terminals affect their capacity for regeneration. We hypothesize that the deafferentation of ventral cochlear nucleus is the structural basis of noise-induced tinnitus. In addition, the immunofluorescent data show a possible connection between NT3 and astrocytes. There appears to be a compensatory process in the supporting glial cells during this degeneration. Glia may play a role in the mechanisms of noise-induced hearing loss. © 2011 Wiley Periodicals, Inc.
15 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/021-539-907-848-327 tex.type: [object Object]
Keywords: Analysis of Variance; Animals; Calcium-Binding Proteins; Cluster Analysis; Cochlea; Cochlear Nucleus; Disease Models; Animal; Excitatory Amino Acid Transporter 2; Hearing Loss; Sensorineural; Hearing loss; Membrane Glycoproteins; Mice; Mice; Inbred C57BL; Mouse model; NT3; Nerve Growth Factors; Nerve Tissue Proteins; Neurodegenerative Diseases; Noise; Time Factors; Tinnitus; animal cell; animal experiment; animal model; animal tissue; article; astrocyte; controlled study; deafferentation; dept.bio; disease severity; environmental exposure; glia cell; hearing loss; immunofluorescence; mouse; nerve cell plasticity; nerve degeneration; nerve ending; nerve regeneration; neurotrophin 3; noise; nonhuman; optical density; posteroventral cochlear nucleus; priority journal; quantitative analysis; tinnitus

Rhizosphere microbiome selection by Epichloë endophytes of Festuca arundinacea - Roberts, Elizabeth Lewis; Ferraro, Aileen (Plant and Soil, 2015)
Aims: Loline alkaloids produced by Epichloë spp. are known to deter feeding by insect herbivores while also serving as a significant carbon source for certain epiphytic bacteria on tall fescue leaves. In this study we examined the role of loline alkaloids in attracting certain bacteria to the rhizosphere of tall fescue plants that harbor loline producing fungal endophytes. Methods: Population studies were used to compare the fitness of known loline catabolizing strains to other rhizosphere bacteria. Pyrosequencing of 16S rRNA fragments compared the composition of bacterial communities inhabiting the endophyte infected tall fescue (Festuca arundinacea) rhizosphere to those of endophyte free fescue plants. Results: Rhizosphere population studies demonstrated that loline catabolizing strains Burkholderia ambifaria 7R and Pseudomonas aureofaciens outcompete and suppress the growth of non-loline catabolizing strains. Pyrosequencing of 16S rRNA fragments showed greater percentages of certain plant growth promoting bacteria in rhizosperes seeded with B. ambifaria 7R than non-inoculated soils. Rhizospheres of endophyte infected plants showed higher species richness (Shannon diversity index = 4.03) over endophyte free rhizospheres (Shannon diversity index = 3.08) and a greater percentage of Firmicutes. Conclusions: The differences in microbial community composition between endophyte-infected and endophyte-free rhizospheres suggest that the presence of fungal endophytes influences microbial community structure. Loline alkaloid production may be one proxy by which the fungal endophyte shapes microbial communities, as evidenced by increased fitness of loline catabolizing bacteria in the tall fescue rhizosphere. © 2015, Springer International Publishing Switzerland.
21 citations (Crossref) [2023-10-31] Citation Key Alias: pop00270 tex.type: [object Object]
Keywords: Bacteria (microorganisms); Burkholderia ambifaria; Endophyte; Epichloë spp; Festuca arundinacea; Firmicutes; Hexapoda; Loline alkaloids; Pseudomonas chlororaphis; Tall fescue; alkaloid; antifeedant; bacterium; community structure; dept.bio; diversity index; endophyte; fitness; fungus; grass; insect; microbial community; microorganism; rhizosphere; species richness

Designing a broad-spectrum integrative approach for cancer prevention and treatment. - Block, Keith I; Gyllenhaal, Charlotte; Lowe, Leroy; Amedei, Amedeo; Amin, A R M Ruhul; Amin, Amr; Aquilano, Katia; Arbiser, Jack; Arreola, Alexandra; Arzumanyan, Alla; Ashraf, S Salman; Azmi, Asfar S; et al. (Seminars in Cancer Biology, 2015)
Targeted therapies and the consequent adoption of "personalized" oncology have achieved notable successes in some cancers; however, significant problems remain with this approach. Many targeted therapies are highly toxic, costs are extremely high, and most patients experience relapse after a few disease-free months. Relapses arise from genetic heterogeneity in tumors, which harbor therapy-resistant immortalized cells that have adopted alternate and compensatory pathways (i.e., pathways that are not reliant upon the same mechanisms as those which have been targeted). To address these limitations, an international task force of 180 scientists was assembled to explore the concept of a low-toxicity "broad-spectrum" therapeutic approach that could simultaneously target many key pathways and mechanisms. Using cancer hallmark phenotypes and the tumor microenvironment to account for the various aspects of relevant cancer biology, interdisciplinary teams reviewed each hallmark area and nominated a wide range of high-priority targets (74 in total) that could be modified to improve patient outcomes. For these targets, corresponding low-toxicity therapeutic approaches were then suggested, many of which were phytochemicals. Proposed actions on each target and all of the approaches were further reviewed for known effects on other hallmark areas and the tumor microenvironment. Potential contrary or procarcinogenic effects were found for 3.9% of the relationships between targets and hallmarks, and mixed evidence of complementary and contrary relationships was found for 7.1%. Approximately 67% of the relationships revealed potentially complementary effects, and the remainder had no known relationship. Among the approaches, 1.1% had contrary, 2.8% had mixed and 62.1% had complementary relationships. These results suggest that a broad-spectrum approach should be feasible from a safety standpoint. This novel approach has potential to be relatively inexpensive, it should help us address stages and types of cancer that lack conventional treatment, and it may reduce relapse risks. A proposed agenda for future research is offered. Copyright © 2015 The Authors. Published by Elsevier Ltd.. All rights reserved.
196 citations (Crossref) [2023-10-31] Place: England Block, Keith I. Block Center for Integrative Cancer Treatment, Skokie, IL, United States. Electronic address: drblock@blockmedical.com. Gyllenhaal, Charlotte. Block Center for Integrative Cancer Treatment, Skokie, IL, United States. Lowe, Leroy. Getting to Know Cancer, Truro, Nova Scotia, Canada; Lancaster Environment Centre, Lancaster University, Bailrigg, Lancaster, United Kingdom. Electronic address: Leroy.lowe@gettingtoknowcancer.org. Amedei, Amedeo. Department of Experimental and Clinical Medicine, University of Florence, Florence, Italy. Amin, A R M Ruhul. Winship Cancer Institute of Emory University, Atlanta, GA, United States. Amin, Amr. Department of Biology, College of Science, United Arab Emirates University, Al Ain, United Arab Emirates. Aquilano, Katia. Department of Biology, University of Rome "Tor Vergata", Rome, Italy. Arbiser, Jack. Winship Cancer Institute of Emory University, Atlanta, GA, United States; Atlanta Veterans Administration Medical Center, Atlanta, GA, United States; Department of Dermatology, Emory University School of Medicine, Emory University, Atlanta, GA, United States. Arreola, Alexandra. Lineberger Comprehensive Cancer Center, University of North Carolina, Chapel Hill, NC, United States. Arzumanyan, Alla. Department of Biology, Temple University, Philadelphia, PA, United States. Ashraf, S Salman. Department of Chemistry, College of Science, United Arab Emirates University, Al Ain, United Arab Emirates. Azmi, Asfar S. Department of Oncology, Karmanos Cancer Institute, Wayne State University, Detroit, MI, United States. Benencia, Fabian. Department of Biomedical Sciences, Ohio University, Athens, OH, United States. Bhakta, Dipita. School of Chemical and Bio Technology, SASTRA University, Thanjavur, Tamil Nadu, India. Bilsland, Alan. University of Glasgow, Glasgow, United Kingdom. Bishayee, Anupam. Department of Pharmaceutical Sciences, College of Pharmacy, Larkin Health Sciences Institute, Miami, FL, United States. Blain, Stacy W. Department of Pediatrics, State University of New York, Downstate Medical Center, Brooklyn, NY, United States. Block, Penny B. Block Center for Integrative Cancer Treatment, Skokie, IL, United States. Boosani, Chandra S. Department of BioMedical Sciences, School of Medicine, Creighton University, Omaha, NE, United States. Carey, Thomas E. Head and Neck Cancer Biology Laboratory, University of Michigan, Ann Arbor, MI, United States. Carnero, Amancio. Instituto de Biomedicina de Sevilla, Consejo Superior de Investigaciones Cientificas, Seville, Spain. Carotenuto, Marianeve. Centro di Ingegneria Genetica e Biotecnologia Avanzate, Naples, Italy; Department of Molecular Medicine and Medical Biotechnology, Federico II, Via Pansini 5, 80131 Naples, Italy. Casey, Stephanie C. Stanford University, Division of Oncology, Department of Medicine and Pathology, Stanford, CA, United States. Chakrabarti, Mrinmay. Department of Pathology, Microbiology, and Immunology, University of South Carolina, School of Medicine, Columbia, SC, United States. Chaturvedi, Rupesh. School of Biotechnology, Jawaharlal Nehru University, New Delhi, India. Chen, Georgia Zhuo. Winship Cancer Institute of Emory University, Atlanta, GA, United States. Chen, Helen. Department of Pediatrics, University of British Columbia, Michael Cuccione Childhood Cancer Research Program, Child and Family Research Institute, Vancouver, British Columbia, Canada. Chen, Sophie. Ovarian and Prostate Cancer Research Laboratory, Guildford, Surrey, United Kingdom. Chen, Yi Charlie. Department of Biology, Alderson Broaddus University, Philippi, WV, United States. Choi, Beom K. Cancer Immunology Branch, Division of Cancer Biology, National Cancer Center, Goyang, Gyeonggi, Republic of Korea. Ciriolo, Maria Rosa. Department of Biology, University of Rome "Tor Vergata", Rome, Italy. Coley, Helen M. Faculty of Health and Medical Sciences, University of Surrey, Guildford, Surrey, United Kingdom. Collins, Andrew R. Department of Nutrition, Faculty of Medicine, University of Oslo, Oslo, Norway. Connell, Marisa. Department of Pediatrics, University of British Columbia, Michael Cuccione Childhood Cancer Research Program, Child and Family Research Institute, Vancouver, British Columbia, Canada. Crawford, Sarah. Cancer Biology Research Laboratory, Southern Connecticut State University, New Haven, CT, United States. Curran, Colleen S. School of Medicine and Public Health, University of Wisconsin-Madison, Madison, WI, United States. Dabrosin, Charlotta. Department of Oncology and Department of Clinical and Experimental Medicine, Linkoping University, Linkoping, Sweden. Damia, Giovanna. Department of Oncology, Istituto Di Ricovero e Cura a Carattere Scientifico - Istituto di Ricerche Farmacologiche Mario Negri, Milan, Italy. Dasgupta, Santanu. Department of Cellular and Molecular Biology, the University of Texas Health Science Center at Tyler, Tyler, TX, United States. DeBerardinis, Ralph J. Children's Medical Center Research Institute, University of Texas - Southwestern Medical Center, Dallas, TX, United States. Decker, William K. Department of Pathology & Immunology, Baylor College of Medicine, Houston, TX, United States. Dhawan, Punita. Department of Surgery and Cancer Biology, Division of Surgical Oncology, Vanderbilt University School of Medicine, Nashville, TN, United States. Diehl, Anna Mae E. Department of Medicine, Duke University Medical Center, Durham, NC, United States. Dong, Jin-Tang. Winship Cancer Institute of Emory University, Atlanta, GA, United States. Dou, Q Ping. Department of Oncology, Karmanos Cancer Institute, Wayne State University, Detroit, MI, United States. Drew, Janice E. Rowett Institute of Nutrition and Health, University of Aberdeen, Aberdeen, Scotland, United Kingdom. Elkord, Eyad. College of Medicine & Health Sciences, United Arab Emirates University, Al Ain, United Arab Emirates. El-Rayes, Bassel. Department of Hematology and Medical Oncology, Emory University, Atlanta, GA, United States. Feitelson, Mark A. Department of Biology, Temple University, Philadelphia, PA, United States. Felsher, Dean W. Stanford University, Division of Oncology, Department of Medicine and Pathology, Stanford, CA, United States. Ferguson, Lynnette R. Discipline of Nutrition and Auckland Cancer Society Research Centre, University of Auckland, Auckland, New Zealand. Fimognari, Carmela. Dipartimento di Scienze per la Qualita della Vita Alma Mater Studiorum-Universita di Bologna, Rimini, Italy. Firestone, Gary L. Department of Molecular & Cell Biology, University of California Berkeley, Berkeley, CA, United States. Frezza, Christian. Medical Research Council Cancer Unit, University of Cambridge, Hutchison/MRC Research Centre, Cambridge, United Kingdom. Fujii, Hiromasa. Department of Orthopedic Surgery, Nara Medical University, Kashihara, Nara, Japan. Fuster, Mark M. Medicine and Research Services, Veterans Affairs San Diego Healthcare System & University of California, San Diego, CA, United States. Generali, Daniele. Department of Medical, Surgery and Health Sciences, University of Trieste, Trieste, Italy; Molecular Therapy and Pharmacogenomics Unit, Azienda Ospedaliera Istituti Ospitalieri di Cremona, Cremona, Italy. Georgakilas, Alexandros G. Physics Department, School of Applied Mathematics and Physical Sciences, National Technical University of Athens, Athens, Greece. Gieseler, Frank. First Department of Medicine, University Hospital Schleswig-Holstein, Campus Lubeck, Lubeck, Germany. Gilbertson, Michael. Getting to Know Cancer, Guelph, Canada. Green, Michelle F. Duke Molecular Physiology Institute, Duke University Medical Center, Durham, NC, United States. Grue, Brendan. Departments of Environmental Science, Microbiology and Immunology, Dalhousie University, Halifax, Nova Scotia, Canada. Guha, Gunjan. School of Chemical and Bio Technology, SASTRA University, Thanjavur, Tamil Nadu, India. Halicka, Dorota. Department of Pathology, New York Medical College, Valhalla, NY, United States. Helferich, William G. University of Illinois at Urbana Champaign, Champaign, IL, United States. Heneberg, Petr. Charles University in Prague, Third Faculty of Medicine, Prague, Czech Republic. Hentosh, Patricia. School of Medical Laboratory and Radiation Sciences, Old Dominion University, Norfolk, VA, United States. Hirschey, Matthew D. Department of Medicine, Duke University Medical Center, Durham, NC, United States; Duke Molecular Physiology Institute, Duke University Medical Center, Durham, NC, United States. Hofseth, Lorne J. College of Pharmacy, University of South Carolina, Columbia, SC, United States. Holcombe, Randall F. Tisch Cancer Institute, Mount Sinai School of Medicine, New York, NY, United States. Honoki, Kanya. Department of Orthopedic Surgery, Nara Medical University, Kashihara, Nara, Japan. Hsu, Hsue-Yin. Department of Life Sciences, Tzu-Chi University, Hualien, Taiwan. Huang, Gloria S. Albert Einstein College of Medicine and Montefiore Medical Center, Bronx, NY, United States. Jensen, Lasse D. Department of Medical and Health Sciences, Linkoping University, Linkoping, Sweden; Department of Microbiology, Tumor and Cell Biology, Karolinska Institutet, Stockholm, Sweden. Jiang, Wen G. Cardiff University School of Medicine, Heath Park, Cardiff, United Kingdom. Jones, Lee W. Department of Medicine, Memorial Sloan-Kettering Cancer Center, New York, NY, United States. Karpowicz, Phillip A. University of Windsor, Windsor, Ontario, Canada. Keith, W Nicol. University of Glasgow, Glasgow, United Kingdom. Kerkar, Sid P. Laboratory Medicine and Pathology, Mayo Clinic, Rochester, MN, United States. Khan, Gazala N. Henry Ford Hospital, Detroit, MI, United States. Khatami, Mahin. Inflammation and Cancer Research, National Cancer Institute (Retired), National Institutes of Health, Bethesda, MD, United States. Ko, Young H. University of Maryland BioPark, Innovation Center, KoDiscovery, Baltimore, MD, United States. Kucuk, Omer. Winship Cancer Institute of Emory University, Atlanta, GA, United States. Kulathinal, Rob J. Department of Biology, Temple University, Philadelphia, PA, United States. Kumar, Nagi B. Moffitt Cancer Center, University of South Florida College of Medicine, Tampa, FL, United States. Kwon, Byoung S. Cancer Immunology Branch, Division of Cancer Biology, National Cancer Center, Goyang, Gyeonggi, Republic of Korea; Department of Medicine, Tulane University Health Sciences Center, New Orleans, LA, United States. Le, Anne. The Sol Goldman Pancreatic Cancer Research Center, Department of Pathology, Johns Hopkins University School of Medicine, Baltimore, MD, United States. Lea, Michael A. New Jersey Medical School, Rutgers University, Newark, NJ, United States. Lee, Ho-Young. College of Pharmacy, Seoul National University, South Korea. Lichtor, Terry. Department of Neurosurgery, Rush University Medical Center, Chicago, IL, United States. Lin, Liang-Tzung. Department of Microbiology and Immunology, School of Medicine, College of Medicine, Taipei Medical University, Taipei, Taiwan. Locasale, Jason W. Division of Nutritional Sciences, Cornell University, Ithaca, NY, United States. Lokeshwar, Bal L. Department of Medicine, Georgia Regents University Cancer Center, Augusta, GA, United States. Longo, Valter D. Andrus Gerontology Center, Division of Biogerontology, University of Southern California, Los Angeles, CA, United States. Lyssiotis, Costas A. Department of Molecular and Integrative Physiology and Department of Internal Medicine, Division of Gastroenterology, University of Michigan, Ann Arbor, MI, United States. MacKenzie, Karen L. Children's Cancer Institute Australia, Kensington, New South Wales, Australia. Malhotra, Meenakshi. Department of Biomedical Engineering, McGill University, Montreal, Canada. Marino, Maria. Department of Science, University Roma Tre, Rome, Italy. Martinez-Chantar, Maria L. Metabolomic Unit, Centro de Investigacion Biomedica en Red de Enfermedades Hepaticas y Digestivas, Technology Park of Bizkaia, Bizkaia, Spain. Matheu, Ander. Biodonostia Institute, Gipuzkoa, Spain. Maxwell, Christopher. Department of Pediatrics, University of British Columbia, Michael Cuccione Childhood Cancer Research Program, Child and Family Research Institute, Vancouver, British Columbia, Canada. McDonnell, Eoin. Duke Molecular Physiology Institute, Duke University Medical Center, Durham, NC, United States. Meeker, Alan K. Department of Pathology, Johns Hopkins University School of Medicine, Baltimore, MD, United States. Mehrmohamadi, Mahya. Field of Genetics, Genomics, and Development, Department of Molecular Biology and Genetics, Cornell University, Ithaca, NY, United States. Mehta, Kapil. Department of Experimental Therapeutics, University of Texas MD Anderson Cancer Center, Houston, TX, United States. Michelotti, Gregory A. Department of Medicine, Duke University Medical Center, Durham, NC, United States. Mohammad, Ramzi M. Department of Oncology, Karmanos Cancer Institute, Wayne State University, Detroit, MI, United States. Mohammed, Sulma I. Department of Comparative Pathobiology, Purdue University Center for Cancer Research, West Lafayette, IN, United States. Morre, D James. Mor-NuCo, Inc, Purdue Research Park, West Lafayette, IN, United States. Muralidhar, Vinayak. Harvard-MIT Division of Health Sciences and Technology, Harvard Medical School, Boston, MA, United States; Koch Institute for Integrative Cancer Research, Massachusetts Institute of Technology, Cambridge, MA, United States. Muqbil, Irfana. Department of Oncology, Karmanos Cancer Institute, Wayne State University, Detroit, MI, United States. Murphy, Michael P. MRC Mitochondrial Biology Unit, Wellcome Trust-MRC Building, Hills Road, Cambridge, United Kingdom. Nagaraju, Ganji Purnachandra. Department of Hematology and Medical Oncology, Emory University, Atlanta, GA, United States. Nahta, Rita. Winship Cancer Institute of Emory University, Atlanta, GA, United States. Niccolai, Elena. University of Florence, Florence, Italy. Nowsheen, Somaira. Medical Scientist Training Program, Mayo Graduate School, Mayo Medical School, Mayo Clinic, Rochester, MN, United States. Panis, Carolina. Laboratory of Inflammatory Mediators, State University of West Parana, UNIOESTE, Parana, Brazil. Pantano, Francesco. Medical Oncology Department, University Campus Bio-Medico, Rome, Italy. Parslow, Virginia R. Discipline of Nutrition and Auckland Cancer Society Research Centre, University of Auckland, Auckland, New Zealand. Pawelec, Graham. Center for Medical Research, University of Tubingen, Tubingen, Germany. Pedersen, Peter L. Departments of Biological Chemistry and Oncology, Member at Large, Sidney Kimmel Comprehensive Cancer Center, Johns Hopkins University, School of Medicine, Baltimore, MD, United States. Poore, Brad. The Sol Goldman Pancreatic Cancer Research Center, Department of Pathology, Johns Hopkins University School of Medicine, Baltimore, MD, United States. Poudyal, Deepak. College of Pharmacy, University of South Carolina, Columbia, SC, United States. Prakash, Satya. Department of Biomedical Engineering, McGill University, Montreal, Canada. Prince, Mark. Department of Otolaryngology-Head and Neck, Medical School, University of Michigan, Ann Arbor, MI, United States. Raffaghello, Lizzia. Laboratory of Oncology, Istituto Giannina Gaslini, Genoa, Italy. Rathmell, Jeffrey C. Duke Molecular Physiology Institute, Duke University Medical Center, Durham, NC, United States. Rathmell, W Kimryn. Lineberger Comprehensive Cancer Center, University of North Carolina, Chapel Hill, NC, United States. Ray, Swapan K. Department of Pathology, Microbiology, and Immunology, University of South Carolina, School of Medicine, Columbia, SC, United States. Reichrath, Jorg. Center for Clinical and Experimental Photodermatology, Clinic for Dermatology, Venerology and Allergology, The Saarland University Hospital, Homburg, Germany. Rezazadeh, Sarallah. Department of Biology, University of Rochester, Rochester, NY, United States. Ribatti, Domenico. Department of Basic Medical Sciences, Neurosciences and Sensory Organs, University of Bari Medical School, Bari, Italy & National Cancer Institute Giovanni Paolo II, Bari, Italy. Ricciardiello, Luigi. Department of Medical and Surgical Sciences, University of Bologna, Bologna, Italy. Robey, R Brooks. White River Junction Veterans Affairs Medical Center, White River Junction, VT, United States; Geisel School of Medicine at Dartmouth, Hanover, NH, United States. Rodier, Francis. Centre de Rechercher du Centre Hospitalier de l'Universite de Montreal and Institut du Cancer de Montreal, Montreal, Quebec, Canada; Universite de Montreal, Departement de Radiologie, Radio-Oncologie et Medicine Nucleaire, Montreal, Quebec, Canada. Rupasinghe, H P Vasantha. Department of Environmental Sciences, Faculty of Agriculture and Department of Pathology, Faculty of Medicine, Dalhousie University, Halifax, Nova Scotia, Canada. Russo, Gian Luigi. Institute of Food Sciences National Research Council, Avellino, Italy. Ryan, Elizabeth P. Department of Environmental and Radiological Health Sciences, Colorado State University, Fort Collins, CO, United States. Samadi, Abbas K. Sanus Biosciences, San Diego, CA, United States. Sanchez-Garcia, Isidro. Experimental Therapeutics and Translational Oncology Program, Instituto de Biologia Molecular y Celular del Cancer, CSIC-Universidad de Salamanca, Salamanca, Spain. Sanders, Andrew J. Cardiff University School of Medicine, Heath Park, Cardiff, United Kingdom. Santini, Daniele. Medical Oncology Department, University Campus Bio-Medico, Rome, Italy. Sarkar, Malancha. Department of Biology, University of Miami, Miami, FL, United States. Sasada, Tetsuro. Department of Immunology, Kurume University School of Medicine, Kurume, Fukuoka, Japan. Saxena, Neeraj K. Department of Medicine, University of Maryland School of Medicine, Baltimore, MD, United States. Shackelford, Rodney E. Department of Pathology, Louisiana State University, Health Shreveport, Shreveport, LA, United States. Shantha Kumara, H M C. Department of Surgery, St. Luke's Roosevelt Hospital, New York, NY, United States. Sharma, Dipali. Department of Oncology, Johns Hopkins University School of Medicine and the Sidney Kimmel Comprehensive Cancer Center at Johns Hopkins, Baltimore, MD, United States. Shin, Dong M. Winship Cancer Institute of Emory University, Atlanta, GA, United States. Sidransky, David. Department of Otolaryngology-Head and Neck Surgery, Johns Hopkins University School of Medicine, Baltimore, MD, United States. Siegelin, Markus David. Department of Pathology and Cell Biology, Columbia University Medical Center, New York, NY, United States. Signori, Emanuela. National Research Council, Institute of Translational Pharmacology, Rome, Italy. Singh, Neetu. Advanced Molecular Science Research Centre (Centre for Advanced Research), King George's Medical University, Lucknow, Uttar Pradesh, India. Sivanand, Sharanya. Department of Cancer Biology, Perelman School of Medicine, University of Pennsylvania, Philadelphia, PA, United States. Sliva, Daniel. DSTest Laboratories, Purdue Research Park, Indianapolis, IN, United States. Smythe, Carl. Department of Biomedical Science, Sheffield Cancer Research Centre, University of Sheffield, Sheffield, United Kingdom. Spagnuolo, Carmela. Institute of Food Sciences National Research Council, Avellino, Italy. Stafforini, Diana M. Huntsman Cancer Institute and Department of Internal Medicine, University of Utah, Salt Lake City, UT, United States. Stagg, John. Centre de Recherche du Centre Hospitalier de l'Universite de Montreal, Faculte de Pharmacie et Institut du Cancer de Montreal, Montreal, Quebec, Canada. Subbarayan, Pochi R. Department of Medicine, University of Miami Miller School of Medicine, Miami, FL, United States. Sundin, Tabetha. Department of Molecular Diagnostics, Sentara Healthcare, Norfolk, VA, United States. Talib, Wamidh H. Department of Clinical Pharmacy and Therapeutics, Applied Science University, Amman, Jordan. Thompson, Sarah K. Department of Surgery, Royal Adelaide Hospital, Adelaide, Australia. Tran, Phuoc T. Departments of Radiation Oncology & Molecular Radiation Sciences, Oncology and Urology, Johns Hopkins School of Medicine, Baltimore, MD, United States. Ungefroren, Hendrik. First Department of Medicine, University Hospital Schleswig-Holstein, Campus Lubeck, Lubeck, Germany. Vander Heiden, Matthew G. Koch Institute for Integrative Cancer Research, Massachusetts Institute of Technology, Cambridge, MA, United States. Venkateswaran, Vasundara. Department of Surgery, University of Toronto, Division of Urology, Sunnybrook Health Sciences Centre, Toronto, Ontario, Canada. Vinay, Dass S. Section of Clinical Immunology, Allergy, and Rheumatology, Department of Medicine, Tulane University Health Sciences Center, New Orleans, LA, United States. Vlachostergios, Panagiotis J. Department of Internal Medicine, New York University Lutheran Medical Center, Brooklyn, New York, NY, United States. Wang, Zongwei. Department of Urology, Massachusetts General Hospital, Harvard Medical School, Boston, MA, United States. Wellen, Kathryn E. Department of Cancer Biology, Perelman School of Medicine, University of Pennsylvania, Philadelphia, PA, United States. Whelan, Richard L. Department of Surgery, St. Luke's Roosevelt Hospital, New York, NY, United States. Yang, Eddy S. Department of Radiation Oncology, University of Alabama at Birmingham School of Medicine, Birmingham, AL, United States. Yang, Huanjie. The School of Life Science and Technology, Harbin Institute of Technology, Harbin, Heilongjiang, China. Yang, Xujuan. University of Illinois at Urbana Champaign, Champaign, IL, United States. Yaswen, Paul. Life Sciences Division, Lawrence Berkeley National Lab, Berkeley, CA, United States. Yedjou, Clement. Department of Biology, Jackson State University, Jackson, MS, United States. Yin, Xin. Medicine and Research Services, Veterans Affairs San Diego Healthcare System & University of California, San Diego, CA, United States. Zhu, Jiyue. Washington State University College of Pharmacy, Spokane, WA, United States. Zollo, Massimo. Centro di Ingegneria Genetica e Biotecnologia Avanzate, Naples, Italy; Department of Molecular Medicine and Medical Biotechnology, Federico II, Via Pansini 5, 80131 Naples, Italy.
Keywords: *Genetic Heterogeneity; *Molecular Targeted Therapy; *Neoplasms/th [Therapy]; *Precision Medicine; Antineoplastic Agents; Phytogenic; Antineoplastic Agents; Phytogenic/tu [Therapeutic Use]; Cancer hallmarks; Drug Resistance; Neoplasm; Drug Resistance; Neoplasm/ge [Genetics]; Genetic Heterogeneity; Humans; Integrative medicine; Molecular Targeted Therapy; Multi-targeted; Neoplasms; Neoplasms/ge [Genetics]; Neoplasms/pa [Pathology]; Neoplasms/pc [Prevention & Control]; Phytochemicals; Precision Medicine; Review; Signal Transduction; Targeted therapy; Tumor Microenvironment; Tumor Microenvironment/ge [Genetics]; anthocyanin; antineoplastic activity; antineoplastic agent; apoptosis; belinostat; berberine; breast cancer; cancer prevention; cancer therapy; cell immortalization; colorectal cancer; curcumin; deguelin; dept.bio; dietary intake; dinaciclib; drug cost; drug efficacy; drug resistance; drug safety; drug targeting; enterolactone; epigallocatechin gallate; gamma linolenic acid; genetic heterogeneity; genetics; genistein; genomic instability; gossypol; human; icosapentaenoic acid; imetelstat; inflammation; integrative medicine; interdisciplinary communication; kaempferol; luteolin; lycopene; melatonin; metastasis; metastasis inhibition; molecularly targeted therapy; naringenin; natural product; nonhuman; palbociclib; patent; pathology; perillyl alcohol; personalized medicine; phenotype; phytochemistry; recurrence risk; resveratrol; risk reduction; romidepsin; selinexor; signal transduction; silibinin; soybean; triptolide; tumor escape; tumor invasion; tumor microenvironment; tumor vascularization; unindexed drug; vorinostat; withaferin A; zerumbone

Cancer prevention and therapy through the modulation of the tumor microenvironment. - Casey, Stephanie C; Amedei, Amedeo; Aquilano, Katia; Azmi, Asfar S; Benencia, Fabian; Bhakta, Dipita; Bilsland, Alan E; Boosani, Chandra S; Chen, Sophie; Ciriolo, Maria Rosa; Crawford, Sarah; Fujii, Hiromasa; et al. (Seminars in Cancer Biology, 2015)
Cancer arises in the context of an in vivo tumor microenvironment. This microenvironment is both a cause and consequence of tumorigenesis. Tumor and host cells co-evolve dynamically through indirect and direct cellular interactions, eliciting multiscale effects on many biological programs, including cellular proliferation, growth, and metabolism, as well as angiogenesis and hypoxia and innate and adaptive immunity. Here we highlight specific biological processes that could be exploited as targets for the prevention and therapy of cancer. Specifically, we describe how inhibition of targets such as cholesterol synthesis and metabolites, reactive oxygen species and hypoxia, macrophage activation and conversion, indoleamine 2,3-dioxygenase regulation of dendritic cells, vascular endothelial growth factor regulation of angiogenesis, fibrosis inhibition, endoglin, and Janus kinase signaling emerge as examples of important potential nexuses in the regulation of tumorigenesis and the tumor microenvironment that can be targeted. We have also identified therapeutic agents as approaches, in particular natural products such as berberine, resveratrol, onionin A, epigallocatechin gallate, genistein, curcumin, naringenin, desoxyrhapontigenin, piperine, and zerumbone, that may warrant further investigation to target the tumor microenvironment for the treatment and/or prevention of cancer. Copyright © 2015 Elsevier Ltd. All rights reserved.
242 citations (Crossref) [2023-10-31] Place: England Casey, Stephanie C. Division of Oncology, Departments of Medicine and Pathology, Stanford University School of Medicine, Stanford, CA, United States. Amedei, Amedeo. Department of Experimental and Clinical Medicine, University of Florence, Florence, Italy. Aquilano, Katia. Department of Biology, University of Rome "Tor Vergata", Rome, Italy. Azmi, Asfar S. Department of Oncology, Wayne State University School of Medicine, Detroit, MI, United States. Benencia, Fabian. Department of Biomedical Sciences, Ohio University, Athens, OH, United States. Bhakta, Dipita. School of Chemical and Biotechnology, SASTRA University, Thanjavur 613401, Tamil Nadu, India. Bilsland, Alan E. Institute of Cancer Sciences, University of Glasgow, Glasgow, United Kingdom. Boosani, Chandra S. Department of Biomedical Sciences, School of Medicine, Creighton University, Omaha, NE, United States. Chen, Sophie. Ovarian and Prostate Cancer Research Laboratory, Guildford, Surrey, United Kingdom. Ciriolo, Maria Rosa. Department of Biology, University of Rome "Tor Vergata", Rome, Italy. Crawford, Sarah. Department of Biology, Southern Connecticut State University, New Haven, CT, United States. Fujii, Hiromasa. Department of Orthopedic Surgery, Nara Medical University, Kashihara, Japan. Georgakilas, Alexandros G. Physics Department, School of Applied Mathematics and Physical Sciences, National Technical University of Athens, Athens, Greece. Guha, Gunjan. School of Chemical and Biotechnology, SASTRA University, Thanjavur 613401, Tamil Nadu, India. Halicka, Dorota. New York Medical College, Valhalla, NY, United States. Helferich, William G. University of Illinois at Urbana-Champaign, Champaign-Urbana, IL, United States. Heneberg, Petr. Charles University in Prague, Third Faculty of Medicine, Prague, Czech Republic. Honoki, Kanya. Department of Orthopedic Surgery, Nara Medical University, Kashihara, Japan. Keith, W Nicol. Institute of Cancer Sciences, University of Glasgow, Glasgow, United Kingdom. Kerkar, Sid P. Center for Cancer Research, National Cancer Institute, National Institutes of Health, Bethesda, MD, United States. Mohammed, Sulma I. Department of Comparative Pathobiology, Purdue University Center for Cancer Research, West Lafayette, IN, United States. Niccolai, Elena. University of Florence, Florence, Italy. Nowsheen, Somaira. Medical Scientist Training Program, Mayo Graduate School, Mayo Medical School, Mayo Clinic, Rochester, MN, United States. Vasantha Rupasinghe, H P. Department of Environmental Sciences, Faculty of Agriculture, Dalhousie University, Nova Scotia, Canada. Samadi, Abbas. Sanus Biosciences, San Diego, United States. Singh, Neetu. Advanced Molecular Science Research Centre (Centre for Advanced Research), King George's Medical University, Lucknow, Uttar Pradesh, India. Talib, Wamidh H. Department of Clinical Pharmacy and Therapeutics, Applied Science University, Amman, Jordan. Venkateswaran, Vasundara. Division of Urology, Sunnybrook Health Sciences Centre, Toronto, Ontario, Canada. Whelan, Richard L. Mount Sinai Roosevelt Hospital, Icahn Mount Sinai School of Medicine, New York City, NY, United States. Yang, Xujuan. University of Illinois at Urbana-Champaign, Champaign-Urbana, IL, United States. Felsher, Dean W. Division of Oncology, Departments of Medicine and Pathology, Stanford University School of Medicine, Stanford, CA, United States. Electronic address: dfelsher@stanford.edu.
Keywords: *Carcinogenesis/de [Drug Effects]; *Neoplasms/dt [Drug Therapy]; *Neovascularization; Pathologic/dt [Drug Therapy]; *Tumor Microenvironment/ge [Genetics]; 5 chloro n2 [1 (5 fluoro 2 pyrimidinyl)ethyl] n4 (5 methyl 1h pyrazol 3 yl) 2; 4 pyrimidinediamine; Antineoplastic Agents; Antineoplastic Agents/tu [Therapeutic Use]; Cancer biology; Cancer prevention; Cancer therapy; Carcinogenesis; Carcinogenesis/ge [Genetics]; Cell Proliferation; Cell Proliferation/de [Drug Effects]; Humans; Janus kinase; Molecular Targeted Therapy; Neoplasms; Neoplasms/ge [Genetics]; Neoplasms/pc [Prevention & Control]; Neovascularization; Pathologic; Neovascularization; Pathologic/ge [Genetics]; Neovascularization; Pathologic/pc [Prevention & Control]; Review; Signal Transduction; Tumor Microenvironment; Tumor Microenvironment/de [Drug Effects]; Tumor microenvironment; antiinflammatory activity; antineoplastic agent; antioxidant activity; antiproliferative activity; apoptosis; bacterial infection; berberine; bevacizumab; cancer prevention; cancer therapy; candidiasis; carcinogenesis; cell proliferation; cholesterol synthesis; cisplatin; colorectal cancer; curcumin; cytokine production; dendritic cell; dept.bio; desoxyrhapontigenin; drug cytotoxicity; drug effects; drug potentiation; drug structure; drug targeting; endoglin; epigallocatechin gallate; fatty liver; fibrosis; genetics; genistein; genomic instability; glioblastoma; human; hydroxymethylglutaryl coenzyme A reductase inhibitor; hypercholesterolemia; hyperlipidemia; hypoxia; indoleamine 2; 3 dioxygenase; interleukin 6; kidney cancer; liver cancer; liver cell carcinoma; lung cancer; lung metastasis; macrophage activation; metastasis inhibition; molecularly targeted therapy; mycosis; naringenin; natural product; non insulin dependent diabetes mellitus; nonhuman; obesity; oncogene; onionin A; paclitaxel; pancreas tumor; parasitosis; piperine; reactive oxygen metabolite; resveratrol; signal transduction; sorafenib; stomach cancer

On the origins of autism: The Quantitative Threshold Exposure hypothesis. - Crawford, S (Medical hypotheses, 2015)
The Quantitative Threshold Exposure (QTE) hypothesis is a multifactorial threshold model that accounts for the cumulative effects of risk factor exposure in both the causation of autism spectrum disorder (ASD) and its dramatic increase over the past 30 years. The QTE hypothesis proposes that ASD is triggered by the cumulative effects of high-level exposure to endogenous and environmental factors that act as antigens to impair normal immune system (IS) and associated central nervous system (CNS) functions during critical developmental stages. The quantitative threshold parameters that comprise a cumulative risk for the development of ASD are identified by the assessment of documented epidemiological factors that, in sum, determine the likelihood that ASD will occur as a result of their effects on critically integrated IS and CNS pathways active during prenatal, neo-natal and early childhood brain maturation. The model proposes an explanation for the relationship between critical developmental stages of brain/immune system development in conjunction with the quantitative effects of genetic and environmental risk factors that may interface with these critical developmental windows. This model may be useful even when the individual contributions of specific risk factors cannot be quantified, as it proposes that the combined quantitative level of exposure to risk factors for ASD rather than exposure to any one risk factor per se defines threshold occurrence rates. Copyright © 2015 Elsevier Ltd. All rights reserved.
10 citations (Crossref) [2023-10-31] Place: United States Crawford, S. Department of Biology, Southern Connecticut State University, 501 Crescent Street, New Haven, CT 06515, United States. Electronic address: crawfords2@southernct.edu.
Keywords: *Autistic Disorder/ep [Epidemiology]; *Environmental Exposure/sn [Statistics & Numerical Data]; *Epidemiologic Methods; *Risk Assessment/mt [Methods]; *Threshold Limit Values; 5 HTT gene; 5 hydroxytryptophan; Article; Autistic Disorder; Causality; DNA polymorphism; Environmental Exposure; Epidemiologic Methods; Evidence-Based Medicine; Humans; Incidence; RLN gene; Risk Assessment; Threshold Limit Values; autism; autoimmune disease; brain dysfunction; brain maturation; cannabinoid 1 receptor; cannabinoid 2 receptor; cannabis use; central nervous system function; childhood disease; childhood feeding; copy number variation; dept.bio; developmental stage; disease association; disease severity; environmental exposure; environmental factor; epidemiological data; evidence based medicine; feeding; feeding behavior; genetic association; genetic predisposition; genetic risk; high risk population; human; hypothesis; immunoreactivity; incidence; infant feeding; intrauterine infection; n acetylgalactosaminidase; nervous system development; nonbiological model; nonhuman; pediatric infectious disease; perinatal period; prevalence; procedures; quantitative threshold exposure hypothesis; reelin; risk assessment; risk factor; statistics and numerical data; tetrahydrocannabinol; threshold limit value; threshold model; unclassified drug; unclassified enzyme; vitamin D deficiency

Physiological responses related to increased grain yield under drought in the first biotechnology‐derived drought‐tolerant maize - Nemali, Krishna S; Bonin, Christopher P; Dohleman, Frank G; Stephens, Mike; Reeves, William; Nelson, Donald E; Castiglioni, Paolo; Whitsel, Joy; Sammons, Bernard; Silady, Rebecca A; Anstrom, Donald; Sharp, Robert E; et al. (Plant Cell and Environment, 2015)
Maize (Zea mays ssp. mays L.) is highly susceptible to drought stress. This work focused on whole-plant physiological mechanisms by which a biotechnology-derived maize event expressing bacterial cold shock protein B (CspB), MON 87460, increased grain yield under drought. Plants of MON 87460 and a conventional control (hereafter 'control') were tested in the field under well-watered (WW) and water-limited (WL) treatments imposed during mid-vegetative to mid-reproductive stages during 2009-2011. Across years, average grain yield increased by 6% in MON 87460 compared with control under WL conditions. This was associated with higher soil water content at 0.5 m depth during the treatment phase, increased ear growth, decreased leaf area, leaf dry weight and sap flow rate during silking, increased kernel number and harvest index in MON 87460 than the control. No consistent differences were observed under WW conditions. This indicates that MON 87460 acclimated better under WL conditions than the control by lowering leaf growth which decreased water use during silking, thereby eliciting lower stress under WL conditions. These physiological responses in MON 87460 under WL conditions resulted in increased ear growth during silking, which subsequently increased the kernel number, harvest index and grain yield compared to the control. Copyright © 2014 The Authors. Plant, Cell & Environment published by John Wiley & Sons Ltd.
80 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/043-772-605-388-897 tex.type: [object Object]
Keywords: *Biotechnology/mt [Methods]; *Droughts; *Zea mays/ph [Physiology]; Bacteria (microorganisms); Bacterial Proteins; Bacterial Proteins/ge [Genetics]; Biotechnology; CspB; Droughts; Ear; Edible Grain; Harvest index; Leaf area; Plant Leaves; Plant Leaves/ph [Physiology]; Plants; Genetically Modified; Plants; Genetically Modified/ph [Physiology]; Sap flow; Soil; Soil water content; Soil/ch [Chemistry]; Water use; Yield; Zea mays; acclimation; adaptation; bacterial protein; biotechnology; chemistry; cold-shock protein CspB; Bacteria; crop yield; dept.bio; drought; drought stress; food grain; genetics; index method; leaf area; maize; physiological response; physiology; plant leaf; procedures; protein; sap flow; soil; soil water; tolerance; transgenic plant; water use efficiency

Anti-inflammatory/antioxidant use in long-term maintenance cancer therapy: a new therapeutic approach to disease progression and recurrence. - Crawford, Sarah (Therapeutic advances in medical oncology, 2014)
The chronic, progressive clinical characteristics of many adult solid tumor malignancies suggest that a more effective therapeutic approach to cancer management may require long-term intervention using nontoxic systemic agents that block critical components of abnormal tumor physiology. Two highly promising systemic targets common to the development, progression and recurrence of many common cancers are dysregulated inflammatory and oxidation/reduction (redox) pathways. Compelling clinical data support the use of anti-inflammatory and antioxidant agents as a therapeutic modality for long-term use in patients diagnosed with several common cancers, including colon cancer and breast cancer. The therapeutic paradigm presented in this paper is the product of a synthesis of what is currently understood about the biological effects of inflammation and oxidative stress that contribute to tumorigenesis, disease progression and recurrence as well as results obtained from research on the use of prophylactics with anti-inflammatory or antioxidant properties in cancer prevention and treatment.
51 citations (Crossref) [2023-10-31] Place: England Crawford, Sarah. Cancer Biology Research Laboratory, Southern Connecticut State University, New Haven, CT 06515, USA.
Keywords: anti-inflammatory agents; antiinflammatory agent; antioxidant; antioxidants; axitinib; bevacizumab; bosutinib; breast cancer; cabozantinib; cancer epidemiology; cancer growth; cancer recurrence; cancer therapy; cetuximab; chemoprophylaxis; chemotherapy; colon cancer; crizotinib; dasatinib; dept.bio; erlotinib; everolimus; gefitinib; human; imatinib; inflammation; ipilimumab; lapatinib; long term care; long-term maintenance cancer therapy; meta analysis (topic); nilotinib; nonhuman; oxidative stress; panitumumab; pazopanib; ponatinib; priority journal; randomized controlled trial (topic); reactive oxygen metabolite; regorafenib; review; ruxolitinib; sorafenib; sunitinib; systematic review (topic); temsirolimus; tofacitinib; trastuzumab; trastuzumab emtansine; unindexed drug; vandetanib; vemurafenib

Cluster M mycobacteriophages Bongo, PegLeg, and Rey with unusually large repertoires of tRNA isotypes - Pope, Welkin H; Anders, Kirk R; Baird, Madison A; Bowman, Charles A; Boyle, Michelle M; Broussard, Gregory W; Chow, Tiffany W; Clase, Kari; Cooper, Shannon D; Cornely, Kathleen; Dejong, Randall J; Delesalle, Veronique A; et al. (Journal of Virology, 2014)
Genomic analysis of a large set of phages infecting the common host Mycobacterium smegmatis mc2155 shows that they span considerable genetic diversity. There are more than 20 distinct types that lack nucleotide similarity with each other, and there is considerable diversity within most of the groups. Three newly isolated temperate mycobacteriophages, Bongo, PegLeg, and Rey, constitute a new group (cluster M), with the closely related phages Bongo and PegLeg forming subcluster M1 and the more distantly related Rey forming subcluster M2. The clusterMmycobacteriophages have siphoviral morphologies with unusually long tails, are homoimmune, and have larger than average genomes (80.2 to 83.7 kbp). They exhibit a variety of features not previously described in other mycobacteriophages, including noncanonical genome architectures and several unusual sets of conserved repeated sequences suggesting novel regulatory systems for both transcription and translation. In addition to containing transfer-messenger RNA and RtcB-like RNA ligase genes, their genomes encode 21 to 24 tRNA genes encompassing complete or nearly complete sets of isotypes. We predict that these tRNAs are used in late lytic growth, likely compensating for the degradation or inadequacy of host tRNAs. They may represent a complete set of tRNAs necessary for late lytic growth, especially when taken together with the apparent lack of codons in the same late genes that correspond to tRNAs that the genomes of the phages do not obviously encode. © 2014, American Society for Microbiology.
40 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/014-261-678-659-153 tex.type: [object Object]
Keywords: Base Composition; Base Sequence; Codon; Conserved Sequence; DNA binding motif; DNA sequence; Gene Order; Genome Size; Genome; Viral; Inverted Repeat Sequences; Lysogeny; Multigene Family; Mycobacteriophages; Mycobacterium smegmatis; Open Reading Frames; Phylogeny; RNA cleavage; RNA degradation; RNA translation; RNA; Transfer; RNA; Viral; Repetitive Sequences; Nucleic Acid; Sequence Alignment; Virion; Virus Assembly; article; controlled study; dept.bio; gene cassette; gene control; gene structure; genetic analysis; genetic transcription; genetic variability; membrane protein; mycobacteriophage; mycobacteriophage Bongo; mycobacteriophage M; mycobacteriophage Pegleg; mycobacteriophage Rey; nonhuman; nucleotide sequence; priority journal; protein gp19; protein gp23; protein gp24; protein gp26; protein gp30; protein gp31; protein gp39; single stranded DNA binding protein; tmp gene; transfer RNA; unclassified drug; viral genetics; virus assembly; virus classification; virus immunity; virus morphology

Postcranial skeleton of Postosuchus kirkpatricki (Archosauria: Paracrocodylomorpha), from the upper Triassic of the United States - Weinbaum, Jonathan C (Geological Society, London, Special Publications, 2013)
Postosuchus kirkpatricki is a Late Triassic (Norian) 'rauisuchid' archosaur from North America. The initial description of the Postosuchus type material included elements from two poposaurids. This confusion has prevented adequate description of the material. Recent examination of the type material and other specimens of Postosuchus, and of related taxa, has helped clarify the osteology of Postosuchus. The type specimens represent c. 75% of the skeleton. Together with other referred material, Postosuchus remains one of the most completely known rauisuchids. The paratype skeleton, which is relatively complete, would have been c. 3.5-4 m in length, and the holotype would have been closer to 5-6 m. Analysis of the postcranial skeleton of Postosuchus suggests that it may have been an obligate biped (based in part on limb proportions, which are similar to some theropod dinosaurs, the size of the manus (30% of the size of the pes) and the highly reduced nature of the digits and vertebral measurements). Possible postcranial autapomorphies of Postosuchus include a large, rugose triangular supra-acetabular buttress confluent with the dorsal margin of the iliac blade, and a symmetrical pes with digits two and three being roughly equal in length. © The Geological Society of London 2013.
35 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/148-386-820-858-734 tex.type: [object Object]
Keywords: Triassic; United States; dept.bio; osteology; peer-reviewed; reptile; skeleton; taxonomy; type specimen

A taxonomic and biostratigraphic re-evaluation of the Post Quarry vertebrate assemblage from the Cooper Canyon Formation (Dockum Group, Upper Triassic) of southern Garza County, western Texas - Martz, Jeffrey W.; Mueller, Bill D.; Nesbitt, Sterling J.; Stocker, Michelle R.; Parker, William G.; Atanassov, Momchil N.; Fraser, Nicholas C.; Weinbaum, Johnathan; Lehane, James R. (Earth and Environmental Science Transactions of The Royal Society of Edinburgh, 2012)
The Post Quarry, within the lower part of the type section of the Upper Triassic Cooper Canyon Formation in southern Garza County, western Texas, contains a remarkably diverse vertebrate assemblage. The Post Quarry has produced: the small temnospondyl Rileymillerus cosgriffi; the metoposaurid Apachesaurus gregorii; possible dicynodonts and eucynodonts; a clevosaurid sphenodontian; non-archosauriform archosauromorphs (Trilophosaurus dornorum, simiosaurians, and possibly Malerisaurus); the phytosaur Leptosuchus; several aetosaurs (Calyptosuchus wellesi, Typothorax coccinarum, Paratypothorax, and Desmatosuchus smalli); the poposauroid Shuvosaurus inexpectatus (Chatterjeea elegans); the rauisuchid Postosuchus kirkpatricki; an early crocodylomorph; several dinosauromorphs (the lagerpetid Dromomeron gregorii, the silesaurid Technosaurus smalli, a herrerasaurid, and an early neotheropod); and several enigmatic small diapsids. Revised lithostratigraphic correlations of the lower Cooper Canyon Formation with the Tecovas Formation, the occurrence of Leptosuchus, and the overall composition of the assemblage indicate that the Post Quarry falls within the Adamanian biozone, and not the Revueltian biozone. Stratigraphic subdivision of the Adamanian biozone may be possible, and the Post Quarry may be correlative with the upper part of the Adamanian biozone in Arizona. The age of the Post Quarry assemblage is possibly late Lacian or earliest Alaunian (late early Norian or earliest middle Norian), between 220 and 215 Ma. © 2013 The Royal Society of Edinburgh.
28 citations (Crossref) [2023-10-31] Citation Key Alias: pop00103 tex.type: [object Object]
Keywords: Adamanian biozone; Dinosauromorpha; Garza County; Leptosuchus; Pseudosuchia; Texas; Triassic; United States; biostratigraphy; biozonation; dept.bio; faunal diversity; fossil assemblage; land vertebrate faunachrons; stratigraphic correlation; taxonomy; type locality; vertebrate; vertebrate locality

A survey of skeletal elements in the orbit of Pseudosuchia and the origin of the crocodylian palpebral - Nesbitt, Sterling J.; Turner, Alan H.; Weinbaum, Jonathan C. (Earth and Environmental Science Transactions of The Royal Society of Edinburgh, 2012)
14 citations (Crossref) [2023-10-31] Citation Key Alias: pop00106 tex.type: [object Object]
Keywords: Aetosaurus ferratus; Archosauria; Crocodylomorpha; Postosuchus kirkpatricki; Saurosuchus galilei; crocodilian; dept.bio; evolution; extinction; fossil assemblage; novelty; skeletal remains; supraorbital; taxonomy

The long journey of stem cell therapeutics. - Crawford, Sarah (Genome Medicine, 2012)
A report on the Euroepistem 2011 meeting 'Epigenomic Programming and Stem Cells for Drug Discovery', Paris, France, 21-22 November 2011.
0 citations (Crossref) [2023-10-31] Place: England Crawford, Sarah. Cancer Biology Research Laboratory, Southern Connecticut State University, 501 Crescent Street, New Haven, CT 06515, USA. crawfords2@southernct.edu.
Keywords: Article; dept.bio; embryonic stem cell; epigenetics; gene; gene silencing; human; induced pluripotent stem cell; nonhuman; priority journal; stem cell transplantation; transcription regulation

A new species of Acentrella Bengtsson (Ephemeroptera: Baetidae) from New York and New England (USA), redescription of the nymph of A. parvula (McDunnough), and key to known adult males of Nearctic Acentrella - Burian, Steven K; Myers, Luke W (Aquatic Insects, 2011)
A new species Acentrella rallatoma (type locality: Connetquot River, Oakdale, NY, USA) is described from nymphs and reared adults. Additional specimens were studied from southeastern New York, southeastern New Hampshire, coastal Connecticut, and Martha's Vineyard, MA, USA. Nymphs can be separated from those of other Nearctic species by: scraper-like outer incisors of mandibles, cerci alternately banded from bases to tips, and row of robust bristle-like setae (with modified tips) on dorsal edge of femora. Male imagos can be separated from those that lack hind wings by: distinctive colour pattern of abdominal terga, and genitalia with pigmented sclerotised penes cover. Comparative analysis of A. rallatoma with other Nearctic species revealed a lack of comparative data on nymphs of its presumptive sister species A. parvula. To facilitate future studies of this group, the nymph of A. parvula is redescribed and regional differences are discussed. Abdominal colour patterns of A. parvula that vary over its range from Florida, USA to Labrador, Canada are illustrated. Problems concerning genus-level diagnostic characters for Acentrella nymphs and adults are discussed to facilitate placement of future taxa. To complement existing keys to Nearctic nymphs of Acentrella a provisional key to the known adult males is given. © 2011 Copyright Taylor and Francis Group, LLC.
1 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/062-428-772-783-321 tex.type: [object Object]
Keywords: A. parvula; Acentrella; Acentrella parvula; Baetidae; Ephemeroptera; dept.bio; new species

Effect of increased extracellular Ca++ on microvesicle production and tumor spheroid formation - Crawford, Sarah; Diamond, Deanna; Brustolon, Laura; Penarreta, Rafaela (Cancer microenvironment : official journal of the International Cancer Microenvironment Society, 2011)
Research on the composition of the tumor micro-environment has demonstrated that membrane delimited microvesicles are shed from many types of malignant tumors, in the peripheral blood of cancer patients as well as in culture media of tumor cells propagated in vitro (Ginestra et al. Anticancer Res 18:3433-3437, 1998). Their documented effects involve the activation of signal transduction pathways by cellular cross-talk that are associated with epigenetic mechanisms that may be important in tumor progression, metastasis, and the activation of angiogenesis (Distler et al. Arthritis Rheum 52:3337-3348, 2005). Live cell imaging microscopic studies conducted in our laboratory of the formation of solid tumor spheroids in vitro show that the shedding of microvesicular structures from tumor cells occurs during this process. The observed properties of the tumor microvesicles suggest a role in solid tumor formation and intercellular communication. The tumor associated microvesicles were shown to be non-apoptotic based on the absence of fluorescent nuclear staining by acridine orange/ethidium bromide staining. Increased concentration of extracellular Ca(++) [5-20 mM] resulted in an increase in the production of tumor-derived microvesicles and also to result in the formation of tumor spheroids whose size was considerably smaller than controls. Increased extracellular [Ca(++)] was also observed to induce the rapid dissociation of solid tumor spheroids to smaller cell aggregates in the absence of significant apoptosis.
19 citations (Crossref) [2023-10-31] Place: Netherlands Crawford, Sarah. Cancer Biology Research Laboratory, Biology Department, Southern Connecticut State University, Jennings Hall 219, 501 Crescent Street, New Haven, CT 06515 USA.
Keywords: Extracellular Ca++; Live cell imaging; Multicellular tumor spheroid; Tumor associated microvesicle; acridine orange; angiogenesis; apoptosis; article; breast carcinoma; calcium ion; cancer cell culture; cell aggregation; cell nucleus; concentration (parameters); controlled study; cytochemistry; dept.bio; epigenetics; ethidium bromide; extracellular calcium; glioblastoma; human; human cell; in vitro study; membrane vesicle; metastasis potential; microscopy; molecular interaction; osteosarcoma; priority journal; signal transduction; tumor growth; tumor microenvironment; tumor spheroid; tumor vascularization

Technological variation in the earliest Oldowan from Gona, Afar, Ethiopia - Stout, Dietrich; Semaw, Sileshi; Rogers, Michael J.; Cauche, Dominique (Journal of Human Evolution, 2010)
Inter-site technological variation in the archaeological record is one of the richest potential sources of information about Plio-Pleistocene hominid behavior and evolution. However, appropriate methods for describing and comparing Oldowan assemblages have yet to be agreed upon, and interpretation of the early record remains highly controversial. Particularly salient is disagreement over whether the Oldowan is a single technological phenomenon or is more accurately divided into multiple regional and/or chronological traditions, perhaps including a less developed Pre-Oldowan phase in the late Pliocene. Some of this disagreement reflects theoretical and methodological differences between research traditions and some is more directly evidential. Here we present a framework for describing and interpreting Oldowan variation and apply it to three Pliocene assemblages (EG-10, EG-12, and OGS-7) from Gona, all dated to c. 2.6 million years (Ma). Results indicate proficient knapping and a full range of Oldowan reduction strategies in these earliest known occurrences, consistent with the idea of an Oldowan “technological stasis” from 2.6–1.6Ma. Patterns of variation in raw material selection and predominant reduction strategy at each site clearly indicate the importance of cultural transmission in the Oldowan, but confounding ecological and economic variation continue to render interpretation in terms of multiple tool making traditions or species inappropriate. We propose that cultural transmission and ecological adaptation should be recognized as complementary, rather than mutually exclusive, mechanisms in future attempts to explain Oldowan technological variation.
157 citations (Crossref) [2023-10-31] tex.ids: ISI:000279276600002, Rogers2010, lens.org/048-194-199-785-52X tex.orcid-numbers: [object Object] tex.researcherid-numbers: [object Object] tex.unique-id: [object Object]
Keywords: Animals; Archaeology; Chaîne opératoire; Chi-Square Distribution; Cultural Evolution; Early Stone Age; Environment; Ethiopia; Fossils; Gona; Hominidae; Humans; Lithic technology; Paleolithic; Paleontology; Pliocene-Pleistocene boundary; Pre-Oldowan; Stone Age; Tool Use Behavior; animal; archaeological evidence; archeology; chi square distribution; cultural anthropology; cultural geography; dept.ant; dept.bio; environment; evolution; fossil; geochronology; hominid; human; paleontology; peer-reviewed; spatial variation; technological development; technology adoption; tool use

The ratio of gametophytes to tetrasporophytes of intertidal chondrus crispus (gigartinaceae) across a salinity gradient - Guidone, Michele; Grace, Sean (Rhodora, 2010)
6 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/031-225-776-360-25X tex.type: [object Object]
Keywords: Chondrus; Chondrus crispus; Gigartinaceae; dept.bio

Reproductive behavior in horseshoe crabs: Does density matter? - Mattei, Jennifer; Beekey, Mark A; Rudman, Adam; Woronik, Alyssa (Current Zoology, 2010)
While the four species of horseshoe crabs share many common reproductive traits with respect to their reproductive systems, they do differ with respect to their mating behavior (monogamy vs. polygynandry). Past research has attributed these differences to a number of factors including: spawning densities, operational sex ratios (OSR's), male condition (or age), environmental and/or genetic factors, or a combination thereof. Mating behaviors in the three Asian horseshoe crab species (Tachypleus gigas, T. tridentatus, and Carcinoscorpius rotundicauda) with low spawning densities and 1:1 operational sex ratios are typically monogamous. In Limulus polyphemus, mating behavior is more variable ranging from monogamy to polygynandry. Here we provide evidence, through a long term behavioral study, that variation in mating behavior is influenced by population density in L. polyphemus. Our study population on two beaches in Connecticut (Long Island Sound) have a spawning density 400 times less than that found in Delaware Bay (0.002 females/m2 vs. 0.8 females/m2) but similar operational sex ratios. Between 90%-95% of all spawning females in CT were paired with only one male, thus exhibiting monogamous behavior. In contrast, between 30 and 60% of spawning females in Delaware Bay have more than one mate and produce clutches of eggs with multiple paternities. Male condition played no role in mating behavior in CT populations. We also observed that on average 18% of the females on the spawning beaches are single. These results suggest that population density is an important condition that determines mating behavior. Also, low population density may lead to decreased mate finding ability and lost opportunities for spawning [Current Zoology 56 (5): 634-642, 2010]. © 2010 Current Zoology.
32 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/090-298-586-515-449 tex.type: [object Object]
Keywords: Carcinoscorpius rotundicauda; Limulus; Limulus polyphemus; Mating behavior; Merostomata; Monogamy; Polygynandry; Population density; Tachypleus gigas; dept.bio

Biotechnological potential of aquatic plant-microbe interactions. - Stout, L; Nusslein, K (Current opinion in biotechnology, 2010)
The rhizosphere in terrestrial systems is the region of soil surrounding plant roots where there is increased microbial activity; in aquatic plants, this definition may be less clear because of diffusion of nutrients in water, but there is still a zone of influence by plant roots in this environment [1]. Within that zone chemical conditions differ from those of the surrounding environment as a consequence of a range of processes that were induced either directly by the activity of plant roots or by the activity of rhizosphere microflora. Recently, there are a number of new studies related to rhizospheres of aquatic plants and specifically their increased potential for remediation of contaminants, especially remediation of metals through aquatic plant-microbial interaction. Copyright 2010 Elsevier Ltd. All rights reserved.
44 citations (Crossref) [2023-10-31] Place: England Stout, L. Department of Biology, Southern Connecticut State University, New Haven, CT 06515, United States. stoutl1@southernct.edu
Keywords: *Biotechnology/mt [Methods]; *Plants/mi [Microbiology]; 1 aminocyclopropanecarboxylic acid; Aquaculture; Aquatic plants; Biodegradation; Environmental; Biotechnology; Chemical conditions; Hydrogen-Ion Concentration; Microbial activities; Microbial interactions; Microflora; New study; Plant Roots; Plant Roots/mi [Microbiology]; Plant roots; Plants; Pollution; Rhizobium leguminosarum; Soils; Surrounding environment; Terrestrial systems; Zone of influences; adenosine triphosphatase; aquatic environment; aquatic flora; bacterial strain; biofilm; biofiltration; biotechnological procedures; biotechnology; cadmium; chromium; cobalt; copper; dept.bio; environmental exposure; heavy metal removal; homeostasis; metallothionein; microorganism; nickel; nonhuman; pH; phytochelatin; phytoremediation; plant growth; plant microorganism interaction; priority journal; process technology; protein binding; protein synthesis; review; rhizofiltration; rhizosphere; siderophore; transgene; volatilization; zinc

The mid-network mayfly maxima (MMM): A general pattern of mayfly (Ephemeroptera) species richness within drainage networks and what we can learn from it - Burian, Steven K. (Zoosymposia, 2019)
For the last 93 years mayfly diversity has been studied at all taxonomic levels from families to populations and all spatial and temporal scales. This has resulted in the description of almost every possible pattern with regard to latitude, elevation, habitat, climate, and season. However, if the focus is on species and sampling restricted to nymphs and the spatial scale limited to drainage networks, then a single recurring pattern appears—the hump-shaped Mid-network Mayfly Maxima (MMM). Past studies have attempted to explain this hump-shaped pattern with regards to some combination of ecologic, hydrologic, climatic, anthropogenic, or historic variables. There is wide agreement that some of these variables are important to the occurrence and distribution of individual species, but there is no consensus as to what combination of these variables comprises the best general explanation of the humped-shaped pattern. Because of the lack of agreement on how to explain this recurring pattern for mayflies and an unwillingness to acknowledge it as a general feature of drainage networks, where mayflies occur, we have become stuck trying to tease out a cause and have failed to recognize that although knowing a cause is important it may not be relevant to the broader use of this information for biomonitoring, climate monitoring, habitat management, and conservation now. I believe that there is sufficient evidence that the MMM exists and occurs in almost every major drainage system and is reasonably predictable using basic attributes of drainage networks pertinent to the aquatic life stage (nymphs). Herein I will summarize pertinent studies that support this contention; reexamine some results from one of the most comprehensive recent studies that included mayfly taxa along altitudinal gradients in North America by Gill et al. (2014), as well as a test dataset from a river in western Maine, USA; comment on information needed to estimate the location of MMM in any drainage network and how the MMM can be used; and discuss how the extent of common vs. rare species affect the perceptions of the regional species pool and the MMM.
Number: 1
Keywords: Ephemeroptera; Mayfly; dept.bio; peer-reviewed; ⚠️ Invalid DOI

So You Want to Start an Institutional Biosafety Committee - Schniederberend, Maren; Fontes, Benjamin; Jeffrey, Rachel (Applied Biosafety, 2019)
Introduction: The number of institutions engaging in research with potentially biohazardous materials has increased, indicating a need for newly formed Institutional Biosafety Committees (IBCs) in the United States and for similar biorisk management committees located outside the United States. Our institution identified the need for an IBC due to the growth of pertinent activities on campus. Objectives: This article shares our experiences creating a new IBC at our institution from September 2017 to April 2019. Our lessons learned and approaches to the challenges faced may be helpful to others finding themselves with similar needs. Methods: In this case study, we outline IBC membership, documents, relationships with federal agencies and within the institution, creation of registration forms, and the review process. Along with our account, we have included links to helpful resources from federal agencies. Results: At the time of the submission of this article, we have established our IBC and reviewed two registrations. Conclusion: This case report demonstrates the successful creation of an IBC that works for our current institutional needs. © ABSA International 2019.
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/177-624-967-404-713, pop00102 tex.type: [object Object]
Keywords: BMBL; EHS; IBC; NIH Guidelines; biorisk management; dept.bio; peer-reviewed; standard operating procedure

Ephemeroptera - Burian, Steven K. (An introduction to the aquatic insects of North America, 2019)
"As with previous editions, this new one is intended to serve as a standard guide to the aquatic and semiaquatic insects of North America"–Preface, xi.
Google-Books-ID: nLh_yAEACAAJ
Keywords: dept.bio; faculty_collection

Understanding maladaptation by uniting ecological and evolutionary perspectives - Brady, Steven P.; Bolnick, Daniel I.; Barrett, Rowan D. H.; Chapman, Lauren; Crispo, Erika; Derry, Alison M.; Eckert, Christopher G.; Fraser, Dylan J.; Fussmann, Gregor F.; Gonzalez, Andrew; Guichard, Frederic; Lamy, Thomas; et al. (The American Naturalist, 2019)
Evolutionary biologists have long trained their sights on adaptation, focusing on the power of natural selection to produce relative fitness advantages while often ignoring changes in absolute fitness. Ecologists generally have taken a different tack, focusing on changes in abundance and ranges that reflect absolute fitness while often ignoring relative fitness. Uniting these perspectives, we articulate various causes of relative and absolute maladaptation and review numerous examples of their occurrence. This review indicates that maladaptation is reasonably common from both perspectives, yet often in contrasting ways. That is, maladaptation can appear strong from a relative fitness perspective, yet populations can be growing in abundance. Conversely, resident individuals can appear locally adapted (relative to nonresident individuals) yet be declining in abundance. Understanding and interpreting these disconnects between relative and absolute maladaptation, as well as the cases of agreement, is increasingly critical in the face of accelerating human-mediated environmental change. We therefore present a framework for studying maladaptation, focusing in particular on the relationship between absolute and relative fitness, thereby drawing together evolutionary and ecological perspectives. The unification of these ecological and evolutionary perspectives has the potential to bring together previously disjunct research areas while addressing key conceptual issues and specific practical problems. © 2019 by The University of Chicago. All rights reserved.
54 citations (Crossref) [2023-10-31]
Keywords: Adaptation; Fitness; Global change; Maladaptation; adult; article; dept.bio; drawing; ecologist; environmental change; female; global change; human; human experiment; male; natural selection; peer-reviewed; resident

Causes of maladaptation. - Brady, Steven P; Bolnick, Daniel I; Angert, Amy L; Gonzalez, Andrew; Barrett, Rowan D H; Crispo, Erika; Derry, Alison M; Eckert, Christopher G; Fraser, Dylan J; Fussmann, Gregor F; Guichard, Frederic; Lamy, Thomas; et al. (Evolutionary applications, 2019)
Evolutionary biologists tend to approach the study of the natural world within a framework of adaptation, inspired perhaps by the power of natural selection to produce fitness advantages that drive population persistence and biological diversity. In contrast, evolution has rarely been studied through the lens of adaptation's complement, maladaptation. This contrast is surprising because maladaptation is a prevalent feature of evolution: population trait values are rarely distributed optimally; local populations often have lower fitness than imported ones; populations decline; and local and global extinctions are common. Yet we lack a general framework for understanding maladaptation; for instance in terms of distribution, severity, and dynamics. Similar uncertainties apply to the causes of maladaptation. We suggest that incorporating maladaptation-based perspectives into evolutionary biology would facilitate better understanding of the natural world. Approaches within a maladaptation framework might be especially profitable in applied evolution contexts - where reductions in fitness are common. Toward advancing a more balanced study of evolution, here we present a conceptual framework describing causes of maladaptation. As the introductory article for a Special Feature on maladaptation, we also summarize the studies in this Issue, highlighting the causes of maladaptation in each study. We hope that our framework and the papers in this Special Issue will help catalyze the study of maladaptation in applied evolution, supporting greater understanding of evolutionary dynamics in our rapidly changing world.
79 citations (Crossref) [2023-10-31] Place: England Brady, Steven P. Biology Department Southern Connecticut State University New Haven CT USA. Bolnick, Daniel I. Department of Ecology and Evolutionary Biology University of Connecticut Mansfield CT USA. Angert, Amy L. Departments of Botany and Zoology University of British Columbia Vancouver BC Canada. Gonzalez, Andrew. Department of Biology McGill University Montreal QC Canada. Gonzalez, Andrew. Quebec Centre for Biodiversity Science, Stewart Biology McGill University Montreal QC Canada. Barrett, Rowan D H. Department of Biology McGill University Montreal QC Canada. Barrett, Rowan D H. Quebec Centre for Biodiversity Science, Stewart Biology McGill University Montreal QC Canada. Barrett, Rowan D H. Redpath Museum McGill University Montreal QC Canada. Crispo, Erika. Department of Biology Pace University New York NY USA. Derry, Alison M. Quebec Centre for Biodiversity Science, Stewart Biology McGill University Montreal QC Canada. Derry, Alison M. Departement des sciences biologiques Universite du Quebec a Montreal Montreal QC Canada. Eckert, Christopher G. Department of Biology Queen's University Kingston ON Canada. Fraser, Dylan J. Department of Biology Concordia University Montreal QC Canada. Fussmann, Gregor F. Department of Biology McGill University Montreal QC Canada. Fussmann, Gregor F. Quebec Centre for Biodiversity Science, Stewart Biology McGill University Montreal QC Canada. Guichard, Frederic. Department of Biology McGill University Montreal QC Canada. Guichard, Frederic. Quebec Centre for Biodiversity Science, Stewart Biology McGill University Montreal QC Canada. Lamy, Thomas. Departement de sciences biologiques Universite de Montreal Montreal QC Canada. Lamy, Thomas. Marine Science Institute University of California Santa Barbara CA USA. McAdam, Andrew G. Department of Integrative Biology University of Guelph Guelph ON Canada. Newman, Amy E M. Department of Integrative Biology University of Guelph Guelph ON Canada. Paccard, Antoine. McGill University Genome Center Montreal QC Canada. Rolshausen, Gregor. Senckenberg Biodiversity and Climate Research Centre (SBiK-F) Frankfurt am Main Germany. Simons, Andrew M. Department of Biology Carleton University Ottawa ON Canada. Hendry, Andrew P. Department of Biology McGill University Montreal QC Canada. Hendry, Andrew P. Quebec Centre for Biodiversity Science, Stewart Biology McGill University Montreal QC Canada. Hendry, Andrew P. Redpath Museum McGill University Montreal QC Canada.
Keywords: adaptation; dept.bio; fitness; global change; maladaptation; peer-reviewed

Fundamental and applied pursuits in evolutionary toxicology are mutually beneficial: A reply to Hahn (2018). - Brady, Steven P; Monosson, Emily; Matson, Cole; Bickham, John W (Evolutionary applications, 2019)
0 citations (Crossref) [2023-10-31] Place: England Brady, Steven P. Biology Department Southern Connecticut State University New Haven CT USA. Monosson, Emily. Ronin Institute for Independent Scholars, Department of Environmental Conservation University of Massachusetts Amherst MA USA. Matson, Cole. Department of Environmental Science and Center for Reservoir and Aquatic Systems Research (CRASR) Baylor University Waco TX USA. Bickham, John W. Department of Wildlife & Fisheries Sciences Texas A&M University College Station TX USA.
Keywords: Evolutionary toxicology; contemporary evolution; dept.bio; ecotoxicology; peer-reviewed

Fitter frogs from polluted ponds: The complex impacts of human-altered environments - Brady, Steven P.; Zamora‐Camacho, Francisco J.; Eriksson, Fredrik A. A.; Goedert, Debora; Comas, Mar; Calsbeek, Ryan (Evolutionary Applications, 2019)
Human-modified habitats rarely yield outcomes that are aligned with conservation ideals. Landscapes that are subdivided by roads are no exception, precipitating negative impacts on populations due to fragmentation, pollution, and road kill. Although many populations in human-modified habitats show evidence for local adaptation, rarely does environmental change yield outright benefits for populations of conservation interest. Contrary to expectations, we report surprising benefits experienced by amphibian populations breeding and dwelling in proximity to roads. We show that roadside populations of the wood frog, Rana sylvatica, exhibit better locomotor performance and higher measures of traits related to fitness compared with frogs from less disturbed environments located further away from roads. These results contrast previous evidence for maladaptation in roadside populations of wood frogs studied elsewhere. Our results indicate that altered habitats might not be unequivocally detrimental and at times might contribute to metapopulation success. While the frequency of such beneficial outcomes remains unknown, their occurrence underscores the complexity of inferring consequences of environmental change.
15 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/025-521-919-587-494, pop00127 tex.type: [object Object]
Keywords: amphibian; dept.bio; human-modified habitats; maladaptation; peer-reviewed; road salt; roads

Immunofluorescence and image analysis pipeline for Drosophila motor neurons - Brown, Jeremy R; Brown, Jeremy R; Phongthachit, Chanpasith; Sulkowski, Mikolaj J (Biology Methods and Protocols, 2019)
The neuromuscular junction (NMJ) of larval Drosophila is widely used as a genetic model for basic neuroscience research. The presynaptic side of the NMJ is formed by axon terminals of motor neurons, the soma of which reside in the ventral ganglion of the central nervous system (CNS). Here we describe a streamlined protocol for dissection and immunostaining of the Drosophila CNS and NMJ that allows processing of multiple genotypes within a single staining tube. We also present a computer script called Automated Image Analysis with Background Subtraction which facilitates identification of motor nuclei, quantification of pixel intensity, and background subtraction. Together, these techniques provide a pipeline for neuroscientists to compare levels of different biomolecules in motor nuclei. We conclude that these methods should be adaptable to a variety of different cell and tissue types for the improvement of efficiency, reproducibility, and throughput during data quantification. © 2019 The Author(s) 2019. Published by Oxford University Press.
1 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/072-055-143-711-580 tex.type: [object Object]
Keywords: dept.bio; peer-reviewed

Is it time to begin prenatal/neonatal screening for autism risk? - Crawford, Sarah Adelaide (Global Journal of Pediatrics & Neonatal Care, 2019)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/111-162-730-836-405, pop00188
Keywords: dept.bio; peer-reviewed

Conservation through the lens of (mal)adaptation: Concepts and meta-analysis - Derry, Alison Margaret; Fraser, Dylan J.; Brady, Steven P.; Astorg, Louis; Lawrence, Elizabeth R.; Martin, Gillian K.; Matte, Jean-Michel; Dastis, Jorge Octavio Negrín; Paccard, Antoine; Barrett, Rowan D. H.; Chapman, Lauren J.; Lane, Jeffrey E.; et al. (Evolutionary Applications, 2019)
Evolutionary approaches are gaining popularity in conservation science, with diverse strategies applied in efforts to support adaptive population outcomes. Yet conservation strategies differ in the type of adaptive outcomes they promote as conservation goals. For instance, strategies based on genetic or demographic rescue implicitly target adaptive population states whereas strategies utilizing transgenerational plasticity or evolutionary rescue implicitly target adaptive processes. These two goals are somewhat polar: adaptive state strategies optimize current population fitness, which should reduce phenotypic and/or genetic variance, reducing adaptability in changing or uncertain environments; adaptive process strategies increase genetic variance, causing maladaptation in the short term, but increase adaptability over the long term. Maladaptation refers to suboptimal population fitness, adaptation refers to optimal population fitness, and (mal)adaptation refers to the continuum of fitness variation from maladaptation to adaptation. Here, we present a conceptual classification for conservation that implicitly considers (mal)adaptation in the short-term and long-term outcomes of conservation strategies. We describe cases of how (mal)adaptation is implicated in traditional conservation strategies, as well as strategies that have potential as a conservation tool but are relatively underutilized. We use a meta-analysis of a small number of available studies to evaluate whether the different conservation strategies employed are better suited toward increasing population fitness across multiple generations. We found weakly increasing adaptation over time for transgenerational plasticity, genetic rescue, and evolutionary rescue. Demographic rescue was generally maladaptive, both immediately after conservation intervention and after several generations. Interspecific hybridization was adaptive only in the F1 generation, but then rapidly leads to maladaptation. Management decisions that are made to support the process of adaptation must adequately account for (mal)adaptation as a potential outcome and even as a tool to bolster adaptive capacity to changing conditions.
41 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/005-301-824-151-444, pop00098 tex.type: [object Object]
Keywords: adaptation; demographic rescue; dept.bio; evolutionary rescue; gene flow; genetic rescue; hybridization; peer-reviewed; transgenerational plasticity; translocation

Ecological feedbacks stabilize a turf-dominated ecosystem at the southern extent of kelp forests in the Northwest Atlantic. - Feehan, Colette J; Grace, Sean P; Narvaez, Carla A (Scientific reports, 2019)
Temperate marine ecosystems globally are undergoing regime shifts from dominance by habitat-forming kelps to dominance by opportunistic algal turfs. While the environmental drivers of shifts to turf are generally well-documented, the feedback mechanisms that stabilize novel turf-dominated ecosystems remain poorly resolved. Here, we document a decline of kelp Saccharina latissima between 1980 and 2018 at sites at the southernmost extent of kelp forests in the Northwest Atlantic and their replacement by algal turf. We examined the drivers of a shift to turf and feedback mechanisms that stabilize turf reefs. Kelp replacement by turf was linked to a significant multi-decadal increase in sea temperature above an upper thermal threshold for kelp survival. In the turf-dominated ecosystem, 45% of S. latissima were attached to algal turf rather than rocky substrate due to preemption of space. Turf-attached kelp required significantly (2 to 4 times) less force to detach from the substrate, with an attendant pattern of lower survival following 2 major wave events as compared to rock-attached kelp. Turf-attached kelp allocated a significantly greater percentage of their biomass to the anchoring structure (holdfast), with a consequent energetic trade-off of slower growth. The results indicate a shift in community dominance from kelp to turf driven by thermal stress and stabilized by ecological feedbacks of lower survival and slower growth of kelp recruited to turf.
24 citations (Crossref) [2023-10-31] Place: England Feehan, Colette J. Department of Biology, Montclair State University, Montclair, NJ, 07043, USA. feehanc@montclair.edu. Grace, Sean P. Department of Biology and Werth Center for Coastal and Marine Studies, Southern Connecticut State University, New Haven, CT, 06515, USA. Narvaez, Carla A. Department of Biology, Villanova University, Villanova, PA, 19085, USA.
Keywords: *Forests; *Kelp/ph [Physiology]; *Marine Biology/mt [Methods]; *Seawater; Atlantic Ocean; Bays; Biomass; Climate Change; Forests; Kelp; Kelp/gd [Growth & Development]; Marine Biology; Rhode Island; Seasons; Seawater; Temperature; article; bay; biomass; climate change; dept.bio; driver; feedback system; forest; growth; development and aging; human; kelp; marine biology; physiology; procedures; sea water; season; temperature; temperature stress

Fitness attributes of bacterial and fungal seed endophytes of tall fescue - Roberts, Elizabeth Lewis; Mormile, Brendan; Adamchek, Christopher (Seed Endophytes: Biology and Biotechnology, 2019)
Increased fitness in tall fescue (Festuca arundinacea) is attributed to infection by Epichloë coenophiala. However, plant growth-promoting (PGP) bacteria also increase the fitness of many host plants, and PGP bacteria have been shown to dominate the phyllosphere and rhizosphere microbiome of E. coenophiala-infected (E+) tall fescue. Because E. coenophialum lives endophytically in tall fescue seeds, we hypothesized that PGP bacteria also live within the seeds and could provide fitness advantages to the host. Endophyte-infected (E+) and endophyte-free (E−) Kentucky-31 tall fescue seeds were surface sterilized to remove epiphytic bacteria. Surface sterilized and non-surface sterilized control plants of each type were cultivated for 6 weeks before withholding water to simulate drought. Normal watering was resumed after 4 days. Plant recovery of each group was measured by assigning a numerical value to tillers based on the state of decline. Surface-sterilized E+ plants were unable to recover as efficiently as E+ controls but outperformed both E− groups. Additionally, total 16S amplified DNA extracted from each seed type was analyzed with Illumina sequencing to assess the internal microbial communities from E+ and E− seeds as well as the seed coat microbiome. E+ seeds have lower diversity of endophytic bacterial species and are dominated by Pseudomonadaceae. Further, several of the seed endophytes are PGP bacterial strains.
Citation Key Alias: lens.org/004-523-831-959-190
Keywords: Clavicipitaceae; Epichloë coenophialum; Epichloë spp.; Plant growth promotion; Plant growth-promoting bacteria; Plant growthpromoting bacteria; Stress tolerance; Tall fescue; dept.bio

Colonization of the tsetse fly midgut with commensal Kosakonia cowanii Zambiae inhibits trypanosome infection establishment. - Weiss, Brian L; Maltz, Michele A; Vigneron, Aurelien; Wu, Yineng; Walter, Katharine S; O'Neill, Michelle B; Wang, Jingwen; Aksoy, Serap (PLOS Pathogens, 2019)
Tsetse flies (Glossina spp.) vector pathogenic trypanosomes (Trypanosoma spp.) in sub-Saharan Africa. These parasites cause human and animal African trypanosomiases, which are debilitating diseases that inflict an enormous socio-economic burden on inhabitants of endemic regions. Current disease control strategies rely primarily on treating infected animals and reducing tsetse population densities. However, relevant programs are costly, labor intensive and difficult to sustain. As such, novel strategies aimed at reducing tsetse vector competence require development. Herein we investigated whether Kosakonia cowanii Zambiae (Kco_Z), which confers Anopheles gambiae with resistance to Plasmodium, is able to colonize tsetse and induce a trypanosome refractory phenotype in the fly. Kco_Z established stable infections in tsetse's gut and exhibited no adverse effect on the fly's survival. Flies with established Kco_Z infections in their gut were significantly more refractory to infection with two distinct trypanosome species (T. congolense, 6% infection; T. brucei, 32% infection) than were age-matched flies that did not house the exogenous bacterium (T. congolense, 36% infected; T. brucei, 70% infected). Additionally, 52% of Kco_Z colonized tsetse survived infection with entomopathogenic Serratia marcescens, compared with only 9% of their wild-type counterparts. These parasite and pathogen refractory phenotypes result from the fact that Kco_Z acidifies tsetse's midgut environment, which inhibits trypanosome and Serratia growth and thus infection establishment. Finally, we determined that Kco_Z infection does not impact the fecundity of male or female tsetse, nor the ability of male flies to compete with their wild-type counterparts for mates. We propose that Kco_Z could be used as one component of an integrated strategy aimed at reducing the ability of tsetse to transmit pathogenic trypanosomes.
28 citations (Crossref) [2023-10-31] Place: United States Weiss, Brian L. Yale School of Public Health, Department of Epidemiology of Microbial Diseases, New Haven, Connecticut, United States of America. Maltz, Michele A. Southern Connecticut State University, New Haven, Connecticut, United States of America. Vigneron, Aurelien. Yale School of Public Health, Department of Epidemiology of Microbial Diseases, New Haven, Connecticut, United States of America. Wu, Yineng. Yale School of Public Health, Department of Epidemiology of Microbial Diseases, New Haven, Connecticut, United States of America. Walter, Katharine S. Yale School of Public Health, Department of Epidemiology of Microbial Diseases, New Haven, Connecticut, United States of America. O'Neill, Michelle B. Yale School of Public Health, Department of Epidemiology of Microbial Diseases, New Haven, Connecticut, United States of America. Wang, Jingwen. Yale School of Public Health, Department of Epidemiology of Microbial Diseases, New Haven, Connecticut, United States of America. Aksoy, Serap. Yale School of Public Health, Department of Epidemiology of Microbial Diseases, New Haven, Connecticut, United States of America. Erratum in (EIN)
Keywords: *Trypanosoma brucei brucei/py [Pathogenicity]; *Trypanosoma congolense/py [Pathogenicity]; *Trypanosomiasis; African/pc [Prevention & Control]; *Tsetse Flies/mi [Microbiology]; *Tsetse Flies/ps [Parasitology]; Adult; Africa South of the Sahara; Africa south of the Sahara; African trypanosomiasis; Animals; Anopheles; Anopheles gambiae; Anopheles/mi [Microbiology]; Article; Drosophila; Enterobacteriaceae; Female; Glossinidae; Humans; Male; Mosquito Vectors; Mosquito Vectors/mi [Microbiology]; Mosquito Vectors/ps [Parasitology]; Plasmodium; Serratia infection; Symbiosis; Trypanosoma brucei brucei; Trypanosoma congolense; Trypanosomiasis; African; Trypanosomiasis; African/me [Metabolism]; Trypanosomiasis; African/mi [Microbiology]; Trypanosomiasis; African/ps [Parasitology]; Tsetse Flies; adult; animal; animal experiment; animal model; animal tissue; antibacterial activity; ascorbic acid; bacterial load; blood flow; cell proliferation assay; clinical effectiveness; colony forming unit; controlled study; cysteine; dept.bio; disease predisposition; economics; female; fitness; fluorescence; genotype phenotype correlation; health program; human; immune system; male; metabolism; microbial colonization; microbiology; microscopy; mosquito vector; nonhuman; pH; parasitology; pathogenicity; peer-reviewed; peptidoglycan recognition protein; population; probability; semen analysis; survival analysis; symbiosis; trypanosomiasis

Antibacterial Assessment of Heteroaryl, Vinyl, Benzyl, and Alkyl Tetrazole Compounds. - Dudley, Joshua; Feinn, Liana; DeFrancesco, Heather; Lindsay, Erica; Coca, Adiel; Roberts, Elizabeth Lewis (Medicinal Chemistry, 2018)
Background: In previous reports, the antibacterial properties of certain tetrazole derivatives have been described. We have previously reported the antibac...
6 citations (Crossref) [2023-10-31] Place: Netherlands Dudley, Joshua. Chemistry Department, Southern Connecticut State University, 501 Crescent St, New Haven, Connecticut 06515, United States. Feinn, Liana. Chemistry Department, Southern Connecticut State University, 501 Crescent St, New Haven, Connecticut 06515, United States. DeFrancesco, Heather. Chemistry Department, Southern Connecticut State University, 501 Crescent St, New Haven, Connecticut 06515, United States. Lindsay, Erica. Chemistry Department, Southern Connecticut State University, 501 Crescent St, New Haven, Connecticut 06515, United States. Coca, Adiel. Chemistry Department, Southern Connecticut State University, 501 Crescent St, New Haven, Connecticut 06515, United States. Roberts, Elizabeth Lewis. Biology Department, Southern Connecticut State University, 501 Crescent St, New Haven, Connecticut 06515, United States.
Keywords: *Anti-Bacterial Agents/pd [Pharmacology]; *Tetrazoles/pd [Pharmacology]; 1 (1h tetrazol 5 yl)isoquinoline; 1; 2 di(1h tetrazol 5 yl)ethene; 2 (1h tetrazol 5 yl)pyrazine; 4 (1h tetrazol 5 yl)pyridine; 5 (1h pyrrol 2 yl) 1h tetrazole; 5 (2 methoxybenzyl) 1h tetrazole; 5 (furan 2 yl) 1h tetrazole; 5 (naphthalen 2 ylmethyl) 1h tetrazole; 5 (pyrrol 2 yl) 1h tetrazole; 5 (thiophen 3 yl) 1h tetrazole; 5 styryl 1h tetrazole; 5-substituted 1H-tetrazoles; (3 + 2) cycloaddition; Amoxicillin; Amoxicillin/pd [Pharmacology]; Anti-Bacterial Agents; Anti-Bacterial Agents/cs [Chemical Synthesis]; Antibacterial activity; Antimicrobial activity; Article; Cerium(III) chloride heptahydrate; Escherichia coli; Escherichia coli/de [Drug Effects]; Heterocycles; Microbial Sensitivity Tests; Microwave; Molecular Structure; Pseudomonas aeruginosa; Pseudomonas aeruginosa/de [Drug Effects]; Staphylococcus aureus; Staphylococcus aureus/de [Drug Effects]; Sulfamethoxazole; Sulfamethoxazole/pd [Pharmacology]; Tetrazoles; Tetrazoles/cs [Chemical Synthesis]; Trimethoprim; Trimethoprim/pd [Pharmacology]; amoxicillin; antibacterial activity; antibiotic agent; antiinfective agent; benzilic acid derivative; carbon nuclear magnetic resonance; chemical structure; controlled study; cotrimoxazole; dept.bio; dept.che; drug effect; heating; incubation time; microbial sensitivity test; minimum inhibitory concentration; nonhuman; peer-reviewed; phenyl(1h tetrazol 5 yl)methanol; priority journal; substitution reaction; sulfamethoxazole; synthesis; tetrazole derivative; trimethoprim; unclassified drug; vinyl derivative

The gene book: Explorations in the code of life - Crawford, Sarah Adelaide (Cognella Academic Publishing, 2018)
The Gene Book: Explorations in the Code of Life is designed to introduce undergraduate college students to foundational concepts in genetics. The text provides in-depth coverage of the essential principles of genetics, from Mendel to molecular gene therapy, and reads like a story, guiding readers through each of these areas in an interesting, engaging, and enlightening way. Milestone scientific discoveries introduce conceptual topics in each of the 10 chapters. The significance of each genetics paradigm is reinforced by the meaningful research context in which it is placed, whether the focus is single gene inheritance of disorders such as PKU and cystic fibrosis, or more complex genetic phenomena. Chromosomes, cell division, and cytogenetic disorders, including Down Syndrome and leukemia, are presented in a riveting historical context. In addition, the principles of molecular genetics are a major focus of this book. Students learn about the double helix, DNA replication, gene expression, mutation, natural selection, genomics, and the tools of molecular DNA analysis. Approachable and effective, The Gene Book is a highly readable comprehensive text on genetics principles designed to highlight essential concepts that make up their very core. The text is well suited to undergraduate genetics courses and can also be used as a primer for more advanced undergraduate and graduate courses in medial or molecular genetics.Sarah Adelaide Crawford is professor of genetics at Southern Connecticut State University. Dr. Crawford received a Ph.D. from Columbia University College of Physicians and Surgeons, an M.S. degree in biochemistry from Princeton University, and a B.S. degree from Marymount Manhattan College. She is director of the Cancer Biology Research Laboratory and the recently opened the Autism Research Laboratory at the Southern Connecticut State University.
Keywords: dept.bio

Genome sequences of Chancellor, Mitti, and Wintermute, three subcluster K4 phages isolated using Mycobacterium smegmatis mc ^2 155 - Edgington, Nicholas P.; Voshell, Stephanie M.; Ware, Vassie C.; Akoto, Francis F.; Alhout, Alexa A.; Atwal, Gurvina J.; Balyozian, John B.; Cadieux, Zachary A.; Chop, Brianna M.; Cresawn, Steven G.; Cudkevich, Netta; Faltine-Gonzalez, Dylan Z.; et al. (Genome Announcements, 2017)
Mycobacteriophages Chancellor, Mitti, and Wintermute infect Mycobacterium smegmatis mc2155 and are closely related to phages Cheetobro and Fionnbharth in subcluster K4. Genome sizes range from 57,697 bp to 58,046 bp. Phages are predicted to be temperate and to infect the pathogen Mycobacterium tuberculosis. © 2017 Edgington et al.
1 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/001-598-311-527-674, pop00117 tex.type: [object Object]
Keywords: Mycobacterium smegmatis; Mycobacterium tuberculosis; dept.bio; genome size; infectious agent; mycobacteriophage; nonhuman

Environmental exposure does not explain putative maladaptation in road-adjacent populations. - Brady, Steven P (Oecologia, 2017)
While the ecological consequences of roads are well described, little is known of their role as agents of natural selection, which can shape adaptive and maladaptive responses in populations influenced by roads. This knowledge gap persists despite a growing appreciation for the influence of evolution in human-altered environments. There, insights indicate that natural selection typically results in local adaptation. Thus, populations influenced by road-induced selection should evolve fitness advantages in their local environment. Contrary to this expectation, wood frog tadpoles from roadside populations show evidence of a fitness disadvantage, consistent with local maladaptation. Specifically, in reciprocal transplants, roadside populations survive at lower rates compared to populations away from roads. A key question remaining is whether roadside environmental conditions experienced by early stage embryos induce this outcome. This represents an important missing piece in evaluating the evolutionary nature of this maladaptation pattern. Here, I address this gap using a reciprocal transplant experiment designed to test the hypothesis that embryonic exposure to roadside pond water induces a survival disadvantage. Contrary to this hypothesis, my results show that reduced survival persists when embryonic exposure is controlled. This outcome indicates that the survival disadvantage is parentally mediated, either genetically and/or through inherited environmental effects. This result suggests that roadside populations are either truly maladapted or potentially locally adapted at later life stages. I discuss these interpretations, noting that regardless of mechanism, patterns consistent with maladaptation have important implications for conservation. In light of the pervasiveness of roads, further resolution explaining maladaptive responses remains a critical challenge in conservation.
14 citations (Crossref) [2023-10-31] Place: Germany Brady, Steven P. School of Forestry & Environmental Studies, Yale University, 370 Prospect Street, New Haven, CT, 06511, USA. brady.steven@gmail.com. Brady, Steven P. Biology Department, Southern Connecticut State University, New Haven, CT, 06515, USA. brady.steven@gmail.com.
Keywords: *Adaptation; Physiological; *Environmental Exposure; *Ranidae; *Selection; Genetic; Acclimatization; Adaptation; Physiological; Amphibia; Amphibians; Animals; Contemporary evolution; Environmental Exposure; Inherited environmental effects; Larva; Local adaptation; Rana sylvatica; Ranidae; Ranidae/ph [Physiology]; Runoff; Selection; Genetic; acclimatization; adaptation; amphibian; animal; dept.bio; embryonic development; environmental conditions; environmental effect; environmental exposure; evolutionary biology; fitness; frog; genetic selection; larva; local adaptation; natural selection; physiology; pond; population type; roadside environment; runoff; survival

Positive sire effects and adaptive genotype by environment interaction occur despite pattern of local maladaptation in roadside populations of an amphibian - Brady, Steven P.; Goedert, Debora (Copeia, 2017)
The global road network causes many negative ecological effects. Contrasting our knowledge of these effects, insights into evolutionary consequences of roads remain undeveloped. Here, we study a suite of populations of the Wood Frog that appear to be evolving maladaptively in response to road-adjacency. Specifically, when raised together in roadside pools, roadside populations survive at lower rates compared to populations away from roads. To begin to understand the cause of this survival disadvantage, we investigated potential parental and genetic sources of maladaptation. First, to assess whether parental effects might induce maladaptation, we measured adult body weight to length ratio ('relative weight') and its influence on offspring survival in a reciprocal transplant experiment across 12 populations. Next, to assess whether genetic effects might limit adaptive responses in offspring, we estimated genetic correlations between environments for survival and fitness-related traits. We found that relative weight was higher in roadside populations and, for males, had a positive influence on offspring survival. This demonstrates a novel transgenerational effect of Wood Frog adult males but suggests that this effect is not causing maladaptive survival. Genetic correlations indicated that a subset of roadside genotypes respond adaptively to road-adjacency despite population level maladaptive survival. This suggests that metapopulation dynamics and/or high levels of nonadditive genetic variance may be limiting adaptation or that insufficient time has elapsed for adaptation to occur. Together, these results highlight the complexity and scale of responses to a pervasive feature of landscape alteration revealed by evolutionary approaches.
6 citations (Crossref) [2023-10-31]
Keywords: Amphibia; Rana sylvatica; adaptation; amphibian; dept.bio; environmental conditions; evolutionary biology; frog; genotype; genotype-environment interaction; heritability; local adaptation; metapopulation; population type; roadside environment; survival

How valid are old species lists? How archived samples can be used to update Ephemeroptera biodiversity information for northern Canada - Giberson, Donna J.; Burian, Steven K. (The Canadian Entomologist, 2017)
Abstract Broad-scale aquatic insect ecological studies are an important potential source of biodiversity information, though taxa lists may contain outdated names or be incompletely or incorrectly identified. We re-examined over 12 000 archived Ephemeroptera (mayfly) specimens from a large environmental assessment project (Mackenzie Valley pipeline study) in Yukon and the Northwest Territories, Canada (1971–1973) and compared the results to data from five recent (post-2000) collecting expeditions. Our goals were to update the species list for Ephemeroptera for Yukon and the Northwest Territories, and to evaluate the benefits of retaining and re-examining ecological samples to improve regional biodiversity information, particularly in isolated or inaccessible areas. The original pipeline study specimen labels reported 17 species in 25 genera for the combined Yukon and Northwest Territories samples, of which six species and 15 genera are still valid. Re-examination of specimens resulted in 45 species in 29 genera, with 14 and seven newly recorded species for Northwest Territories and Yukon, respectively. The recent collecting resulted in 50 species, 29 of which were different from the pipeline study, and five of which were new territorial records (Northwest Territories: four species; Yukon: one species). Re-examination of archived ecological specimens provides a cost-effective way to update regional biodiversity information.
4 citations (Crossref) [2023-10-31]
Keywords: Canada; Ephemeroptera; Hexapoda; Mackenzie Valley; Northwest Territories; Yukon Territory; aquatic organism; biodiversity; dept.bio; environmental assessment; information; mayfly; new record; sampling; species inventory

Range extensions for recently described North American species of Acentrella Bengtsson (Insecta: Ephemeroptera: Baetidae) - Webb, Jeffrey M.; Burian, Steven K. (Check List, 2017)
New state records are provided for two recently described species of North American Acentrella Bengtsson, 1912. Acentrella nadineae McCafferty, Waltz & Webb, 2009 is newly reported from Connecticut, Massachusetts, and Minnesota, and A. rallatoma Burian & Myers, 2011 is reported from Minnesota.
1 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/103-027-562-874-776, pop00306 tex.type: [object Object]
Keywords: Mayfly; Nearctic; New records; Range extension; dept.bio; mayfly; new records; range extension

Antimicrobial evaluation of 5-substituted aryl 1H-tetrazoles - Feinn, Liana; Dudley, Joshua; Coca, Adiel; Roberts, Elizabeth Lewis (Medicinal Chemistry, 2017)
Background: Tetrazole derivatives such as 1-substituted dinitrobenzyl tetrazoles and their oxa and selanyl analogs have previously been studied against drug-susceptible and multidrugresistant mycobacteria. In addition, other tetrazole derivatives have been shown to inhibit CTX-M class A μ-lactamases. Objective: To study the antibacterial activity of 5-substituted aryl 1H-tetrazole derivatives. Methods: The antibacterial activity of several known 5-substituted aryl 1H-tetrazole derivatives was evaluated against Staphylococcus aureus, Escherichia coli, and Pseudomonas aeruginosa. The activity was assessed by determining the minimum inhibitory concentration of these tetrazole derivatives and comparing them to the known antibiotics amoxicillin, trimethoprim and sulfamethoxazole. Results: Some derivatives showed significant antibacterial activity with the most active derivatives exhibiting a minimum inhibitory concentration (MIC) of 125-250 μg/mL against Staphylococcus aureus and Escherichia coli. Using some of these tetrazole compounds in combination with trimethoprim led to a synergistic effect that gave MIC values ranging from 0.24-1.95 μg/mL against Escherichia coli and 3.91-31.3 μg/mL against Staphylococcus aureus. The tetrazole derivatives were prepared in an isopropanol/water mixture using microwave heating at 160 °C for 1h. The cycloaddition between organonitriles and sodium azide was catalyzed by indium chloride. Conclusion: This study shows a significant synergistic effect between the tetrazole compounds tested and trimethoprim which could be used to potentially develop new antibacterial agents. © 2017 Bentham Science Publishers.
4 citations (Crossref) [2023-10-31]
Keywords: 1; 4 di(tetrazol 5 yl)benzene; 2 propanol; 4 acetylbenzonitrile; 4 acetylbenzotetrazole; 4 bromobenzotetrazole; 5 substituted aryl tetrazole derivative; 5-substituted 1H-tetrazoles; Antibacterial activity; Antimicrobial activity; Article; Escherichia coli; Indium chloride; Microwave chemistry; Pseudomonas aeruginosa; Staphylococcus aureus; [2 + 3] cycloaddition; amoxicillin; antibacterial activity; antibiotic agent; catalysis; clinical assessment; comparative study; controlled study; cycloaddition; dept.bio; dept.che; drug effect; drug screening; drug structure; indium chloride; microwave cooking; minimum inhibitory concentration; nonhuman; peer-reviewed; priority journal; reaction analysis; sodium azide; sulfamethoxazole; tetrazole derivative; trimethoprim; unclassified drug; water

Winter Quiescence, Growth Rate, and the Release from Competition in the Temperate Scleractinian Coral Astrangia poculata (Ellis & Solander 1786) - Grace, Sean (Northeastern Naturalist, 2017)
I examined winter quiescence (dormancy), growth rate, and competition in the scleractinian coral Astrangia poculata (Northern Star-coral) at an intertidal and a subtidal site in Rhode Island. I observed the onset, duration, and cessation of quiescence from November 2013 to May 2014 and noted when coral tentacles no longer exhibited tactile responses, which I used as a proxy for quiescence. Results demonstrated that intertidal corals entered quiescence in December 2013, when air/water temperatures ranged from 0.71 °C to 5.7 °C, whereas subtidal populations entered quiescence in January when water temperatures ranged from 3.4 °C to 4.3 °C. Corals exited quiescence at similar temperatures (6.0–8.5 °C), again doing so earlier in the intertidal than subtidal populations (April and May 2014, respectively). Corals at both sites grew (added polyps) over the course of the study, but during quiescence, growth ceased in subtidal corals, and intertidal corals lost peripheral polyps. Competitive interactions between Northern Star-coral and the tunicate Didemnum vexillum (Carpet Tunicate) decreased during quiescence with a corresponding increase in “halo” width around each coral. I observed no change in halo-width between coral and the sponge Cliona celata (Red Boring Sponge). All corals examined exhibited winter quiescence, grew during the course of the study, and were released from competition with Carpet Sea-squirt Tunicate; no change in competition with Red Boring Sponge was observed.
18 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/116-846-890-414-593, pop00163 tex.type: [object Object]
Keywords: dept.bio; peer-reviewed

Prophage-mediated defence against viral attack and viral counter-defence. - Dedrick, Rebekah M; Jacobs-Sera, Deborah; Bustamante, Carlos A Guerrero; Garlena, Rebecca A; Mavrich, Travis N; Pope, Welkin H; Reyes, Juan C Cervantes; Russell, Daniel A; Adair, Tamarah; Alvey, Richard; Bonilla, J Alfred; Bricker, Jerald S; et al. (Nature Microbiology, 2017)
Temperate phages are common, and prophages are abundant residents of sequenced bacterial genomes. Mycobacteriophages are viruses that infect mycobacterial hosts including Mycobacterium tuberculosis and Mycobacterium smegmatis, encompass substantial genetic diversity and are commonly temperate. Characterization of ten Cluster N temperate mycobacteriophages revealed at least five distinct prophage-expressed viral defence systems that interfere with the infection of lytic and temperate phages that are either closely related (homotypic defence) or unrelated (heterotypic defence) to the prophage. Target specificity is unpredictable, ranging from a single target phage to one-third of those tested. The defence systems include a single-subunit restriction system, a heterotypic exclusion system and a predicted (p)ppGpp synthetase, which blocks lytic phage growth, promotes bacterial survival and enables efficient lysogeny. The predicted (p)ppGpp synthetase coded by the Phrann prophage defends against phage Tweety infection, but Tweety codes for a tetrapeptide repeat protein, gp54, which acts as a highly effective counter-defence system. Prophage-mediated viral defence offers an efficient mechanism for bacterial success in host-virus dynamics, and counter-defence promotes phage co-evolution.
175 citations (Crossref) [2023-10-31] Place: England Dedrick, Rebekah M. Department of Biological Sciences, University of Pittsburgh, Pittsburgh, Pennsylvania 15260, USA. Jacobs-Sera, Deborah. Department of Biological Sciences, University of Pittsburgh, Pittsburgh, Pennsylvania 15260, USA. Bustamante, Carlos A Guerrero. Department of Biological Sciences, University of Pittsburgh, Pittsburgh, Pennsylvania 15260, USA. Garlena, Rebecca A. Department of Biological Sciences, University of Pittsburgh, Pittsburgh, Pennsylvania 15260, USA. Mavrich, Travis N. Department of Biological Sciences, University of Pittsburgh, Pittsburgh, Pennsylvania 15260, USA. Pope, Welkin H. Department of Biological Sciences, University of Pittsburgh, Pittsburgh, Pennsylvania 15260, USA. Reyes, Juan C Cervantes. Department of Biological Sciences, University of Pittsburgh, Pittsburgh, Pennsylvania 15260, USA. Russell, Daniel A. Department of Biological Sciences, University of Pittsburgh, Pittsburgh, Pennsylvania 15260, USA. Adair, Tamarah. Department of Biology, Baylor University, Waco, Texas 76798, USA. Alvey, Richard. Biology Department, Illinois-Wesleyan University, Bloomington, Illinois 61702, USA. Bonilla, J Alfred. Biology Department, University of Wisconsin-River Falls, River Falls, Wisconsin 54016, USA. Bricker, Jerald S. Biology Department, Nebraska-Wesleyan University, Lincoln, Nebraska 68504, USA. Brown, Bryony R. Department of Biological Sciences, University of Pittsburgh, Pittsburgh, Pennsylvania 15260, USA. Byrnes, Deanna. Biology Department, Carthage College, Kenosha, Wisconsin 53140, USA. Cresawn, Steven G. Biology Department, James Madison University, Harrisonburg, Virginia 22807, USA. Davis, William B. School of Molecular Biosciences, Washington State University Pullman, Washington 99164, USA. Dickson, Leon A. Department of Biology, Howard University, Washington, Washington DC 20059, USA. Edgington, Nicholas P. Biology Department, Southern Connecticut State University, New Haven, Connecticut 06515, USA. Findley, Ann M. Biology, School of Sciences, University of Louisiana at Monroe, Monroe, Louisiana 71209, USA. Golebiewska, Urszula. Biological Sciences and Geology, Queensborough Community College, Bayside, New York 11364, USA. Grose, Julianne H. Biology Department, Brigham Young University, Provo, Utah 84602, USA. Hayes, Cory F. Department of Biological Sciences, University of Pittsburgh, Pittsburgh, Pennsylvania 15260, USA. Hughes, Lee E. Biological Sciences, University of North Texas, Denton, Texas 76203, USA. Hutchison, Keith W. Molecular and Biomedical Sciences, University of Maine, Honors College, Orono, Maine 04469, USA. Isern, Sharon. Department of Biological Sciences, Florida Gulf Coast University, Fort Myers, Florida 33965, USA. Johnson, Allison A. Biology Department, Virginia Commonwealth University, Richmond, Virginia 23284, USA. Kenna, Margaret A. Biological Sciences, Lehigh University, Bethlehem, Pennsylvania 18015, USA. Klyczek, Karen K. Biology Department, University of Wisconsin-River Falls, River Falls, Wisconsin 54016, USA. Mageeney, Catherine M. Biological Sciences, Lehigh University, Bethlehem, Pennsylvania 18015, USA. Michael, Scott F. Department of Biological Sciences, Florida Gulf Coast University, Fort Myers, Florida 33965, USA. Molloy, Sally D. Molecular and Biomedical Sciences, University of Maine, Honors College, Orono, Maine 04469, USA. Montgomery, Matthew T. Department of Biological Sciences, University of Pittsburgh, Pittsburgh, Pennsylvania 15260, USA. Neitzel, James. Biology Department, The Evergreen State College, Olympia, Washington 98502, USA. Page, Shallee T. Division of Environmental and Biological Sciences, University of Maine-Machias, Machias, Maine 04654, USA. Pizzorno, Marie C. Biology Department, Bucknell University, Lewisburg, Pennsylvania 17837, USA. Poxleitner, Marianne K. Biology Department, Gonzaga University, Spokane, Washington 99258, USA. Rinehart, Claire A. Biology Department, Western Kentucky University, Bowling Green, Kentucky 42101, USA. Robinson, Courtney J. Department of Biology, Howard University, Washington, Washington DC 20059, USA. Rubin, Michael R. Biology Department, University of Puerto Rico-Cayey, Cayey, Puerto Rico 00736, USA. Teyim, Joseph N. Biological Sciences, Lehigh University, Bethlehem, Pennsylvania 18015, USA. Vazquez, Edwin. Biology Department, University of Puerto Rico-Cayey, Cayey, Puerto Rico 00736, USA. Ware, Vassie C. Biological Sciences, Lehigh University, Bethlehem, Pennsylvania 18015, USA. Washington, Jacqueline. Department of Biology and Chemistry, Nyack College, Nyack, New York 10960, USA. Hatfull, Graham F. Department of Biological Sciences, University of Pittsburgh, Pittsburgh, Pennsylvania 15260, USA.
Keywords: *Mycobacteriophages/ph [Physiology]; *Mycobacterium smegmatis/vi [Virology]; *Mycobacterium tuberculosis/vi [Virology]; *Prophages/ph [Physiology]; DNA; Viral; DNA; Viral/ge [Genetics]; Genetic Variation; Genome; Bacterial; Genome; Viral; Ligases; Ligases/ge [Genetics]; Lysogeny; Mycobacteriophages; Mycobacteriophages/ge [Genetics]; Mycobacterium smegmatis; Mycobacterium smegmatis/ge [Genetics]; Mycobacterium tuberculosis; Mycobacterium tuberculosis/ge [Genetics]; Phylogeny; Prophages; Prophages/en [Enzymology]; Prophages/ge [Genetics]; Viral Proteins; Viral Proteins/ge [Genetics]; bacterial genome; dept.bio; enzymology; genetic variation; genetics; guanosine 3'; 5'-polyphosphate synthetases; ligase; lysogenization; mycobacteriophage; phylogeny; physiology; prophage; viral protein; virology; virus DNA; virus genome

Physiological consequences of exposure to salinized roadside ponds on wood frog larvae and adults - Hall, Emily M.; Brady, Steven P.; Mattheus, Nichole M.; Earley, Ryan L.; Diamond, Molly; Crespi, Erica J. (Biological Conservation, 2017)
40 citations (Crossref) [2023-10-31]
Keywords: dept.bio

Evolutionary toxicology: Toward a unified understanding of life's response to toxic chemicals. - Brady, Steven P; Monosson, Emily; Matson, Cole W; Bickham, John W (Evolutionary Applications, 2017)
45 citations (Crossref) [2023-10-31] Place: England Brady, Steven P. Biology Department Southern Connecticut State University New Haven CT USA. Monosson, Emily. The Ronin Institute for Independent Scholars and Department of Environmental Conservation University of Massachusetts Amherst MA USA. Matson, Cole W. Department of Environmental Science and Center for Reservoir and Aquatic Systems Research (CRASR) Baylor University Waco TX USA. Bickham, John W. Department of Wildlife & Fisheries Sciences Texas A&M University College Station College Station TX USA.
Keywords: dept.bio; peer-reviewed

Road ecology: shifting gears toward evolutionary perspectives - Brady, Steven P.; Richardson, Jonathan L. (Frontiers in Ecology and the Environment, 2017)
Recent advances in understanding the often rapid pace of evolution are reshaping our view of organisms and their capacity to cope with environmental change. Though evolutionary perspectives have gained traction in many fields of conservation, road ecology is not among them. This is surprising because roads are pervasive landscape features that generate intense natural selection. The biological outcomes from these selection pressures – whether adaptive or maladaptive – can have profound consequences for population persistence. We argue that studying evolutionary responses is critical to accurately understand the impacts of roads. Toward that end, we describe the basic tenets and relevance of contemporary evolution and showcase the few examples where it has been documented in road ecology. We outline practical ways that road ecologists can estimate and interpret evolutionary responses in their research. Finally, we suggest priority research topics and discuss how evolutionary insights can inform conservation in landscapes traversed by roads.
42 citations (Crossref) [2023-10-31]
Keywords: dept.bio; peer-reviewed

Incorporating evolutionary insights to improve ecotoxicology for freshwater species - Brady, Steven P.; Richardson, Jonathan L.; Kunz, Bethany K. (Evolutionary Applications, 2017)
Ecotoxicological studies have provided extensive insights into the lethal and sublethal effects of environmental contaminants. These insights are critical for environmental regulatory frameworks, which rely on knowledge of toxicity for developing policies to manage contaminants. While varied approaches have been applied to ecotoxicological questions, perspectives related to the evolutionary history of focal species or populations have received little consideration. Here, we evaluate chloride toxicity from the perspectives of both macroevolution and contemporary evolution. First, by mapping chloride toxicity values derived from the literature onto a phylogeny of macroinvertebrates, fish, and amphibians, we tested whether macroevolutionary relationships across species and taxa are predictive of chloride tolerance. Next, we conducted chloride exposure tests for two amphibian species to assess whether potential contemporary evolutionary change associated with environmental chloride contamination influences chloride tolerance across local populations. We show that explicitly evaluating both macroevolution and contemporary evolution can provide important and even qualitatively different insights from those obtained via traditional ecotoxicological studies. While macroevolutionary perspectives can help forecast toxicological end points for species with untested sensitivities, contemporary evolutionary perspectives demonstrate the need to consider the environmental context of exposed populations when measuring toxicity. Accounting for divergence among populations of interest can provide more accurate and relevant information related to the sensitivity of populations that may be evolving in response to selection from contaminant exposure. Our data show that approaches accounting for and specifically examining variation among natural populations should become standard practice in ecotoxicology.
34 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/032-040-409-668-282, pop00101 tex.type: [object Object]
Keywords: LC50; acute exposure; adaptation; chloride; dept.bio; maladaptation; peer-reviewed; road salt runoff

Autism risk: What do vaccines have to do with - Crawford, Sarah Adelaide (Academic Journal of Pediatrics & Neonatology, 2017)
Keywords: dept.bio; ⚠️ Invalid DOI

Using time dynamically in static intervals: Does it close the achievement gap? - Grace, Lori (Learning Environments Research, 2017)
A mixed-methods study was undertaken with 118 biology students in two urban high schools. A Student-Centered Adaptable Learning Environment (SCALE) was created to improve engagement from affective and cognitive perspectives using choice, creativity and technological allowances. Results demonstrated that fast and slow learners are generally separated by about 30 min in terms of inputting speeds, but can be as much as 65 min apart from one another. Given that traditional classrooms afford students only 45 min in which to learn, static time could have become a source of inequity in public schools. SCALE optimally allowed for the dynamic use of time in constrained periods, therefore reducing and even eliminating any negative relationships between speed of learning and resultant achievement gains in the block setting. Especially benefitting from their ability to maneuver were the slowest learners, who showed the largest achievement improvements in either time interval amongst ability groupings. As learning speed can be the most critical contributing component of resultant educational outcomes, providing students the ability to use time dynamically should be considered as a feasible solution to helping teachers reestablish equity in mixed-ability classrooms in public schools. © 2017, Springer Science+Business Media Dordrecht.
1 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/056-365-031-456-996 tex.type: [object Object]
Keywords: Cognitive levelling; Dynamic time; Educational technology; Learning equity; Learning speed gap; Psychosocial learning environments; dept.bio